A coastal altimetry retracking strategy based on waveform classification and sub-waveform extraction - Le Yang; Mingsen Lin; Qinhuo Liu; Delu Pan (International Journal of Remote Sensing, 2012)

Comparison of MODIS land surface temperature and ground-based observed air temperature in complex topography - Yen-Jen Lai; Ching-Feng Li; Po-Hsiung Lin; Tsong-Hue Wey; Cheng-Sheng Chang (International Journal of Remote Sensing, 2012)

Synthesis and antitumour activities of a novel class of dehydroabietylamine derivatives - Yong Chen; Zhong-Xiang Lin; Ai-Min Zhou (Natural Product Research, 2012)

Effects of Sub-soil Drip Fertigation on Sugarcane in Field Conditions - Gui-Fen Chen; Qi-Zhan Tang; Yang-Rui Li; Yu-Yi Huang; Bin Liu; Lin Xu; Hai-Rong Huang (Sugar Tech, 2012)

Assessment and zoning of eco-environmental sensitivity for a typical developing province in China - Xiaoyan Dai; Zhuo Li; Shouyi Lin; Wencheng Xu (Stochastic Environmental Research and Risk Assessment, 2012)

Conservation and characterization of unique porcine interstitial telomeric sequences - GuangZhen Ji; Kai Liu; ChengBin Chen; WeiMin Ruan; Christina Glytsou; Yang Yang; Maja Okuka; WenQing Song; Sarantis Gagos; Ning Li; Lin Liu (Science China Life Sciences, 2012)

Thaxtomin A-deficient endophytic Streptomyces sp. enhances plant disease resistance to pathogenic Streptomyces scabies - Lan Lin; Hui Ming Ge; Tong Yan; Yan Hua Qin; Ren Xiang Tan (Planta, 2012)

The novel Solanum tuberosum calcium dependent protein kinase, StCDPK3, is expressed in actively growing organs - Carolina Grandellis; Verónica Giammaria; Magalí Bialer; Franco Santin; Tian Lin; David J. Hannapel; Rita M. Ulloa (Planta, 2012)

PhPT4 Is a Mycorrhizal-Phosphate Transporter Suppressed by Lysophosphatidylcholine in Petunia Roots - Zhijing Tan; Yuanlei Hu; Zhongping Lin (Plant Molecular Biology Reporter, 2012)

Expression of Maize Gene Encoding C4-Pyruvate Orthophosphate Dikinase (PPDK) and C4-Phosphoenolpyruvate Carboxylase (PEPC) in Transgenic Arabidopsis - Yu-Min Wang; Wei-Gang Xu; Lin Hu; Lei Zhang; Yan Li; Xi-He Du (Plant Molecular Biology Reporter, 2012)

The Bxb1 Recombinase Mediates Site-Specific Deletion in Transgenic Wheat - Ann Blechl; Jeanie Lin; Min Shao; Roger Thilmony; James Thomson (Plant Molecular Biology Reporter, 2012)

Characterization and Expression of a Phytochelatin Synthase Gene in Birch-leaf Pear (Pyrus betulaefolia Bunge) - You Hong Chang; Hui Li; Yu Cong; Jing Lin; Bao Long Sheng (Plant Molecular Biology Reporter, 2012)

Transcriptomic changes and signalling pathways induced by arsenic stress in rice roots - Tsai-Lien Huang; Quynh Thi Thuy Nguyen; Shih-Feng Fu; Chung-Yi Lin; Ying-Chih Chen; Hao-Jen Huang (Plant Molecular Biology, 2012)

Combinational transformation of three wheat genes encoding fructan biosynthesis enzymes confers increased fructan content and tolerance to abiotic stresses in tobacco - Xiaomin Bie; Ke Wang; Maoyun She; Lipu Du; Shuangxi Zhang; Jiarui Li; Xiang Gao; Zhishan Lin; Xingguo Ye (Plant Cell Reports, 2012)

A Survey of Applications of Biological Products for Drug Interference of Immunogenicity Assays - Yow-Ming C. Wang; Lanyan Fang; Lin Zhou; Jie Wang; Hae-Young Ahn (Pharmaceutical Research, 2012)

A Mucormycosis Case in a Cirrhotic Patient Successfully Treated with Posaconazole and Review of Published Literature - Shang-Yi Lin; Po-Liang Lu; Kun-Bow Tsai; Chun-Yu Lin; Wei-Ru Lin; Tun-Chieh Chen; Ya-Ting Chang; Chung-Hao Huang; Chi-Yu Chen; Chung-Chih Lai; Yen-Hsu Chen (Mycopathologia, 2012)

Identification of a new gene encoding 5-enolpyruvylshikimate-3-phosphate synthase using genomic library construction strategy - Chang-Yan Zhou; Yong-Sheng Tian; Zhi-Sheng Xu; Wei Zhao; Chen Chen; Wen-Hua Bao; Lin Bian; Run Cai; Ai-Zhong Wu (Molecular Biology Reports, 2012)

Identification of key pathways and transcription factors related to Parkinson disease in genome wide - Bin Zhang; Cuiping Xia; Qunfeng Lin; Jie Huang (Molecular Biology Reports, 2012)

Interactive cellular proteins related to classical swine fever virus non-structure protein 2 by yeast two-hybrid analysis - Kai Kang; Kangkang Guo; Qinhai Tang; Yanming Zhang; Jiang Wu; Weiwei Li; Zhi Lin (Molecular Biology Reports, 2012)

Interactions of interleukin-12A and interleukin-12B polymorphisms on the risk of intracranial aneurysm - Li-Juan Li; Xin-Min Pan; Xiutian Sima; Zhao-Hui Li; Lu-Shun Zhang; Hong Sun; Yi Zhu; Wei-Bo Liang; Lin-Bo Gao; Lin Zhang (Molecular Biology Reports, 2012)

Structure and evolution of the mitochondrial genome of Exorista sorbillans: the Tachinidae (Diptera: Calyptratae) perspective - Yuan-jun Shao; Xian-qiong Hu; Guang-da Peng; Rui-xian Wang; Rui-na Gao; Chao Lin; Wei-de Shen; Rui Li; Bing Li (Molecular Biology Reports, 2012)

Expression profiles of key candidate genes involved in steroidogenesis during follicular atresia in the pig ovary - Zengxiang Pan; Jinbi Zhang; Fei Lin; Xueshan Ma; Xuguang Wang; Honglin Liu (Molecular Biology Reports, 2012)

A real-time PCR to detect and analyze virulent EMCV loads in sows and piglets - Zhao Wang; Yebing Liu; Wencheng Lin; Shangjin Cui (Molecular Biology Reports, 2012)

Subcellular localization of different regions of porcine Six1 gene and its expression analysis in C2C12 myoblasts - Wangjun Wu; Zhuqing Ren; Chao Chen; Yang Liu; Lin Zhang; Zhe Chao; Bo Zuo; Dequan Xu; Minggang Lei; Yuanzhu Xiong (Molecular Biology Reports, 2012)

Age-dependent down-regulation of DNA polymerase δ1 in human lymphocytes - Jin-Ling Wang; Hong-Lin Guo; Pei-Chang Wang; Chen-Geng Liu (Molecular and Cellular Biochemistry, 2012)

High density lipoprotein cholesterol promotes the proliferation of bone-derived mesenchymal stem cells via binding scavenger receptor-B type I and activation of PI3K/Akt, MAPK/ERK1/2 pathways - Jianfeng Xu; Juying Qian; Xinxing Xie; Li Lin; Jianying Ma; Zheyong Huang; Mingqiang Fu; Yunzeng Zou; Junbo Ge (Molecular and Cellular Biochemistry, 2012)

Alteration of discoidin domain receptor-2 expression: possible role in peroxynitrite-induced apoptosis in human cerebral vascular smooth muscle cells - Lin Li; Zhiyong Yue; Xiaojuan Wan; Guodong Zhang; Shasha Song; Xiaohui Bai; Yulian Jiao; Yuanrong Ju; Jianfeng Li (Molecular & Cellular Toxicology, 2012)

Analysis of carbamazepine serum by differential pulse voltammetry (DPV) and comparison with fluorescence polarization immunoassay (FPIA): an animal study - W. Y. Lin; M. L. Pan; H. Y. Wang; Y. O. Su; P. W. Huang (Medicinal Chemistry Research, 2012)

Bacterial and Archaeal Symbionts in the South China Sea Sponge Phakellia fusca: Community Structure, Relative Abundance, and Ammonia-Oxidizing Populations - Minqi Han; Fang Liu; Fengli Zhang; Zhiyong Li; Houwen Lin (Marine Biotechnology, 2012)

Low-intensity pulsed ultrasound therapy: a potential strategy to stimulate tendon-bone junction healing - Zhi-min Ying; Tiao Lin; Shi-gui Yan (Journal of Zhejiang University-SCIENCE B, 2012)

Combining proteomics, serum biomarkers and bioinformatics to discriminate between esophageal squamous cell carcinoma and pre-cancerous lesion - Xiao-hui Zhai; Jie-kai Yu; Chen Lin; Li-dong Wang; Shu Zheng (Journal of Zhejiang University-SCIENCE B, 2012)

Docetaxel-loaded liposomes: preparation, pH sensitivity, Pharmacokinetics, and tissue distribution - Hong Zhang; Rui-ying Li; Xia Lu; Zhen-zhen Mou; Gui-mei Lin (Journal of Zhejiang University-SCIENCE B, 2012)

Volatile profile analysis and quality prediction of Longjing tea (Camellia sinensis) by HS-SPME/GC-MS - Jie Lin; Yi Dai; Ya-nan Guo; Hai-rong Xu; Xiao-chang Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Haem Oxygenase-1 is Involved in Hydrogen Sulfide-induced Cucumber Adventitious Root Formation - Yu-Ting Lin; Mei-Yue Li; Wei-Ti Cui; Wei Lu; Wen-Biao Shen (Journal of Plant Growth Regulation, 2012)

Efficient multi-site-directed mutagenesis directly from genomic template - Fengtao Luo; Xiaolan Du; Tujun Weng; Xuan Wen; Junlan Huang; Lin Chen (Journal of Biosciences, 2012)

Integrate-and-fire vs Poisson models of LGN input to V1 cortex: noisier inputs reduce orientation selectivity - I-Chun Lin; Dajun Xing; Robert Shapley (Journal of Computational Neuroscience, 2012)

Characterisation of the Virulence Factors and Genetic Types of Methicillin Susceptible Staphylococcus aureus from Patients and Healthy Individuals - King-Ting Lim; Yasmin Abu Hanifah; Mohd Yasim Mohd Yusof; Kwai-Lin Thong (Indian Journal of Microbiology, 2012)

Cathepsin B SNPs elevate the pathological development of oral cancer and raise the susceptibility to carcinogen-mediated oral cancer - Mu-Kuan Chen; Shih-Chi Su; Chiao-Wen Lin; Chiung-Man Tsai; Shun-Fa Yang; Chia-Jui Weng (Human Genetics, 2012)

Regulation of pericellular proteolysis by hepatocyte growth factor activator inhibitor type 1 (HAI-1) in trophoblast cells - Kazuyo Kohama; Makiko Kawaguchi; Tsuyoshi Fukushima; Chen-Yong Lin; Hiroaki Kataoka (Human Cell, 2012)

Invading time of Colletotrichum gloeosporioides affects fruit drop and infection rate in ‘Irwin’ mango (Mangifera indica L.) - Chin-Hsing Chang; Tzong-Shyan Lin; Wen-Ju Yang (Horticulture, Environment, and Biotechnology, 2012)

Molecular characterization and expression pattern of insulin-like growth factor binding protein-3 (IGFBP-3) in common carp, Cyprinus carpio - Wenbo Chen; Haoran Lin; Wensheng Li (Fish Physiology and Biochemistry, 2012)

Establishment and characterization of a new fish cell line from head kidney of half-smooth tongue sole (Cynoglossus semilaevis) - Yuan Zheng; Na Wang; Ming-Shu Xie; Zhen-Xia Sha; Song-Lin Chen (Fish Physiology and Biochemistry, 2012)

Heat acclimation decreased oxidative DNA damage resulting from exposure to high heat in an occupational setting - Yung-Kai Huang; Che-Wei Lin; Chen-Chen Chang; Pai-Fen Chen; Chien-Jen Wang; Yu-Mei Hsueh; Hung-Che Chiang (European Journal of Applied Physiology, 2012)

Sobol’ sensitivity analysis of parameters in the common land model for simulation of water and energy fluxes - Jianhui Xu; Hong Shu; Hongnan Jiang; Lin Dong (Earth Science Informatics, 2012)

Infusion of Endothelial Progenitor Cells Accelerates Hematopoietic and Immune Reconstitution, and Ameliorates the Graft-Versus-Host Disease After Hematopoietic Stem Cell Transplantation - Lingyu Zeng; Chong Chen; Guoliang Song; Zhiling Yan; Shijuan Xu; Lu Jia; Shuang Ding; Jiang Cao; Wei Chen; Hai Cheng; Zhenyu Li; Wei Sang; et al. (Cell Biochemistry and Biophysics, 2012)

Effects of Ibutilide on Canine Cardiac Pacing Threshold and on Induction Rates of Atrial Fibrillation - Jian-ling Sun; Rong Han; Ji-hong Guo; Xiao-ying Li; Xian-lin Ma; Chong-yu Wang (Cell Biochemistry and Biophysics, 2012)

An Electrochemical Approach to Simultaneous Determination of Acetaminophen and Ofloxacin - Te-San Chen; Kuo-Lin Huang; Jia-Long Chen (Bulletin of Environmental Contamination and Toxicology, 2012)

Development of a substrate-coupled biocatalytic process driven by an NADPH-dependent sorbose reductase from Candida albicans for the asymmetric reduction of ethyl 4-chloro-3-oxobutanoate - Ping Cai; Mingdong An; Lin Xu; Sheng Xu; Ning Hao; Yan Li; Kai Guo; Ming Yan (Biotechnology Letters, 2012)

Effects of Selenium Source and Level on Growth Performance, Tissue Selenium Concentrations, Antioxidation, and Immune Functions of Heat-Stressed Broilers - Xiudong Liao; Lin Lu; Sufen Li; Songbai Liu; Liyang Zhang; Guangying Wang; Ang Li; Xugang Luo (Biological Trace Element Research, 2012)

Isolation and Characterization of a Novel Noncoding RNA from Nickel-Induced Lung Cancer - Jing Zhang; Yang Zhou; Youjun Wu; Lin Ma; Yingying Fan; Xuan Kang; Hongjun Shi; Jun Zhang (Biological Trace Element Research, 2012)

Recombined sequences between the non-coding control regions of JC and BK viruses found in the urine of a renal transplantation patient - Yu-Ching Liaw; Cheng-Hsu Chen; Kuo-Hsiung Shu; Chiung-Yao Fang; Wei-Chih Ou; Pei-Lain Chen; Cheng-Huang Shen; Mien-Chun Lin; Deching Chang; Meilin Wang (Virus Genes, 2012)

Use of reverse genetics to develop a novel marker porcine reproductive and respiratory syndrome virus - Tao Lin; Xiangrui Li; Huochun Yao; Zuzhang Wei; Feifei Tan; Runxia Liu; Lichang Sun; Rong Zhang; Wenliang Li; Jiaqi Lu; Guangzhi Tong; Shishan Yuan (Virus Genes, 2012)

Molecular characterization and phylogenetic analysis of porcine epidemic diarrhea virus (PEDV) samples from field cases in Fujian, China - Xi Chen; Jinxian Yang; Fusong Yu; Junqing Ge; Tianlong Lin; Tieying Song (Virus Genes, 2012)

Localized all-cell knock-out (LACKO) strategy is needed for studying adult stage diseases - Xiaolan Du; Ying Zhu; Fengtao Luo; Lin Chen (Transgenic Research, 2012)

Ectopic overexpression of swine PPARγ2 upregulated adipocyte genes expression and triacylglycerol in skeletal muscle of mice - Jinliang Huang; Yuanzhu Xiong; Ting Li; Lin Zhang; Zijian Zhang; Bo Zuo; Dequan Xu; Zhuqing Ren (Transgenic Research, 2012)

The extremely high level expression of human serum albumin in the milk of transgenic mice - Xiaojie Wu; Yanli Lin; Fuyin Xiong; Yanrong Zhou; Fang Yu; Jixian Deng; Peitang Huang; Hongxing Chen (Transgenic Research, 2012)

Bromophenols from marine algae with potential anti-diabetic activities - Xiukun Lin; Ming Liu (Journal of Ocean University of China, 2012)

Biosorption behavior and mechanism of lead (II) from aqueous solution by aerobic granules (AG) and bacterial alginate (BA) - Lin Wang; Yu Li (Journal of Ocean University of China, 2012)

Conditional QTL mapping of protein content in wheat with respect to grain yield and its components - LIN WANG; FA CUI; JINPING WANG; LI JUN; ANMING DING; CHUNHUA ZHAO; XINGFENG LI; DESHUN FENG; JURONG GAO; HONGGANG WANG (Journal of Genetics, 2012)

Abnormal concentration and origin of heavy hydrocarbon in upper permian coal seams from Enhong syncline, Yunnan, China - Fengjuan Lan; Yong Qin; Ming Li; Yucheng Lin; Aikuan Wang; Jian Shen (Journal of Earth Science, 2012)

Preliminary observations of MHC class I A region polymorphism in three populations of Chinese-origin rhesus macaques - Aixue Li; Xin Wang; Yi Liu; Yanbin Zhao; Bing Liu; Lihua Sui; Lin Zeng; Zhaozeng Sun (Immunogenetics, 2012)

Characterization of 62 polymorphic EST-SSR markers in the blood clam (Tegillarca granosa) and their cross-amplification in Scapharca subcrenata - Yinghui Dong; Hanhan Yao; Zhihua Lin; Lingling Zhang; Zhenmin Bao (Conservation Genetics Resources, 2012)

Impact of tourists’ perceived value on behavioral intention for mega events: Analysis of inbound and domestic tourists at Shanghai World Expo - Chaohui Wang; Lin Lu; Qiaoyun Xia (Chinese Geographical Science, 2012)

Transesterification of Rapeseed Oil to Biodiesel on CaO/α-Fe Hollow Fiber Catalyst: Optimization by Response Surface Methodology - Lin Lin; Xiaoqiang Li; Fengjie Cui; Haining Zhou; Xiangqian Shen; Mingdong Dong (BioEnergy Research, 2012)

In Vivo Tracking of Superparamagnetic Iron Oxide Nanoparticle Labeled Chondrocytes in Large Animal Model - Jiarong Chen; Fuyou Wang; Yi Zhang; Xuhong Jin; Lin Zhang; Yong Feng; Xiao Lin; Liu Yang (Annals of Biomedical Engineering, 2012)

Folic acid inhibits endothelial cell proliferation through activating the cSrc/ERK 2/NF-κB/p53 pathway mediated by folic acid receptor - Shyr-Yi Lin; Woan-Ruoh Lee; Yi-Fan Su; Sung-Po Hsu; Hsu-Chen Lin; Pei-Yin Ho; Tien-Chi Hou; Yu-Pei Chou; Chun-Ting Kuo; Wen-Sen Lee (Angiogenesis, 2012)

Strengthening of paleo‐typhoon and autumn rainfall in Taiwan corresponding to the Southern Oscillation at late Holocene - Huei‐Fen Chen; Shie‐Ying Wen; Shen‐Rong Song; Tien‐Nan Yang; Teh‐Quei Lee; Sue‐Fen Lin; Shih‐Chieh Hsu; Kuo‐Yen Wei; Ping‐Yu Chang; Pai‐Sen Yu (Journal of Quaternary Science, 2012)
The purpose of this study is to improve prehistoric knowledge of paleo‐typhoon and winter monsoon activity in the western North Pacific after 8 cal. ka BP. We examine two sediment cores derived from lakes located to the south and north of the Ilan Plain in northeastern Taiwan. Seasonal and typhoon rainfall data over the past several decades are collected for this study region. We also use mineral indicators, K/Rb ratios and grain size to estimate sediment sources, intensity of chemical weathering and rainfall intensity. The results show that the chemical weathering index (K/Rb ratio) of Meihua Lake indicates the continuing effects of autumn rainfall, while coarse grain sizes of Dahu Lake sediments suggest increased intensity in typhoon rainfall. Grain size results reveal that increasing El Niño–Southern Oscillation intensity in the tropical Pacific has intensified the activity of super typhoons in the western North Pacific. Finally, we find that frequent activity of super paleo‐typhoons occurred in Taiwan during the La Niña‐like state, and the strengthening winter monsoon activity and higher sea surface temperature enhanced plentiful autumn rainfall in El Niño‐like state. After comparing our results with the paleo‐typhoon data in Japan and south China, we suggest that the tracks of super typhoon are mainly affected by variations in the warm pool and subtropical Northwestern Pacific High in the western Pacific. Copyright © 2012 John Wiley & Sons, Ltd.

Human Health Risk Assessment of 16 Priority Polycyclic Aromatic Hydrocarbons in Soils of Chattanooga, Tennessee, USA - Erika Hussar; Sean Richards; Zhi-Qing Lin; Robert P. Dixon; Kevin A. Johnson (Water, Air, & Soil Pollution, 2012)

Performance and Bacterial Community Diversity of a Full-Scale Biofilter Treating Leachate Odor in a Sanitary Landfill Site - Lin Li; Yunping Han; Junxin Liu (Water, Air, & Soil Pollution, 2012)

Escherichia coli Membranes Depleted of SecYEG Elicit SecA-Dependent Ion-Channel Activity but Lose Signal Peptide Specificity - Bor-Ruei Lin; Ying-Hsin Hsieh; Chun Jiang; Phang C. Tai (The Journal of Membrane Biology, 2012)

Crystal structures of rice (Oryza sativa) glyceraldehyde-3-phosphate dehydrogenase complexes with NAD and sulfate suggest involvement of Phe37 in NAD binding for catalysis - Yueh-Chu Tien; Phimonphan Chuankhayan; Yen-Chieh Huang; Chung-De Chen; Jahan Alikhajeh; Shou-Lin Chang; Chun-Jung Chen (Plant Molecular Biology, 2012)

Dramatic genotypic difference in, and effect of genetic crossing on, tissue culture-induced mobility of retrotransposon Tos17 in rice - Chunjing Lin; Xiuyun Lin; Lanjuan Hu; Jingjing Yang; Tianqi Zhou; Likun Long; Chunming Xu; Shaochen Xing; Bao Qi; Yingshan Dong; Bao Liu (Plant Cell Reports, 2012)

In vitro selection of glyphosate-tolerant variants from long-term callus cultures of Zoysia matrella [L.] Merr - Shu Chen; Mingliang Chai; Yufang Jia; Zhongshan Gao; Li Zhang; Minxia Gu; Wendan Lin; Liping Wang (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Annual ring widths are good predictors of changes in net primary productivity of alpine Rhododendron shrubs in the Sergyemla Mountains, southeast Tibet - Gaoqiang Kong; Tianxiang Luo; Xinsheng Liu; Lin Zhang; Eryuan Liang (Plant Ecology, 2012)

Effects of local biotic neighbors and habitat heterogeneity on tree and shrub seedling survival in an old-growth temperate forest - Xuejiao Bai; Simon A. Queenborough; Xugao Wang; Jian Zhang; Buhang Li; Zuoqiang Yuan; Dingliang Xing; Fei Lin; Ji Ye; Zhanqing Hao (Oecologia, 2012)

Using decomposition analysis to evaluate the performance of China’s 30 provinces in CO2 emission reductions over 2005–2009 - Jidong Kang; Tao Zhao; Xiaosong Ren; Tao Lin (Natural Hazards, 2012)

NADPH oxidase 2 plays a critical role in dysfunction and apoptosis of pancreatic β-cells induced by very low-density lipoprotein - Juan Jiao; Lin Dou; Miao Li; Yonggang Lu; Han-Bang Guo; Yong Man; Shu Wang; Jian Li (Molecular and Cellular Biochemistry, 2012)

Mechano growth factor (MGF) promotes proliferation and inhibits differentiation of porcine satellite cells (PSCs) by down-regulation of key myogenic transcriptional factors - Li-Li Qin; Xiao-Kui Li; Jian Xu; De-Lin Mo; Xiong Tong; Zhi-Cheng Pan; Jia-Qi Li; Yao-Sheng Chen; Zhe Zhang; Chong Wang; Qiao-Ming Long (Molecular and Cellular Biochemistry, 2012)

Chemoselective synthesis, antiproliferative activities, and SAR study of 1H-pyrazol-5-yl-N,N-dimethylformamidines and pyrazolyl-2-azadienes - Kau-Shan Wen; Hui-Yi Lin; Yu-Ying Huang; Kimiyoshi Kaneko; Hiroyuki Takayama; Masayuki Kimura; Shin-Hun Juang; Fung Fuh Wong (Medicinal Chemistry Research, 2012)

Pharmacophore modeling, virtual screening, and molecular docking studies for discovery of novel Carbonic anhydrase IX inhibitors - Chun-Lin Lu; Lu Zhou; Zi-Cheng Li; Xiang Gao; Wei Zhang (Medicinal Chemistry Research, 2012)

Influence of gonadotropin-releasing hormone agonist on the effect of chemotherapy upon ovarian cancer and the prevention of chemotherapy-induced ovarian damage: an experimental study with nu/nu athymic mice - Qiong-yan Lin; Yi-feng Wang; Hui-nan Weng; Xiu-jie Sheng; Qing-ping Jiang; Zhi-ying Yang (Journal of Zhejiang University-SCIENCE B, 2012)

XRCC1 Arg399Gln and clinical outcome of platinum-based treatment for advanced non-small cell lung cancer: a meta-analysis in 17 studies - Jian Chen; Qing-wei Zhao; Gen-ming Shi; Lin-run Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Nkx2-1: a novel tumor biomarker of lung cancer - Li Yang; Min Lin; Wen-jing Ruan; Liang-liang Dong; En-guo Chen; Xiao-hong Wu; Ke-jing Ying (Journal of Zhejiang University-SCIENCE B, 2012)

Significance of IL-6 in the transition of hormone-resistant prostate cancer and the induction of myeloid-derived suppressor cells - Chun-Te Wu; Ching-Chuan Hsieh; Cheng-Chia Lin; Wen-Cheng Chen; Ji-Hong Hong; Miao-Fen Chen (Journal of Molecular Medicine, 2012)

Genetic variation in the Nrf2 promoter associates with defective spermatogenesis in humans - Bolan Yu; Huanlan Lin; Lixia Yang; Kang Chen; Haihua Luo; Jianqiao Liu; Xingcheng Gao; Xuefeng Xia; Zhaofeng Huang (Journal of Molecular Medicine, 2012)

Role of Neurotrophins in the Development and Function of Neural Circuits That Regulate Energy Homeostasis - Samira Fargali; Masato Sadahiro; Cheng Jiang; Amy L. Frick; Tricia Indall; Valeria Cogliani; Jelle Welagen; Wei-Jye Lin; Stephen R. Salton (Journal of Molecular Neuroscience, 2012)

Atypical work schedules are associated with poor sleep quality and mental health in Taiwan female nurses - Pei-Chen Lin; Chung-Hey Chen; Shung-Mei Pan; Chih-Hong Pan; Chiou-Jong Chen; Yao-Mei Chen; Hsin-Chia Hung; Ming-Tsang Wu (International Archives of Occupational and Environmental Health, 2012)

Tectonics of the Middle Triassic intracontinental Xuefengshan Belt, South China: new insights from structural and chronological constraints on the basal décollement zone - Yang Chu; Michel Faure; Wei Lin; Qingchen Wang; Wenbin Ji (International Journal of Earth Sciences, 2012)

First record of wild ephyrae of the giant jellyfish Nemopilema nomurai - Masaya Toyokawa; Masashi Shibata; Jia-Hua Cheng; Hui-Yu Li; Jian-Zhong Ling; Nan Lin; Zun-Lei Liu; Yi Zhang; Manabu Shimizu; Hideki Akiyama (Fisheries Science, 2012)

Reproductive hormones and interleukin-6 in serious leisure male athletes - Leah Z. FitzGerald; Wendie A. Robbins; James S. Kesner; Lin Xun (European Journal of Applied Physiology, 2012)

Characterization of pilP, a gene required for twitching motility, pathogenicity, and biofilm formation of Acidovorax avenae subsp. avenae RS-1 - He Liu; Wen-Xiao Tian; Muhammad Ibrahim; Bin Li; Guo-Qing Zhang; Bo Zhu; Guan-Lin Xie (European Journal of Plant Pathology, 2012)

Changes in labile soil organic matter fractions following land use change from monocropping to poplar-based agroforestry systems in a semiarid region of Northeast China - Rong Mao; De-Hui Zeng; Lu-Jun Li; Ya-Lin Hu (Environmental Monitoring and Assessment, 2012)

Photocatalytic degradation of methyl orange by a multi-layer rotating disk reactor - Chia-Nan Lin; Chih-Yi Chang; Hung Ji Huang; Din Ping Tsai; Nae-Lih Wu (Environmental Science and Pollution Research, 2012)

Microbial structure and chemical components of aerosols caused by rotating brushes in a wastewater treatment plant - Yunping Han; Lin Li; Junxin Liu; Mengzhu Zhang (Environmental Science and Pollution Research, 2012)

Relationships Between Nitrogen Transformation Rates and Gene Abundance in a Riparian Buffer Soil - Lin Wu; Deanna L. Osmond; Alexandria K. Graves; Michael R. Burchell; Owen W. Duckworth (Environmental Management, 2012)

Does glyphosate impact on Cu uptake by, and toxicity to, the earthworm Eisenia fetida? - Chui-Fan Zhou; Yu-Jun Wang; Yuan-Chun Yu; Rui-Juan Sun; Xiang-Dong Zhu; Hai-Lin Zhang; Dong-Mei Zhou (Ecotoxicology, 2012)

Coupled dynamics of energy budget and population growth of tilapia in response to pulsed waterborne copper - Wei-Yu Chen; Chia-Jung Lin; Yun-Ru Ju; Jeng-Wei Tsai; Chung-Min Liao (Ecotoxicology, 2012)

The Response of Soil Nematode Community to Nitrogen, Water, and Grazing History in the Inner Mongolian Steppe, China - Wei-bin Ruan; Yuan Sang; Qing Chen; Xiang Zhu; Shan Lin; Yu-bao Gao (Ecosystems, 2012)

PA2800 Plays an Important Role in Both Antibiotic Susceptibility and Virulence in Pseudomonas aeruginosa - Lixin Shen; Xiangli Gao; Jinhua Wei; Lin Chen; Xin Zhao; Bo Li; Kangmin Duan (Current Microbiology, 2012)

Extracytoplasmic Stress Responses Induced by Antimicrobial Cationic Polyethylenimines - Blaine A. Lander; Kyle D. Checchi; Stephen A. Koplin; Virginia F. Smith; Tammy L. Domanski; Daniel D. Isaac; Shirley Lin (Current Microbiology, 2012)

Effect of Ibutilide on the Canine Cardiac Conduction System - Jian Ling Sun; Rong Han; Ji Hong Guo; Xiao Ying Li; Xian Lin Ma; Chong Yu Wang (Cell Biochemistry and Biophysics, 2012)

Characterization of a recombinant cellobiose 2-epimerase from Dictyoglomus turgidum that epimerizes and isomerizes β-1,4- and α-1,4-gluco-oligosaccharides - Jung-Eun Kim; Yeong-Su Kim; Lin-Woo Kang; Deok-Kun Oh (Biotechnology Letters, 2012)

Halohasta litorea gen. nov. sp. nov., and Halohasta litchfieldiae sp. nov., isolated from the Daliang aquaculture farm, China and from Deep Lake, Antarctica, respectively - Yun-Zhuang Mou; Xing-Xing Qiu; Mei-Lin Zhao; Heng-Lin Cui; Dickson Oh; Mike L. Dyall-Smith (Extremophiles, 2012)

Influence of hybrid giant Napier grass on salt and nutrient distributions with depth in a saline soil - Chongjian Ma; Ravi Naidu; Faguang Liu; Changhua Lin; Hui Ming (Biodegradation, 2012)

Neuroprotective effects of tert-butylhydroquinone on paraquat-induced dopaminergic cell degeneration in C57BL/6 mice and in PC12 cells - Huangyuan Li; Siying Wu; Zhangjing Wang; Wei Lin; Chenzi Zhang; Bin Huang (Archives of Toxicology, 2012)

Albumin prevents reactive oxygen species-induced mitochondrial damage, autophagy, and apoptosis during serum starvation - Shu-Yu Liu; Chia-Ling Chen; Tsan-Tzu Yang; Wei-Ching Huang; Chia-Yuan Hsieh; Wan-Jou Shen; Tsung-Ting Tsai; Chi-Chang Shieh; Chiou-Feng Lin (Apoptosis, 2012)

Paenibacillus beijingensis sp. nov., a novel nitrogen-fixing species isolated from jujube garden soil - Miao Gao; Lin-qi Xie; Ya-xiong Wang; Jian Chen; Jing Xu; Xiao-xia Zhang; Xin-hua Sui; Jun-lian Gao; Jian-guang Sun (Antonie van Leeuwenhoek, 2012)

Influence of a southern shift of the ITCZ from Quick Scatterometer data on the Pacific North Equatorial Countercurrent - Fanghua Wu; Pengfei Lin; Hailong Liu (Advances in Atmospheric Sciences, 2012)

Numerical study on the impact of ground heating and ambient wind speed on flow fields in street canyons - Lei Li; Lin Yang; Li-Jie Zhang; Yin Jiang (Advances in Atmospheric Sciences, 2012)

Antioxidant system of tea (Camellia sinensis) leaves in response to phosphorus supply - Zheng-He Lin; Li-Song Chen; Rong-Bing Chen; Fang-Zhou Zhang (Acta Physiologiae Plantarum, 2012)

Bromoform production from seawater treated with bromoperoxidase - Chia Yu Lin; Steven L. Manley (Limnology and Oceanography, 2012)
Bromoform (CHBr 3 ; 11–486 fmol L −1 h −1 ), dibromomethane (CH 2 Br 2 ; 0–9.4 fmol L −1 h −1 ), and low amounts of chloride‐substituted chlorobromomethanes were produced from southern California coastal surface seawater upon the addition of algal bromoperoxidase (BrPO) and hydrogen peroxide. Production was greater from water collected near shore than 16 km offshore, presumably reflecting the difference in the reactive dissolved organic matter (DOM react ) concentrations. In the spring, there was an increase in phytoplankton abundance, and CHBr 3 production from BrPO incubations was greater, presumably due to increased DOM react . In the winter, CH 2 Br 2 production was enhanced, although still lower than CHBr 3 , suggesting a qualitative change in DOM composition due to terrestrial runoff. During the month of the highest precipitation, CHBr 3 and CH 2 Br 2 production was enhanced in samples obtained from the mouth of an urban river, suggesting a higher concentration of DOM react of terrestrial origins. DOM was fractionated by ultrafiltration and subject to the BrPO incubation. The higher molecular weight fractions contained a higher concentration of DOM that was susceptible to BrPO bromination, yielding polybromomethanes. Polybromomethane and iodomethane production associated with phytoplankton blooms results from the reaction between the surrounding DOM, and hypobromous acid (HOBr) and hypoiodous acid released from extracellular (apoplastic) BrPO. The reaction of HOBr and DOM (biological bleaching) could represent a significant DOM degradation pathway. Cell‐free BrPO, derived from dead cells, could remain catalytically active in seawater and produce low amounts of polyhalomethanes prior to biological degradation.

Maize potential yields and yield gaps in the changing climate of northeast China - Zhijuan Liu; Xiaoguang Yang; Kenneth G. Hubbard; Xiaomao Lin (Global Change Biology, 2012)
Northeast China ( NEC ) is not only one of the major agricultural production areas in China, but it is also the most susceptible to climate variability. This led us to investigate the impact of climate change on maize potential yield and yield gaps in this region, where maize accounts for about 30% of the nation's production. The APSIM ‐Maize model was calibrated and validated for maize phenology and yields. The validated model was then used to estimate potential yields, rain‐fed potential yields, and yield gaps for assessing the climate impacts on maize productivity in NEC . During maize growing seasons from 1981 to 2010, the analysis indicates a warming trend all across NEC , whereas the trends in solar radiation and total precipitation tended to decrease. When the same hybrid was specified in APSIM for all years, a simulated increase of maximum temperature resulted in a negative impact on both potential yield and rain‐fed potential yield. A simulated increase in minimum temperature produced no significant changes in potential or rain‐fed potential yield. However, the increase of minimum temperature was shown to result in a positive impact on the on‐farm yield, consistent with our finding that farmers adopted longer season hybrids for which the increase in minimum temperature provided better conditions for germination, emergence, and grain filling during night time. The gap between potential and rain‐fed potential yields was shown to be larger at locations with lower seasonal precipitation ( NEC . Within NEC , on‐farm maize yields were, on average, only 51% of the potential yields, indicating a large exploitable yield gap, which provides an opportunity to significantly increase production by effective irrigation, fertilization, herbicide, and planting density in NEC .

New sphingolipid psychotramide A–D from the stem of Psychotria sp. - Cui-Xian Zhang; Xi-Xin He; Shan-Yue Guan; Ying Zhong; Chao-Zhan Lin; Tian-Qin Xiong; Chen-Chen Zhu (Natural Product Research, 2012)

Spatio-temporal variability of streamflow in the Yellow River: possible causes and implications - Chi Yuan Miao; Wen Shi; Xun Hong Chen; Lin Yang (Hydrological Sciences Journal, 2012)

Accounting for a changing and uncertain climate in planning and policymaking today: lessons for developing countries - Nicola Ranger; Su-Lin Garbett-Shiels (Climate and Development, 2012)

Biodegradation of poly(ε-caprolactone) (PCL) by a new Penicillium oxalicum strain DSYD05-1 - Fan Li; Dan Yu; Xiumei Lin; Dongbo Liu; Hongmei Xia; Shan Chen (World Journal of Microbiology and Biotechnology, 2012)

Effect of Sulfate Availability on the Isotopic Signature of Reduced Sulfurous Compounds in the Sediments of a Subtropical Estuary - Lan-Feng Fan; Saulwood Lin; Wei-Gang He; Kuo-Ming Huang; Chang-Po Chen; Hwey-Lian Hsieh (Wetlands, 2012)

Molecular diversity, genomic constitution, and QTL mapping of fiber quality by mapped SSRs in introgression lines derived from Gossypium hirsutum × G. darwinii Watt - Bin Wang; Yichun Nie; Zhongxu Lin; Xianlong Zhang; Junjie Liu; Jing Bai (Theoretical and Applied Genetics, 2012)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Erratum to: Probing and tracking organelles in living plant cells - Tong Chen; Xiaohua Wang; Daniel von Wangenheim; Maozhong Zheng; Jozef Šamaj; Wanquan Ji; Jinxing Lin (Protoplasma, 2012)

Rapid sex identification of papaya (Carica papaya) using multiplex loop-mediated isothermal amplification (mLAMP) - Te-Hua Hsu; Jin-Chywan Gwo; Kuan-Hung Lin (Planta, 2012)

Characterization and expression analysis of three cold shock protein (CSP) genes under different stress conditions in the Antarctic bacterium Psychrobacter sp. G - Weizhi Song; Xuezheng Lin; Xiaohang Huang (Polar Biology, 2012)

Agrobacterium tumefaciens-Mediated Transformation of the Halophyte Leymus chinensis (Trin.) - Yan-Lin Sun; Soon-Kwan Hong (Plant Molecular Biology Reporter, 2012)

Functional Markers for Cellulose Synthase and Their Comparison to SSRs in Cotton - Zhongxu Lin; Ying Wang; Xianlong Zhang; Jinfa Zhang (Plant Molecular Biology Reporter, 2012)

Effectiveness of soil N availability indices in predicting site productivity in the oil sands region of Alberta - En-Rong Yan; Ya-Lin Hu; Francis Salifu; Xiao Tan; Z. Chi Chen; Scott X. Chang (Plant and Soil, 2012)

Dorsal root ganglion compression as an animal model of sciatica and low back pain - Xiao-Yu Lin; Jing Yang; Hui-Ming Li; San-Jue Hu; Jun-Ling Xing (Neuroscience Bulletin, 2012)

Selectivity of N170 in the left hemisphere as an electrophysiological marker for expertise in reading Chinese - Jing Zhao; Su Li; Si-En Lin; Xiao-Hua Cao; Sheng He; Xu-Chu Weng (Neuroscience Bulletin, 2012)

Novel glycine-dependent inactivation of NMDA receptors in cultured hippocampal neurons - Yun-Feng Zhang; Xia Li; Liang-Liang Peng; Guo-Hua Wang; Kai-Fu Ke; Zheng-Lin Jiang (Neuroscience Bulletin, 2012)

Potential hazard analysis and risk assessment of debris flow by fuzzy modeling - Jeng-Wen Lin; Cheng-Wu Chen; Cheng-Yi Peng (Natural Hazards, 2012)

Fuzzy regression decision systems for assessment of the potential vulnerability of bridge to earthquakes - Jeng-Wen Lin (Natural Hazards, 2012)

Multi-environment mapping and meta-analysis of 100-seed weight in soybean - Ya-nan Sun; Jun-bo Pan; Xiang-lin Shi; Xiang-yu Du; Qiong Wu; Zhao-ming Qi; Hong-wei Jiang; Da-wei Xin; Chun-yan Liu; Guo-hua Hu; Qing-shan Chen (Molecular Biology Reports, 2012)

Neural Stem Cells Enhance Nerve Regeneration after Sciatic Nerve Injury in Rats - Lin Xu; Shuai Zhou; Guo-Ying Feng; Lu-Ping Zhang; Dong-Mei Zhao; Yi Sun; Qian Liu; Fei Huang (Molecular Neurobiology, 2012)

NLK is a key regulator of proliferation and migration in gallbladder carcinoma cells - Zhujun Tan; Maolan Li; Wenguang Wu; Lin Zhang; Qichen Ding; Xiangsong Wu; Jiasheng Mu; Yingbin Liu (Molecular and Cellular Biochemistry, 2012)

Investigation of array-derived rotation in TAIPEI 101 - Chin-Jen Lin; Wen-Gee Huang; Han-Pang Huang; Bor-Shouh Huang; Chin-Shang Ku; Chun-Chi Liu (Journal of Seismology, 2012)

Investigation of ground rotational motions caused by direct and scattered P-waves from the 4 March 2008 TAIGER explosion experiment - Nguyen Dinh Pham; Bor-Shouh Huang; Chin-Jen Lin; Tuan-Minh Vu; Ngoc-Anh Tran (Journal of Seismology, 2012)

Comparison of point and array-computed rotations for the TAIGER explosions of 4 March 2008 - Lauren M. Kendall; Charles A. Langston; W. H. K. Lee; C. J. Lin; C. C. Liu (Journal of Seismology, 2012)

Effects of rotation motions on strong-motion data - H. C. Chiu; F. J. Wu; C. J. Lin; H. C. Huang; C. C. Liu (Journal of Seismology, 2012)

Protective effects of Lycium barbarum polysaccharide on neonatal rat primary cultured hippocampal neurons injured by oxygen-glucose deprivation and reperfusion - Chen Rui; Li Yuxiang; Hao Yinju; Zhu Qingluan; Wu Yang; Zhao Qipeng; Wang Hao; Ma Lin; Liu Juan; Zhao Chengjun; Jiang Yuanxu; Wang Yanrong; et al. (Journal of Molecular Histology, 2012)

Increased Th17 cell frequency concomitant with decreased Foxp3+ Treg cell frequency in the peripheral circulation of patients with carotid artery plaques - Zhen-dong Liu; Lin Wang; Fang-hong Lu; Hui Pan; Ying-xin Zhao; Shu-jian Wang; Shang-wen Sun; Cui-ling Li; Xiao-liang Hu (Inflammation Research, 2012)

High glucose increases nitric oxide generation in lipopolysaccharide-activated macrophages by enhancing activity of protein kinase C-α/δ and NF-κB - Kuo-Feng Hua; Szu-Hsuan Wang; Wei-Chih Dong; Chai-Yi Lin; Chen-Lung Ho; Tzu-Hua Wu (Inflammation Research, 2012)

Bacterially mediated iron cycling and associated biogeochemical processes in a subtropical shallow coastal aquifer: implications for groundwater quality - Chaofeng Lin; Eloise I. Larsen; Genevieve R. Larsen; Malcolm E. Cox; James J. Smith (Hydrobiologia, 2012)

Involvement of FGF9/16/20 subfamily in female germ cell development of the Nile tilapia, Oreochromis niloticus - Yun-Lv Sun; Sheng Zeng; Kai Ye; Chao Yang; Ming-Hui Li; Bao-Feng Huang; Li-Na Sun; Lin-Yan Zhou; De-Shou Wang (Fish Physiology and Biochemistry, 2012)

In vivo screening of zebrafish microRNA responses to bacterial infection and their possible roles in regulating immune response genes after lipopolysaccharide stimulation - Tsung-Han Wu; Chieh-Yu Pan; Ming-Ching Lin; Jung-Chen Hsieh; Cho-Fat Hui; Jyh-Yih Chen (Fish Physiology and Biochemistry, 2012)

Microbiologic characteristics of pathogenic bacteria from hospitalized trauma patients who survived Wenchuan earthquake - B. Zhang; Z. Liu; Z. Lin; X. Zhang; W. Fu (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

The dissection and SSR mapping of a high-temperature adult-plant stripe rust resistance gene in American spring wheat cultivar Alturas - Lei Zhao; Jing Feng; Chun-Yu Zhang; Xiao-Dan Xu; Xian-Ming Chen; Quan Sun; Qing Miao; Shi-Chang Xu; Feng Lin (European Journal of Plant Pathology, 2012)

Identification and molecular cytology analysis of cold tolerance introgression lines derived from Oryza sativa L. mating with O. rufipogon Griff. - Xiang-Dong Luo; Liang-Fang Dai; Juan-Fang Cao; Shui-Rong Jian; Ya-Ling Chen; Biao-Lin Hu; Jian-Kun Xie (Euphytica, 2012)

Simulation of Wind Circulation and Pollutant Diffusion Over the Pearl River Delta Region - Li-Ping Zeng; Wen-Shi Lin; Qi Fan; Ye-Rong Feng (Environmental Modeling & Assessment, 2012)

Metal (Pb, Cd, and Cu)-induced reactive oxygen species accumulations in aerial root cells of the Chinese banyan (Ficus microcarpa) - Nan Liu; Zhifang Lin; Hui Mo (Ecotoxicology, 2012)

Effects of heavy metals on the expression of a zinc-inducible metallothionein-III gene and antioxidant enzyme activities in Crassostrea gigas - Ming Cong; Huifeng Wu; Xiaoli Liu; Jianmin Zhao; Xuan Wang; Jiasen Lv; Lin Hou (Ecotoxicology, 2012)

Regulation on Expression of Toll-like Receptors on Monocytes After Stimulation with the 3-o-C12-HSL Molecule from Pseudomonas aeruginosa - Qi Lu; Yujia Lin; Xiqiang Yang; Wei Liu; Xianhong Zhang; Daochao Huang; Haiying Zhong (Current Microbiology, 2012)

Dynamical seasonal prediction using the global environmental multiscale model with a variable resolution modeling approach - Marko Markovic; Hai Lin; Katja Winger (Climate Dynamics, 2012)

An Improved AhR Reporter Gene Assay for Analyzing Dioxins in Soil, Sediment and Fish - How-Ran Chao; Ya-Fan Wang; Yao-Nan Wang; Ding-Yan Lin; Yan-You Gou; Chien-Yu Chen; Kuan-Chung Chen; Wen-Kai Wu; Bao-An Chiang; Yu-Ting Huang; Lien-Te Hsieh; Kuei-Jyum C. Yeh; et al. (Bulletin of Environmental Contamination and Toxicology, 2012)

Role of obesity in a randomized placebo-controlled trial of difluoromethylornithine (DFMO) + sulindac for the prevention of sporadic colorectal adenomas - Jason A. Zell; Bruce S. Lin; Nikki Madson; Christine E. McLaren; Eugene W. Gerner; Frank L. Meyskens (Cancer Causes & Control, 2012)

Unincorporated iron pool is linked to oxidative stress and iron levels in Caenorhabditis elegans - Natalie A. Rangel; Lawrence Lin; Kanyasiri Rakariyatham; Albert Bach; Kim Trinh; Matthew H. S. Clement; Chandra Srinivasan (BioMetals, 2012)

Molecular characterization and phylogenetic analysis of Sugarcane yellow leaf virus isolates from China - San-Ji Gao; Yi-Hua Lin; Yong-Bao Pan; Mona B. Damaj; Qin-Nan Wang; T. Erik Mirkov; Ru-Kai Chen (Virus Genes, 2012)

Classical swine fever virus NS5A protein localizes to endoplasmic reticulum and induces oxidative stress in vascular endothelial cells - Lei He; Yan-ming Zhang; Zhi Lin; Wei-wei Li; Jing Wang; He-Lin Li (Virus Genes, 2012)

Development of transgenic watermelon resistant to Cucumber mosaic virus and Watermelon mosaic virus by using a single chimeric transgene construct - Ching-Yi Lin; Hsin-Mei Ku; Yi-Hua Chiang; Hsiu-Yin Ho; Tsong-Ann Yu; Fuh-Jyh Jan (Transgenic Research, 2012)

Retrieval of total suspended matter from MODIS 250 m imagery in the Bohai Sea of China - Lin Wang; Dongzhi Zhao; Jianhong Yang; Yanlong Chen (Journal of Oceanography, 2012)

Disease-modifying drugs for multiple sclerosis and JC virus expression - Craig S. Miller; Sidney A. Houff; Jason Hopper; Robert J. Danaher; Julie A. Gurwell; Yushun Lin; Nubia Vega; Joseph R. Berger (Journal of NeuroVirology, 2012)

Identification, fine mapping and characterization of Rht-dp, a recessive wheat dwarfing (reduced height) gene derived from Triticum polonicum - Hou-Yang Kang; Li-Juan Lin; Zhi-Jian Song; Jing-Ya Yuan; Mei-Yu Zhong; Hai-Qin Zhang; Xing Fan; Li-Na Sha; Yi Wang; Li-Li Xu; Jian Zeng; Yong-Hong Zhou (Genes & Genomics, 2012)

Genetic characterization of a new subtype of Hantaan virus isolated from a hemorrhagic fever with renal syndrome (HFRS) epidemic area in Hubei Province, China - Jin-lin Li; Jia-xin Ling; Dong-ying Liu; Jing Liu; Yuan-yuan Liu; Fei Wei; Fan Luo; Wen Chen; Yi-hui Zhang; Hai-rong Xiong; Wei Hou; Zhan-qiu Yang (Archives of Virology, 2012)

Interplay of RsbM and RsbK controls the σ B activity of Bacillus cereus - Lei‐Chin Chen; Jung‐Chi Chen; Jwu‐Ching Shu; Chien‐Yen Chen; Ssu‐Ching Chen; Shu‐Hwa Chen; Chun‐Yen Lin; Chi‐Yu Lu; Chien‐Cheng Chen (Environmental Microbiology, 2012)
Summary The alternative transcription factor σ B of Bacillus cereus controls the expression of a number of genes that respond to environmental stress. Four proteins encoded in the sigB gene cluster, including RsbV, RsbW, RsbY (RsbU) and RsbK, are known to be essential in the σ B ‐mediated stress response. In the context of stress, the hybrid sensor kinase RsbK is thought to phosphorylate the response regulator RsbY, a PP2C serine phosphatase, leading to the dephosphorylation of the phosphorylated RsbV. The unphosphorylated RsbV then sequesters the σ B antagonist, RsbW, ultimately liberating σ B . The gene arrangement reveals an open reading frame, bc1007 , flanked immediately downstream by rsbK within the sigB gene cluster. However, little is known about the function of bc1007 . In this study, the deletion of bc1007 resulted in high constitutive σ B expression independent of environmental stimuli, indicating that bc1007 plays a role in σ B regulation. A bacterial two‐hybrid analysis demonstrated that BC1007 interacts directly with RsbK, and autoradiographic studies revealed a specific C 14 ‐methyl transfer from the radiolabelled S‐adenosylmethionine to RsbK when RsbK was incubated with purified BC1007. Our data suggest that BC1007 (RsbM) negatively regulates σ B activity by methylating RsbK. Additionally, mutagenic substitution was employed to modify 12 predicted methylation residues in RsbK. Certain RsbK mutants were able to rescue σ B activation in a rsbK ‐deleted bacterial strain, but RsbK E439A failed to activate σ B , and RsbK E446A only moderately induced σ B . These results suggest that Glu439 is the preferred methylation site and that Glu446 is potentially a minor methylation site. Gene arrays of the rsbK orthologues and the neighbouring rsbM orthologues are found in a wide range of bacteria. The regulation of sigma factors through metylation of RsbK‐like sensor kinases appears to be widespread in the microbial world.

Study on the relationship between sub-pixel percentage cover and multi-temporal NDVI - Hongshuo Wang; Hui Lin; Jinsong Chen; Fulong Chen (International Journal of Remote Sensing, 2012)

Structural optimization and evaluation of butenolides as potent antifouling agents: modification of the side chain affects the biological activities of compounds - Yongxin Li; Fengying Zhang; Ying Xu; Kiyotaka Matsumura; Zhuang Han; Lingli Liu; Wenhan Lin; Yanxing Jia; Pei-Yuan Qian (Biofouling, 2012)

Microcosm Study of Iron Mobilization and Greenhouse Gas Evolution in Soils of a Plantation-Forested Subtropical Coastal Catchment - Chaofeng Lin; Eloise I. Larsen; Peter R. Grace; James J. Smith (Water, Air, & Soil Pollution, 2012)

Formation of Volatile Halogenated By-Products During the Chlorination of Oxytetracycline - Bin Xu; He-Zhen Zhu; Yi-Li Lin; Kai-Yuan Shen; Wen-Hai Chu; Chen-Yan Hu; Kang-Ning Tian; Seleli Andrew Mwakagenda; Xiang-Yu Bi (Water, Air, & Soil Pollution, 2012)

Photocatalytic Degradation of Reactive Black 5 by Fish Scale-Loaded TiO2 Composites - Li-Ngee Ho; Soon-An Ong; Yee Lin See (Water, Air, & Soil Pollution, 2012)

SNP identification and allelic-specific PCR markers development for TaGW2, a gene linked to wheat kernel weight - Zibo Yang; Zhiyuan Bai; Xiaolin Li; Pei Wang; Qingxia Wu; Lin Yang; Liqun Li; Xuejun Li (Theoretical and Applied Genetics, 2012)

The isolation of Pi1, an allele at the Pik locus which confers broad spectrum resistance to rice blast - Lixia Hua; Jianzhong Wu; Caixia Chen; Weihuai Wu; Xiuying He; Fei Lin; Li Wang; Ikuo Ashikawa; Takashi Matsumoto; Ling Wang; Qinghua Pan (Theoretical and Applied Genetics, 2012)

Effects of Sugarcane Ratooning Cultivation on the Alteration of Bacterial Communities in the Rhizosphere Soil - Lin Sheng; Zhang Aijia; Wang Rongyu; Cheng Ting; Zhou Mingming; Yuan Zhaonian; Lin Wenxiong (Sugar Tech, 2012)

Erratum to: Single nucleotide polymorphisms in the human corticosteroid-binding globulin promoter alter transcriptional activity - Yue Li; Liang Wu; JingHui Lei; Cheng Zhu; HongMei Wang; XiaoGuang Yu; HaiYan Lin (Science China Life Sciences, 2012)

Total body irradiation of donors can alter the course of tolerance and induce acute rejection in a spontaneous tolerance rat liver transplantation model - YeWei Zhang; HeWei Zhao; Lin Bo; YinXue Yang; Xiang Lu; JingFeng Sun; JianFei Wen; Xia He; GuoWen Yin (Science China Life Sciences, 2012)

Retrieval of aerosol optical depth over bright targets in the urban areas of North China during winter - ShenShen Li; LiangFu Chen; JinHua Tao; Dong Han; ZhongTing Wang; Lin Su; Meng Fan; Chao Yu (Science China Earth Sciences, 2012)

Functional redundancy of the two 5-hydroxylases in monolignol biosynthesis of Populus trichocarpa: LC–MS/MS based protein quantification and metabolic flux analysis - Jack P. Wang; Christopher M. Shuford; Quanzi Li; Jina Song; Ying-Chung Lin; Ying-Hsuan Sun; Hsi-Chuan Chen; Cranos M. Williams; David C. Muddiman; Ronald R. Sederoff; Vincent L. Chiang (Planta, 2012)

The constitutive expression of Chrysanthemum dichrum ICE1 in Chrysanthemum grandiflorum improves the level of low temperature, salinity and drought tolerance - Lin Chen; Yu Chen; Jiafu Jiang; Sumei Chen; Fadi Chen; Zhiyong Guan; Weimin Fang (Plant Cell Reports, 2012)

Involvement of heme oxygenase-1 in β-cyclodextrin–hemin complex-induced cucumber adventitious rooting process - Yuting Lin; Meiyue Li; Liqin Huang; Wenbiao Shen; Yong Ren (Plant Cell Reports, 2012)

Productive leaf functional traits of Chinese savanna species - Jiao-Lin Zhang; L. Poorter; Kun-Fang Cao (Plant Ecology, 2012)

Erratum to: Identification of C4 photosynthesis metabolism and regulatory-associated genes in Eleocharis vivipara by SSH - Taiyu Chen; Rongjian Ye; Xiaolei Fan; Xianghua Li; Yongjun Lin (Photosynthesis Research, 2012)

Pharmacokinetic Considerations for Antibody Drug Conjugates - Kedan Lin; Jay Tibbitts (Pharmaceutical Research, 2012)

Characterization of a Nanoparticulate Drug Delivery System Using Scanning Ion Occlusion Sensing - Lin Yang; Murray F. Broom; Ian G. Tucker (Pharmaceutical Research, 2012)

Pharmacokinetic and Pharmacodynamic Modeling of Opioid-Induced Gastrointestinal Side Effects in Patients Receiving Tapentadol IR and Oxycodone IR - Xu Steven Xu; Mila Etropolski; David Upmalis; Akiko Okamoto; Rachel Lin; Partha Nandy (Pharmaceutical Research, 2012)

Impact of MCP-1 and CCR-2 gene polymorphisms on coronary artery disease susceptibility - Hsiu-Ling Lin; Kwo-Chang Ueng; Yih-Shou Hsieh; Whei-Ling Chiang; Shun-Fa Yang; Shu-Chen Chu (Molecular Biology Reports, 2012)

Expression profile of miRNAs in Populus cathayana L. and Salix matsudana Koidz under salt stress - Jing Zhou; Mingying Liu; Jing Jiang; Guirong Qiao; Sheng Lin; Haiying Li; Lihua Xie; Renying Zhuo (Molecular Biology Reports, 2012)

Syndecan-1 expression in human glioma is correlated with advanced tumor progression and poor prognosis - Yimin Xu; Jun Yuan; Ziheng Zhang; Lvbiao Lin; Shengliang Xu (Molecular Biology Reports, 2012)

Polymorphisms in the cytotoxic T-lymphocyte antigen 4 gene and acute rejection risk in transplant recipients - Cheng-lin Zhu; Qiang Huang; Chen-hai Liu; Fang Xie (Molecular Biology Reports, 2012)

High levels of glucose induce “metabolic memory” in cardiomyocyte via epigenetic histone H3 lysine 9 methylation - Xi-Yong Yu; Yong-Jian Geng; Jia-Liang Liang; Saidan Zhang; He-Ping Lei; Shi-Long Zhong; Qiu-Xiong Lin; Zhi-Xin Shan; Shu-Guang Lin; Yangxin Li (Molecular Biology Reports, 2012)

Erratum to: NLK is a key regulator of proliferation and migration in gallbladder carcinoma cells - Zhujun Tan; Maolan Li; Wenguang Wu; Lin Zhang; Qichen Ding; Xiangsong Wu; Jiasheng Mu; Yingbin Liu (Molecular and Cellular Biochemistry, 2012)

Influence of UGT genetic polymorphism on the interindividual variability in mitiglinide pharmacokinetic in Chinese - Jing-feng Xu; Zhan-qing Wang; Chen-xia Yan; Qian Xu; Lin Xu; Gang-tao Zhao; Yong-ge Yang (Medicinal Chemistry Research, 2012)

Constitutive activation of STAT3 is predictive of poor prognosis in human gastric cancer - Hua Xiong; Wan Du; Ji-Lin Wang; Ying-Chao Wang; Jie-Ting Tang; Jie Hong; Jing-Yuan Fang (Journal of Molecular Medicine, 2012)

Lipoxin A4 Inhibits 5-Lipoxygenase Translocation and Leukotrienes Biosynthesis to Exert a Neuroprotective Effect in Cerebral Ischemia/Reperfusion Injury - Le Wu; Sen Miao; Lin-Bing Zou; Ping Wu; Hua Hao; Ke Tang; Pan Zeng; Jing Xiong; Hong-Hua Li; Qiang Wu; Lei Cai; Du-Yun Ye (Journal of Molecular Neuroscience, 2012)

Efficacy of a Therapeutic Vaccine Using Mutated β-amyloid Sensitized Dendritic Cells in Alzheimer’s Mice - Zhongqiu Luo; Jialin Li; Neel R. Nabar; Xiaoyang Lin; Ge Bai; Jianfeng Cai; Shu-Feng Zhou; Chuanhai Cao; Jinhuan Wang (Journal of Neuroimmune Pharmacology, 2012)

Crystal Structures, Interactions with Biomacromolecules and Anticancer Activities of Mn(II), Ni(II), Cu(II) Complexes of Demethylcantharate and 2-Aminopyridine - Fan Zhang; Qiu-Yue Lin; Xiao-Liang Zheng; Ling-Ling Zhang; Qiong Yang; Jia-Ying Gu (Journal of Fluorescence, 2012)

Cool seasons are related to poor prognosis in patients with infective endocarditis - Su-Jung Chen; Tze-Fan Chao; Yenn-Jiang Lin; Li-Wei Lo; Yu-Feng Hu; Ta-Chuan Tuan; Tsui-Lieh Hsu; Wen-Chung Yu; Hsin-Bang Leu; Shih-Lin Chang; Shih-Ann Chen (International Journal of Biometeorology, 2012)

Prediction of hydraulically transmissive fractures using geological and geophysical attributes: a case history from the mid Jhuoshuei River basin, Taiwan - Po-Yi Chou; Hung-Chieh Lo; Shih-Meng Hsu; Yen-Tsu Lin; Chi-Chao Huang (Hydrogeology Journal, 2012)

Rhodococcus sp. Q5, a novel agarolytic bacterium isolated from printing and dyeing wastewater - Zehua Feng; Lin Peng; Mei Chen; Mengying Li (Folia Microbiologica, 2012)

Stream discharge characteristics through urbanization gradient in Danshui River, Taiwan: perspectives from observation and simulation - Jr-Chuan Huang; Chun-Chiang Lin; Shih-Chien Chan; Tsung-Yu Lee; Shih-Chieh Hsu; Cheing-Tung Lee; Jiun-Chuan Lin (Environmental Monitoring and Assessment, 2012)

The effects of cerium on the growth and some antioxidant metabolisms in rice seedlings - Dongwu Liu; Xue Wang; Yousheng Lin; Zhiwei Chen; Hongzhi Xu; Lina Wang (Environmental Science and Pollution Research, 2012)

Clinical Value of ELISA-MPT64 for the Diagnosis of Tuberculous Pleurisy - Zhonghua Liu; Changtai Zhu; Hua Yang; Haili Hu; Yonghong Feng; Lianhua Qin; Zhenling Cui; Aixiao Bi; Ruijuan Zheng; Ruiliang Jin; Lin Fan; Zhongyi Hu (Current Microbiology, 2012)

Addendum to “Simulating cold season snowpack: Impacts of snow albedo and multi-layer snow physics”: Waliser, D., J. Kim, Y. Xue, Y. Chao, A. Eldering, R. Fovell, A. Hall, Q. Li, K. N. Liou, J. McWilliams, S. Kapnick, R. Vasic, F. De Sale, and Y. Yu (2011), Climatic Change, 109 (Suppl 1):S95–S117, DOI 10.1007/s10584-011-0312-5 - Duane E. Waliser; Bin Guan; Jui-Lin F. Li; Jinwon Kim (Climatic Change, 2012)

Perfluorinated Compounds in Surface Water and Organisms from Baiyangdian Lake in North China: Source Profiles, Bioaccumulation and Potential Risk - Zhen Zhou; Yali Shi; Wenhui Li; Lin Xu; Yaqi Cai (Bulletin of Environmental Contamination and Toxicology, 2012)

Dissipation and Residue Determination of Fluoroglycofen-Ethyl in Soybean and Soil by UPLC-MS–MS - Yue Geng; Ran Jia; Chongjiu Li; Xiaodong Ma; Yan Lin (Bulletin of Environmental Contamination and Toxicology, 2012)

Construction of self-cloning, indigenous wine strains of Saccharomyces cerevisiae with enhanced glycerol and glutathione production - Rui-Ying Hao; Yan-Lin Liu; Zhao-Yue Wang; Bo-run Zhang (Biotechnology Letters, 2012)

Heat-processed Gynostemma pentaphyllum extract improves obesity in ob/ob mice by activating AMP-activated protein kinase - Rehman Gauhar; Seung-Lark Hwang; Si-Sung Jeong; Ji-Eun Kim; Hebok Song; Dong Chan Park; Kyung-Sik Song; Tae Young Kim; Won Keun Oh; Tae-Lin Huh (Biotechnology Letters, 2012)

Nuclear transition between the conjunction cells of Phaeodactylum tricornutum Bohlin (Bacillariophyta) - Si Li; Kehou Pan; Baohua Zhu; Lin Zhang (Journal of Ocean University of China, 2012)

Evaluating the monthly and interannual variation of net primary production in response to climate in Wuhan during 2001 to 2010 - Wei Gong; Lunche Wang; Aiwen Lin; Miao Zhang (Geosciences Journal, 2012)

The IL-10 promoter haplotype and cancer risk: evidence from a meta-analysis - Kui Zhang; Lushun Zhang; Xianmin Wang; Lin Zhang (Familial Cancer, 2012)

Mutation screening of RAD51C in high-risk breast and ovarian cancer families - Wenping Lu; Xianshu Wang; Hongsheng Lin; Noralane M. Lindor; Fergus J. Couch (Familial Cancer, 2012)

Is the Evolution of Viviparity Accompanied by a Relative Increase in Maternal Abdomen Size in Lizards? - Yan-Yan Sun; Yu Du; Jing Yang; Tian-Bao Fu; Chi-Xian Lin; Xiang Ji (Evolutionary Biology, 2012)

Isolation and characterization of microsatellite loci in the Reevese’s butterfly lizard Leiolepis reevesii (Agamidae) - Lei Hua; Lu-Xi Mao; Ce Chen; Jian-Fang Gao; Long-Hui Lin (Conservation Genetics Resources, 2012)

Development of microsatellite markers in an ungulate mammal, the Formosan serow (Capricornis swinhoei) - Y. Y. Chang; M. C. Chao; S. T. Ding; E.-C. Lin; H. S. Tsao; H. W. Yuan; P. H. Wang (Conservation Genetics Resources, 2012)

Complete genome sequence of narcissus late season yellows virus infecting Chinese narcissus in China - Shuang-Qing Lin; Jian-Guo Shen; Fang-Luan Gao; Wei Cai; Zhen Huang; Li-Yan Xie; Zu-Jian Wu (Archives of Virology, 2012)

High angle prestack depth migration with absorption compensation - Hui Zhou; He Lin; Shan-Bo Sheng; Han-Ming Chen; Ying Wang (Applied Geophysics, 2012)

Application of 3D GPR attribute technology in archaeological investigations - Wen-Ke Zhao; Gang Tian; Bang-Bing Wang; Zhan-Jie Shi; Jin-Xin Lin (Applied Geophysics, 2012)

Research on seismic survey design for doubly complex areas - Hu Zhao; Cheng Yin; Ming-Sheng Wu; Xiao-Hua Wu; Shu-Lin Pan (Applied Geophysics, 2012)

The Influence of Ischemic Factors on the Migration Rates of Cell Types Involved in Cutaneous and Subcutaneous Pressure Ulcers - Gil Topman; Feng-Huei Lin; Amit Gefen (Annals of Biomedical Engineering, 2012)

Inflamed tumor-associated adipose tissue is a depot for macrophages that stimulate tumor growth and angiogenesis - Marek Wagner; Rolf Bjerkvig; Helge Wiig; Juan M. Melero-Martin; Ruei-Zeng Lin; Michael Klagsbrun; Andrew C. Dudley (Angiogenesis, 2012)

Equal modulation of endothelial cell function by four distinct tissue-specific mesenchymal stem cells - Ruei-Zeng Lin; Rafael Moreno-Luna; Bin Zhou; William T. Pu; Juan M. Melero-Martin (Angiogenesis, 2012)

Niacin improves ischemia-induced neovascularization in diabetic mice by enhancement of endothelial progenitor cell functions independent of changes in plasma lipids - Po-Hsun Huang; Chih-Pei Lin; Chao-Hung Wang; Chia-Hung Chiang; Hsiao-Ya Tsai; Jia-Shiong Chen; Feng-Yen Lin; Hsin-Bang Leu; Tao-Cheng Wu; Jaw-Wen Chen; Shing-Jong Lin (Angiogenesis, 2012)

Characteristics, processes, and causes of the spatio-temporal variabilities of the East Asian monsoon system - Ronghui Huang; Jilong Chen; Lin Wang; Zhongda Lin (Advances in Atmospheric Sciences, 2012)

On the differences and climate impacts of early and late stratospheric polar vortex breakup - Lin Li; Chongyin Li; Jing Pan; Yanke Tan (Advances in Atmospheric Sciences, 2012)

Ethylene antagonizes the inhibition of germination in Arabidopsis induced by salinity by modulating the concentration of hydrogen peroxide - Yingchao Lin; Jiajia Wang; Yuangang Zu; Zhonghua Tang (Acta Physiologiae Plantarum, 2012)

Production of isoflavone genistein in transgenic IFS tobacco roots and its role in stimulating the development of arbuscular mycorrhiza - Zhijing Tan; Rongrong Liu; Yuanlei Hu; Zhongping Lin (Acta Physiologiae Plantarum, 2012)

Effects of fertilization and drought stress on tannin biosynthesis of Casuarina equisetifolia seedlings branchlets - Li Hua Zhang; Hong Bo Shao; Gong Fu Ye; Yi Ming Lin (Acta Physiologiae Plantarum, 2012)

The distribution of chlorophyll a in the tropical eastern Indian Ocean in austral summer - Lisha Hong; Chunsheng Wang; Yadong Zhou; Mianrun Chen; Hongbin Liu; Zhongyang Lin; Xunshu Song (Acta Oceanologica Sinica, 2012)

Spatial and temporal variability of colored dissolved organic matter absorption properties in the Taiwan Strait - Hui Lin; Weidong Guo; Minghui Hu; Cai Lin; Weidong Ji (Acta Oceanologica Sinica, 2012)

Islands of Ice: Influence of Free-Drifting Antarctic Icebergs on Pelagic Marine Ecosystems - Maria Vernet; Kenneth Smith; Adrián Cefarelli; John Helly; Ronald Kaufmann; Hai Lin; David Long; Alison Murray; Bruce Robison; Henry Ruhl; Timothy Shaw; Alana Sherman; et al. (Oceanography, 2012)

Geographic distance and pH drive bacterial distribution in alkaline lake sediments across Tibetan Plateau - Jinbo Xiong; Yongqin Liu; Xiangui Lin; Huayong Zhang; Jun Zeng; Juzhi Hou; Yongping Yang; Tandong Yao; Rob Knight; Haiyan Chu (Environmental Microbiology, 2012)
Summary Continent‐scale biogeography has been extensively studied in soils and marine systems, but little is known about biogeographical patterns in non‐marine sediments. We used barcode pyrosequencing to quantify the effects of local geochemical properties and geographic distance for bacterial community structure and membership, using sediment samples from 15 lakes on the Tibetan Plateau (4–1670 km apart). Bacterial communities were surprisingly diverse, and distinct from soil communities. Four of 26 phyla detected were dominant: Proteobacteria , Bacteroidetes , Firmicutes and Actinobacteria , albeit 20.2% of sequences were unclassified at the phylum level. As previously observed in acidic soil, pH was the dominant factor influencing alkaline sediment community structure, phylotype richness and phylogenetic diversity. In contrast, archaeal communities were less affected by pH. More geographically distant sites had more dissimilar communities ( r = 0.443, P = 0.030). Variance partitioning analysis showed that geographic distance (historical contingencies) contributed more to bacterial community variation (12.2%) than any other factor, although the environmental factors explained more variance when combined (28.9%). Together, our results show that pH is the best predictor of bacterial community structure in alkaline sediments, and confirm that both geographic distance and chemical factors govern bacterial biogeography in lake sediments.

Time-dependent expression and distribution of Egr-1 during skeletal muscle wound healing in rats - Yan-Yan Fan; Guang-Hua Ye; Ke-Zhi Lin; Lin-Sheng Yu; Shu-Zhen Wu; Miao-Wu Dong; Jun-Ge Han; Xiang-Ping Feng; Xing-Biao Li (Journal of Molecular Histology, 2012)

Calculation of the sensible heat flux of the global ocean using satellite data - Jiayi Pan; Hui Lin (International Journal of Remote Sensing, 2012)

Winter wheat mapping using temporal signatures of MODIS vegetation index data - Huasheng Sun; Aigong Xu; Hui Lin; Lianpeng Zhang; Yan Mei (International Journal of Remote Sensing, 2012)

Image misalignment caused by decimation in image fusion evaluation - Linhai Jing; Qiuming Cheng; Huadong Guo; Qizhong Lin (International Journal of Remote Sensing, 2012)

Landslides and catchment sedimentation in the Ta-Chia River influenced by the 1999 Taiwan Chi-Chi earthquake - Keh-Jian Shou; Li-Yuan Fei; Jiin-Fa Lee; Cheng-Yueh Wei; Sheng-Tsi Huang; You-Chang Lin (International Journal of Remote Sensing, 2012)

A new triterpenoid saponin from Gynostemma pentaphyllum - Lin Shi; Xian-Jun Meng; Jia-Qing Cao; Yu-Qing Zhao (Natural Product Research, 2012)

Physiological impacts of magnesium-deficiency in Citrus seedlings: photosynthesis, antioxidant system and carbohydrates - Gang-Hua Yang; Lin-Tong Yang; Huan-Xin Jiang; Yan Li; Ping Wang; Li-Song Chen (Trees, 2012)

Experimental Investigation on the Filtering Flow Law of Pre-gelled Particle in Porous Media - Jing Wang; Hui-qing Liu; Zeng-lin Wang; Peng-cheng Hou (Transport in Porous Media, 2012)

Molecular characterization of the PpMADS1 gene from peach - Cui Li; Hua Xie; Lin Zhang; Yong Xu; Yun-Fu Li; Rong-Cai Ma (Tree Genetics & Genomes, 2012)

Spatiotemporal dynamics of soil erosion risk for Anji County, China - Zhenlan Jiang; Shiliang Su; Changwei Jing; Shengpan Lin; Xufeng Fei; Jiaping Wu (Stochastic Environmental Research and Risk Assessment, 2012)

Frontiers in reproductive aging—challenge and perspective - Lin Liu (Science China Life Sciences, 2012)

Single nucleotide polymorphisms in the human corticosteroid-binding globulin promoter alter transcriptional activity - Yue Li; Liang Wu; JingHui Lei; Cheng Zhu; HongMei Wang; XiaoGuang Yu; HaiYan Lin (Science China Life Sciences, 2012)

Spectra response from macromolecular structure evolution of tectonically deformed coal of different deformation mechanisms - XiaoShi Li; YiWen Ju; QuanLin Hou; Hong Lin (Science China Earth Sciences, 2012)

Expression of NtPT5 Is Correlated with the Degree of Colonization in Tobacco Roots Inoculated with Glomus etunicatum - Zhijing Tan; Yuanlei Hu; Zhongping Lin (Plant Molecular Biology Reporter, 2012)

Molecular Cloning and Characterization of BcMF22, a Novel Gene Related to Pollen Development and Fertilization in Brassica campestris ssp. chinensis - Yifei Li; Lin Qiu; Li Huang; Jiashu Cao (Plant Molecular Biology Reporter, 2012)

Nanoscale organo-mineral reactions of biochars in ferrosol: an investigation using microscopy - Yun Lin; Paul Munroe; Stephen Joseph; Stephen Kimber; Lukas Van Zwieten (Plant and Soil, 2012)

Large-scale collection and annotation of gene models for date palm (Phoenix dactylifera, L.) - Guangyu Zhang; Linlin Pan; Yuxin Yin; Wanfei Liu; Dawei Huang; Tongwu Zhang; Lei Wang; Chengqi Xin; Qiang Lin; Gaoyuan Sun; Mohammed M. Ba Abdullah; Xiaowei Zhang; et al. (Plant Molecular Biology, 2012)

A new isoform of thioredoxin h group in potato, SbTRXh1, regulates cold-induced sweetening of potato tubers by adjusting sucrose content - Tianjiu He; Botao Song; Jun Liu; Xia Chen; Yongbin Ou; Yuan Lin; Huiling Zhang; Conghua Xie (Plant Cell Reports, 2012)

Ontogenetic shifts in a prey’s chemical defences influence feeding responses of a snake predator - John Llewelyn; Kris Bell; Lin Schwarzkopf; Ross A. Alford; Richard Shine (Oecologia, 2012)

Construction and function of mammary gland specific goat GH expression vector - Qinghua Yu; Qi Tian; Jian Lin; Qiang Zhang; Liqi Zhu; Qian Yang (Molecular Biology Reports, 2012)

An updated meta-analysis of the p53 codon 72 polymorphism and gastric cancer risk - Kui-Jie Liu; Hai-Zhi Qi; Hong-Liang Yao; San-Lin Lei; Zhen-Dong Lei; Tie-Gang Li; Hua Zhao (Molecular Biology Reports, 2012)

Association between polymorphisms of the CYP11A1 gene and polycystic ovary syndrome in Chinese women - Cheng-wei Zhang; Xin-lin Zhang; Yan-jie Xia; Yun-xia Cao; Wen-jun Wang; Pei Xu; Ye-na Che; Xiao-ke Wu; Long Yi; Qian Gao; Yong Wang (Molecular Biology Reports, 2012)

Estrogen improved metabolic syndrome through down-regulation of VEGF and HIF-1α to inhibit hypoxia of periaortic and intra-abdominal fat in ovariectomized female rats - JinWen Xu; QiuLing Xiang; GuiPing Lin; XiaoDong Fu; KeWen Zhou; Ping Jiang; ShuHui Zheng; TingHuai Wang (Molecular Biology Reports, 2012)

Transcriptional responses to drought stress in root and leaf of chickpea seedling - Xiansheng Wang; Ying Liu; Yuying Jia; Hanyan Gu; Hongyu Ma; Tian Yu; Hua Zhang; Quanjia Chen; Lin Ma; Aixing Gu; Jusong Zhang; Shubing Shi; et al. (Molecular Biology Reports, 2012)

Cloning and characterization of miRNAs from maize seedling roots under low phosphorus stress - Zhiming Zhang; Haijian Lin; Yaou Shen; Jian Gao; Kui Xiang; Li Liu; Haiping Ding; Guangsheng Yuan; Hai Lan; Shufeng Zhou; Maojun Zhao; Shibin Gao; et al. (Molecular Biology Reports, 2012)

Overexpression of the halophyte Kalidium foliatum H+-pyrophosphatase gene confers salt and drought tolerance in Arabidopsis thaliana - Manhong Yao; Youling Zeng; Lin Liu; Yunlan Huang; Enfeng Zhao; Fuchun Zhang (Molecular Biology Reports, 2012)

Exploring a sulfone linker utilizing trimethyl aluminum as a cleavage reagent: solid-phase synthesis of sulfonamides and ureas - Tsai-Wen Chung; Chih-Hau Chen; Chu-Chung Lin; Hsien-Jen Wu; Chung-Ming Sun; Wen-Sheng Chung (Molecular Diversity, 2012)

Novel ionic liquid supported-multicomponent reaction toward chimeric bis-heterocycles - Chih-Hau Chen; Chan-Yu Chen; Po-Tsung Lin; Chung-Ming Sun (Molecular Diversity, 2012)

Peroxisome Proliferator-Activated Receptor Gamma (PPAR-γ) and Neurodegenerative Disorders - Yu-Chang Chen; Jui-Sheng Wu; Hsin-Da Tsai; Chien-Yu Huang; Jin-Jer Chen; Grace Y. Sun; Teng-Nan Lin (Molecular Neurobiology, 2012)

The Niujiaotang Cd-rich zinc deposit, Duyun, Guizhou province, southwest China: ore genesis and mechanisms of cadmium concentration - Lin Ye; Nigel J. Cook; Tiegeng Liu; Cristiana L. Ciobanu; Wei Gao; Yulong Yang (Mineralium Deposita, 2012)

An analytical investigation of a sequence of unusual springtime ozone episodes over metropolitan Taichung in 2007 - Wan-Li Cheng; Li-Wei Lai; Walter Den; Shu-Ying Wang; Pay-Liam Lin; Chueh-Ying Pai (Meteorology and Atmospheric Physics, 2012)

A PY-nuclear localization signal is required for nuclear accumulation of HCMV UL79 protein - Lin Wang; Meili Li; Mingsheng Cai; Junji Xing; Shuai Wang; Chunfu Zheng (Medical Microbiology and Immunology, 2012)

Synergistic effects of streptolysin S and streptococcal pyrogenic exotoxin B on the mouse model of group A streptococcal infection - Chih-Hsin Hung; Nina Tsao; Yi-Fang Zeng; Shiou-Ling Lu; Chuan Chiang-Ni; Yee-Shin Lin; Jiunn-Jong Wu; Chih-Feng Kuo (Medical Microbiology and Immunology, 2012)

Inhibition of Japanese Encephalitis Virus Infection by the Sulfated Polysaccharide Extracts from Ulva lactuca - Ya-Huang Chiu; Yi-Lin Chan; Tsung-Lin Li; Chang-Jer Wu (Marine Biotechnology, 2012)

Screening for significant atherosclerotic renal artery stenosis with a regression model in patients undergoing transradial coronary angiography/intervention - Li-jin Pu; Ying Shen; Rui-yan Zhang; Qi Zhang; Lin Lu; Feng-hua Ding; Jian Hu; Zheng-kun Yang; Wei-feng Shen (Journal of Zhejiang University-SCIENCE B, 2012)

Soil microbial communities and enzyme activities in a reclaimed coastal soil chronosequence under rice–barley cropping - Qinglin Fu; Chen Liu; Nengfei Ding; Yicheng Lin; Bin Guo; Jiafa Luo; Hailong Wang (Journal of Soils and Sediments, 2012)

Does South‐to‐North Water Transfer Reduce the Environmental Impact of Water Consumption in China? - Chen Lin; Sangwon Suh; Stephan Pfister (Journal of Industrial Ecology, 2012)
Summary The South‐to‐North Water Transfer Project (SNWTP) is planned in China to alleviate the problem of the heterogeneous distribution of water resources. The project is expected to reduce water stress and decrease associated environmental impacts in northern China. This article utilizes life cycle impact assessment modeling, including regionalized water consumption impact assessment and an interregional input‐output model, to examine the potential of the SNWTP to reduce the impact of water consumption embodied in final demand. The environmental impacts of water consumption embodied in final demands within northern and southern China are calculated based on current conditions and on the scenario that the water transfer project is completed. The results show that the SNWTP increases the environmental impact of water consumption in southern China and reduces it in northern China. In total, the SNWTP will lead to a 5.74% net reduction in the environmental impact of water consumption embodied in the final demand from both southern and northern China. When monetized, the environmental benefit of the SNWTP could translate into 436 million euro (570 million U.S. dollars) per year, paying the total project cost back over 30 years without considering non‐environmental benefits and costs.

Urban Phosphorus Metabolism through Food Consumption - Gui‐Lin Li; Xuemei Bai; Shen Yu; Hua Zhang; Yong‐Guan Zhu (Journal of Industrial Ecology, 2012)
Summary Urbanization has significant impacts on local, regional, and global biogeochemical cycles, including through nutrient enrichment by food consumption, and especially in rapidly urbanizing countries. This article presents a time‐series estimation of phosphorus (P) metabolism through food consumption in Chinese cities and examines its relationship to income level during the period 1985–2006. Our results show that approximately 39% of the total dietary P inflow is exported through direct sewage discharge without treatment, 35% is exported via the output of solid human excreta, 7% is exported through sewage sludge landfill, and 19% is left within urban areas. The total inflow of dietary P to urban systems increases with per capita disposable income level. Furthermore, the ratio of dietary P remaining in urban systems to total dietary P inflow, the dietary P remaining in urban systems per capita, and the dietary P remaining per unit urban built‐up area respond in an inverted U shape to increases in per capita disposable income; the per capita outflow of dietary P shows a U‐shaped response. These relationships may indicate that the impact of urban dietary P on urban environmental systems follows the traditional environmental Kuznets curve, while the environmental impact of urban dietary P on surrounding nonurban ecosystems initially decreases but then increases with the rising income of urban residents.

Study of ionospheric anomalies due to impact of typhoon using Principal Component Analysis and image processing - JYH-WOEI LIN (Journal of Earth System Science, 2012)

Isolation and characterization of a long-chain acyl-coenzyme A synthetase encoding gene from the marine microalga Nannochloropsis oculata - Lin Zhang; Xiaolei Ma; Guanpin Yang; Baohua Zhu; Jichang Han; Wengong Yu; Kehou Pan (Journal of Applied Phycology, 2012)

Chronic aspiration shifts the immune response from adaptive immunity to innate immunity in a murine model of asthma - Kuei-Ying Su; Anitra D. Thomas; Jui-Chih Chang; Jason H. Leung; Sean M. Lee; Zoie E. Holzknecht; Mary Lou Everett; W. Michael Foster; Monica Kraft; William Parker; R. Duane Davis; Shu S. Lin (Inflammation Research, 2012)

Coexisting mutations/polymorphisms of the long QT syndrome genes in patients with repaired Tetralogy of Fallot are associated with the risks of life-threatening events - Shuenn-Nan Chiu; Mei-Hwan Wu; Ming-Jai Su; Jou-Kou Wang; Ming-Tai Lin; Chien-Chih Chang; Hui-Wen Hsu; Ching-Tsuen Shen; Olivier Thériault; Mohamed Chahine (Human Genetics, 2012)

Haplotype variations of gene Ppd-D1 in Aegilops tauschii and their implications on wheat origin - Lin Huang; Qing Wang; Lian-Quan Zhang; Zhong-Wei Yuan; Ji-Rui Wang; Huai-Gang Zhang; You-Liang Zheng; Deng-Cai Liu (Genetic Resources and Crop Evolution, 2012)

Slope Stability Analysis of Earthen Levee Strengthened by High Performance Turf Reinforcement Mat under Hurricane Overtopping Flow Conditions - Yingzi Xu; Lin Li; Farshad Amini (Geotechnical and Geological Engineering, 2012)

Investigation on Soil–Water Characteristic Curves of Untreated and Stabilized Highly Clayey Expansive Soils - Botao Lin; Amy B. Cerato (Geotechnical and Geological Engineering, 2012)

Effects of ambient cadmium with calcium on mRNA expressions of calcium uptake related transporters in zebrafish (Danio rerio) larvae - Chih-Tsen Liu; Ming-Yi Chou; Chia-Hao Lin; Su Mei Wu (Fish Physiology and Biochemistry, 2012)

Emotional primes modulate the responses to others’ pain: an ERP study - Jing Meng; Li Hu; Lin Shen; Zhou Yang; Hong Chen; Xiting Huang; Todd Jackson (Experimental Brain Research, 2012)

Fasudil, a Rho-kinase inhibitor, protects against excessive endurance exercise training-induced cardiac hypertrophy, apoptosis and fibrosis in rats - Tsung-Jung Ho; Chi-Chang Huang; Chih-Yang Huang; Wan-Teng Lin (European Journal of Applied Physiology, 2012)

Characterization of carbapenem-nonsusceptible Klebsiella pneumoniae bloodstream isolates at a Taiwanese hospital: clinical impacts of lowered breakpoints for carbapenems - N. Y. Lee; J. J. Wu; S. H. Lin; W. C. Ko; L. H. Tsai; J. J. Yan (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

Pollution and variation of stream nitrate in a protected high-mountain watershed of Central Taiwan: evidence from nitrate concentration and nitrogen and oxygen isotope compositions - Tsung-Ren Peng; Hsing-Juh Lin; Chung-Ho Wang; Tsang-Sen Liu; Shuh-Ji Kao (Environmental Monitoring and Assessment, 2012)

Production of monoclonal antibody and application in indirect competitive ELISA for detecting okadaic acid and dinophytoxin-1 in seafood - Shi-Ying Lu; Yu Zhou; Yan-Song Li; Chao Lin; Xian-Mei Meng; Dong-Ming Yan; Zhao-Hui Li; Shi-Yu Yu; Zeng-Shan Liu; Hong-Lin Ren (Environmental Science and Pollution Research, 2012)

Binding of triclosan to human serum albumin: insight into the molecular toxicity of emerging contaminant - Jiabin Chen; Xuefei Zhou; Yalei Zhang; Yanqin Zi; Yajie Qian; Haiping Gao; Shuangshuang Lin (Environmental Science and Pollution Research, 2012)

Embryonic exposure to low concentration of bisphenol A affects the development of Oryzias melastigma larvae - Qiansheng Huang; Chao Fang; Yajie Chen; Xinlong Wu; Ting Ye; Yi Lin; Sijun Dong (Environmental Science and Pollution Research, 2012)

Co-remediation of cadmium-polluted soil using stainless steel slag and ammonium humate - Lin Zhuo; Hua Li; Fangqin Cheng; Yonglin Shi; Qiuhua Zhang; Weiyu Shi (Environmental Science and Pollution Research, 2012)

Highly efficient decolorization of Malachite Green by a novel Micrococcus sp. strain BD15 - Lin-Na Du; Ming Zhao; Gang Li; Xiao-Ping Zhao; Yu-Hua Zhao (Environmental Science and Pollution Research, 2012)

Occurrence of diarrheagenic Escherichia coli genes in raw water of water treatment plants - Shih-Wei Huang; Bing-Mu Hsu; Yen-Jui Su; Dar-Der Ji; Wei-Chen Lin; Jyh-Larng Chen; Feng-Cheng Shih; Po-Min Kao; Yi-Chou Chiu (Environmental Science and Pollution Research, 2012)

Biogeochemical cycling of ferric oxyhydroxide affecting As partition in groundwater aquitard - Sheng-Wei Wang; Chen-Wuing Liu; Kuang-Liang Lu; Li-Hung Lin (Environmental Geochemistry and Health, 2012)

Spatial variation of bacterial community structure of the Northern South China Sea in relation to water chemistry - Juan Ling; Jun-De Dong; You-Shao Wang; Yan-Ying Zhang; Chao Deng; Li Lin; Mei-Lin Wu; Fu-Lin Sun (Ecotoxicology, 2012)

Effects of three different PAHs on nitrogen-fixing bacterial diversity in mangrove sediment - Fu-Lin Sun; You-Shao Wang; Cui-Ci Sun; Ya-Lan Peng; Chao Deng (Ecotoxicology, 2012)

Survivals of D. galeata in sub-tropical reservoirs: harmful effects of toxic cyanobacteria in food source - Bo-Ping Han; Xian Lin; Lamei Lei; Jiguang Gu (Ecotoxicology, 2012)

Transcriptional and Functional Studies of a Cd(II)/Pb(II)-Responsive Transcriptional Regulator(CmtR) from Acidithiobacillus ferrooxidans ATCC 23270 - Chunli Zheng; Yanjun Li; Li Nie; Lin Qian; Lu Cai; Jianshe Liu (Current Microbiology, 2012)

Genetic population structure of the masked palm civet Paguma larvata, (Carnivora: Viverridae) in Japan, revealed from analysis of newly identified compound microsatellites - Tomo Inoue; Yayoi Kaneko; Koji Yamazaki; Tomoko Anezaki; Shuuji Yachimori; Keiji Ochiai; Liang-Kong Lin; Kurtis Jai-Chyi Pei; Yen-Jean Chen; Shih-Wei Chang; Ryuichi Masuda (Conservation Genetics, 2012)

Gastrectomy and risk of pancreatic cancer: systematic review and meta-analysis of observational studies - Yuanfeng Gong; Quanbo Zhou; Yu Zhou; Qing Lin; Bing Zeng; Rufu Chen; Zhihua Li (Cancer Causes & Control, 2012)

Cloning, expression and characterization of meso-2,3-butanediol dehydrogenase from Klebsiella pneumoniae - Gen Lin Zhang; Cui Wei Wang; Chun Li (Biotechnology Letters, 2012)

Biocatalytic resolution of benzyl glycidyl ether and its derivates by Talaromyces flavus: effect of phenyl ring substituents on enantioselectivity - Chun Wei; Yunyun Chen; Honglei Shen; Shan Wang; Lin Chen; Qing Zhu (Biotechnology Letters, 2012)

Pharmacokinetics, Tissue Distribution, and Plasma Protein Binding Study of Platinum Originating from Dicycloplatin, a Novel Antitumor Supramolecule, in Rats and Dogs by ICP-MS - Di Zhao; Yongjie Zhang; Chunxiang Xu; Can Dong; Hui Lin; Lingli Zhang; Cuiyun Li; Shuangxia Ren; Xin Wang; Shuoye Yang; Deen Han; Xijing Chen (Biological Trace Element Research, 2012)

Isoform specific regulation of divalent metal (ion) transporter (DMT1) by proteasomal degradation - Michael D. Garrick; Lin Zhao; Jerome A. Roth; Houbo Jiang; Jian Feng; Natalie J. Foot; Hazel Dalton; Sharad Kumar; Laura M. Garrick (BioMetals, 2012)

Disruption of Bombyx mori nucleopolyhedrovirus ORF71 (Bm71) results in inefficient budded virus production and decreased virulence in host larvae - Min-Juan Zhang; Ruo-Lin Cheng; Yi-Han Lou; Wan-Lu Ye; Tao Zhang; Xiao-Ying Fan; Hai-Wei Fan; Chuan-Xi Zhang (Virus Genes, 2012)

Neuromuscular complications in HIV: effects of aging - Jessica Robinson-Papp; Ik Lin Tan; David M. Simpson (Journal of NeuroVirology, 2012)

Changes in the thermal and hydraulic regime within the active layer in the Qinghai-Tibet Plateau - Changwei Xie; Lin Zhao; Tonghua Wu; Xicheng Dong (Journal of Mountain Science, 2012)

The mitochondrial genome of the quiet-calling katydids, Xizicus fascipes (Orthoptera: Tettigoniidae: Meconematinae) - MING RU YANG; ZHI JUN ZHOU; YAN LIN CHANG; LE HONG ZHAO (Journal of Genetics, 2012)

Stratigraphic architecture and computer modelling of carbonate platform margin, late ordovician Lianglitage formation, Central Tarim Basin - Hao Li; Changsong Lin; Yanmei Zhang; Rongxi Zhang; Zhifeng Rui; Lili Huang (Journal of Earth Science, 2012)

Temporal and spatial evolution analysis: The early Paleozoic Paleo-Uplifts in the Tarim basin - Hao Liu; Changsong Lin; Yingmin Wang; Dishuo Zhang (Journal of Earth Science, 2012)

Detrital zircon U-Pb geochronology and its provenance implications on Silurian Tarim basin - Jingyan Liu; Changsong Lin; Sitian Li; Zhenzhong Cai; Shiqiang Xia; Chao Fu; Yongquan Liu (Journal of Earth Science, 2012)

Major unconformities, tectonostratigraphic frameword, and evolution of the superimposed Tarim basin, Northwest China - Changsong Lin; Hao Li; Jingyan Liu (Journal of Earth Science, 2012)

Structural and functional conservation of CLEC-2 with the species-specific regulation of transcript expression in evolution - Lan Wang; Shifang Ren; Haiyan Zhu; Dongmei Zhang; Yuqing Hao; Yuanyuan Ruan; Lei Zhou; Chiayu Lee; Lin Qiu; Xiaojing Yun; Jianhui Xie (Glycoconjugate Journal, 2012)

Structural characterization and immunostimulatory activity of a novel linear α-(1 → 6)-D-glucan isolated from Panax ginseng C. A. Meyer - Lin Sun; Xiaoxia Peng; Pan Sun; Jiahong Shi; Xiaowen Yuan; Jingjing Zhu; Guihua Tai; Yifa Zhou (Glycoconjugate Journal, 2012)

Tetrapeptide H-Ala-Glu-Asp-Arg-OH Stimulates Expression of Cytoskeletal and Nuclear Matrix Proteins - V. Kh. Khavinson; N. S. Lin’kova; V. O. Polyakova; I. M. Kvetnoy; V. V. Benberin; M. M. D’yakonov; Yu. S. Titkov (Bulletin of Experimental Biology and Medicine, 2012)

Effect of Chitinase on Resistance to Fungal Pathogens in Sea Buckthorn, Hippophae rhamnoides, and Cloning of Class I and III Chitinase Genes - Yan-Lin Sun; Soon-Kwan Hong (Biochemical Genetics, 2012)

Molecular Characteristics of the Porcine TIMD4 Gene and Its Association Analysis - Jing Yuan; Zhong-Lin Tang; Shulin Yang; Ji-Yue Cao; Kui Li (Biochemical Genetics, 2012)

Antigen capture ELISA system for henipaviruses using polyclonal antibodies obtained by DNA immunization - Yoshihiro Kaku; Akira Noguchi; Glenn A. Marsh; Jennifer A. Barr; Akiko Okutani; Kozue Hotta; Boldbaatar Bazartseren; Christopher C. Broder; Akio Yamada; Satoshi Inoue; Lin-Fa Wang (Archives of Virology, 2012)

Development of a fluorescent-intercalating-dye-based reverse transcription loop-mediated isothermal amplification assay for rapid detection of seasonal Japanese B encephalitis outbreaks in pigs - C. J. Tian; Z. X. Lin; X. M. He; Q. Luo; C. B. Luo; H. Q. Yu; R. Chen; X. W. Wu; D. Z. Zhu; Z. J. Ren; Y. Z. Bi; J. Ji (Archives of Virology, 2012)

Sequencing and analysis of the complete genome of Rana grylio virus (RGV) - Xiao-Ying Lei; Tong Ou; Ruo-Lin Zhu; Qi-Ya Zhang (Archives of Virology, 2012)

The effect of the red wine polyphenol resveratrol on a rat model of biliary obstructed cholestasis: involvement of anti-apoptotic signalling, mitochondrial biogenesis and the induction of autophagy - Tsu-Kung Lin; Li-Tung Huang; Ying-Hsien Huang; Mao-Meng Tiao; Kuo-Shu Tang; Chia-Wei Liou (Apoptosis, 2012)

Juglanthraquinone C, a novel natural compound derived from Juglans mandshurica Maxim, induces S phase arrest and apoptosis in HepG2 cells - Yao Yao; Yu-Wei Zhang; Lu-Guo Sun; Biao Liu; Yong-Li Bao; Hua Lin; Yu Zhang; Li-Hua Zheng; Ying Sun; Chun-Lei Yu; Yin Wu; Guan-Nan Wang; et al. (Apoptosis, 2012)

Pleistocene speciation with and without gene flow in Euphaea damselflies of subtropical and tropical East Asian islands - YAT‐HUNG LEE; CHUNG‐PING LIN (Molecular Ecology, 2012)
Climatic oscillations during the Pleistocene period could have had a profound impact on the origin of tropical species by the alternation of allopatric isolation and interpopulation gene flow cycles. However, whether tropical speciation involves strictly allopatric isolation, or proceeds in the face of homogenizing gene flow, is relatively unclear. Here, we investigated geographical modes of speciation in four closely related Euphaea damselfly species endemic to the subtropical and tropical East Asian islands using coalescent analyses of a multilocus data set. The reconstructed phylogenies demonstrated distinct species status for each of the four species and the existence of two sister species pairs, Euphaea formosa / E. yayeyamana and E. decorata / E. ornata . The species divergence time of the sibling Euphaea damselflies dates back to within the last one Mya of the Middle to Lower Pleistocene. The speciation between the populous E. formosa of Taiwan and the less numerous E. yayeyamana of the Yaeyama islands occurred despite significant bidirectional, asymmetric gene flow, which is strongly inconsistent with a strictly allopatric model. In contrast, speciation of the approximately equal‐sized populations of E. decorata of the southeast Asian mainland and E. ornata of Hainan is inferred to have involved allopatric divergence without gene flow. Our findings suggest that differential selection of natural or sexual environments is a prominent driver of species divergence in subtropical E. formosa and E. yayeyamana ; whereas for tropical E. decorata and E. ornata at lower latitudes, allopatric isolation may well be a pivotal promoter of species formation.

Leaf element concentrations of terrestrial plants across China are influenced by taxonomy and the environment - Shi‐Bao Zhang; Jiao‐Lin Zhang; J. W. Ferry Slik; Kun‐Fang Cao (Global Ecology and Biogeography, 2012)
Aim The productivity, functioning and biogeochemical cycles of terrestrial ecosystems are strongly affected by leaf element concentrations. Understanding the biological and ecological factors affecting leaf element concentrations is therefore important for modelling the productivity and nutrient fluxes of ecosystems and their responses to global change. The present study aimed to determine how leaf element concentrations are linked to taxonomy and the environment. Location China. Methods The concentrations of 10 leaf elements of 702 terrestrial plant species from different biomes were extracted from publications. The links between environmental variables, taxonomy and leaf elements were analyzed using phylogenetically comparative methods and partial Mantel tests. Results Taxonomy had stronger effects on leaf S and SiO 2 than latitude, explaining 40.2–43.9% of total variation, whereas latitude had stronger effects on leaf N, P, K, Fe, Al, Mn, Na and Ca concentrations, explaining 19.5–52.1% of total variation. Leaf N, S, Al, Fe and Na concentrations were correlated with mean annual precipitation (MAP), while leaf N, P and Fe concentrations were correlated with mean annual temperature (MAT). Latitude, MAP and MAT were significantly correlated with the first axis of a principal components analysis (PCA). This first axis was associated with leaf elements involved in protein synthesis and photosynthesis. The other PCA axes, which were not correlated with MAT, latitude and MAP, were associated with leaf elements responsible for cell structure and enzymes. Main conclusions Leaf element concentrations of terrestrial plants in China were correlated with climate, latitude and taxonomy. With the exception of S and SiO 2 , the environmental factors were more important in explaining leaf element variation than taxonomy. Therefore, changes in temperature and precipitation will directly affect the spatial patterns of leaf elements and thus the associated nutrient fluxes and ecosystem functioning.

Profiling tropospheric refractivity in real time, based on a relevance vector machine and single ground-based GPS receiver - Leke Lin; Zhenwei Zhao; Qinglin Zhu; Yerong Zhang (International Journal of Remote Sensing, 2012)

A new phenylalkanoid from the rhizomes of Zingiber officinale - Soong-Yu Kuo; Rong-Jyh Lin; Yu-Ting Yeh; Jun-Yen Lee; Chung-Yi Chen (Natural Product Research, 2012)

A new furanocoumarin from the mangrove endophytic fungus Penicillium sp. (ZH16) - Zhongjing Huang; Jianxiang Yang; Xiaoling Cai; Zhigang She; Yongcheng Lin (Natural Product Research, 2012)

Mathematical Models’ Establishment of Hot-Air Drying for Spratelloides gracilis - Yuting Ding; Yiming Hu; Jianyou Zhang; Fei Lu; Lin Liu (Journal of Aquatic Food Product Technology, 2012)

Amino Acid Profiles of Bivalve Mollusks from Beibu Gulf, China - De-Wei Chen; Jian Su; Xiao-Ling Liu; Dong-Mei Yan; Ying Lin; Wei-Ming Jiang; Xiao-Han Chen (Journal of Aquatic Food Product Technology, 2012)

Interactions of Denitrifying Bacteria, Actinomycetes, and Fungi on Nitrate Removal in Mix-Culturing Systems - Xiurong Lin; Lixiang Cao; Jian Xiong; Renduo Zhang (Water, Air, & Soil Pollution, 2012)

Identification of a major QTL for silique length and seed weight in oilseed rape (Brassica napus L.) - Pu Yang; Chang Shu; Lin Chen; Jinsong Xu; Jiangsheng Wu; Kede Liu (Theoretical and Applied Genetics, 2012)

Exploring the spatial and temporal relationships between mosquito population dynamics and dengue outbreaks based on climatic factors - Ching-Tsan Tsai; Fung-Chang Sung; Patrick S. Chen; Shu-Chiung Lin (Stochastic Environmental Research and Risk Assessment, 2012)

Restudy of the storage and migration model of the Quaternary groundwater in Beijing Plain area - YuanZhang Liu; Qiang Wu; Pei Lin; JiuRong Liu; LiTing Xing; ZhiHui Gao (Science China Earth Sciences, 2012)

A geostrophic empirical mode based on altimetric sea surface height - Lin Zhang; Che Sun (Science China Earth Sciences, 2012)

Two novel positive cis-regulatory elements involved in green tissue-specific promoter activity in rice (Oryza sativa L ssp.) - Rongjian Ye; Fei Zhou; Yongjun Lin (Plant Cell Reports, 2012)

Expression profile analysis of the polygalacturonase-inhibiting protein genes in rice and their responses to phytohormones and fungal infection - Liaoxun Lu; Fei Zhou; Yong Zhou; Xiaolei Fan; Shuifeng Ye; Lei Wang; Hao Chen; Yongjun Lin (Plant Cell Reports, 2012)

Identification and characterization of differentially expressed genes in the halophyte Halostachys caspica under salt stress - Lin Liu; Yan Wang; Youling Zeng; Yakupjan Haxim; Fuchun Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Thermal infrared anomalies as a precursor of strong earthquakes in the distant future - Qing-Lin Yao; Zu-Ji Qiang (Natural Hazards, 2012)

Celecoxib inhibits growth of human autosomal dominant polycystic kidney cyst-lining epithelial cells through the VEGF/Raf/MAPK/ERK signaling pathway - Tao Xu; Nian-Song Wang; Li-Li Fu; Chao-Yang Ye; Sheng-Qiang Yu; Chang-Lin Mei (Molecular Biology Reports, 2012)

Endothelin-induced differentiation of Nkx2.5+ cardiac progenitor cells into pacemaking cells - Xi Zhang; Jin-Ping Guo; Ya-Li Chi; Yan-Chun Liu; Chuan-Sen Zhang; Xiang-Qun Yang; Hai-Yan Lin; Er-Peng Jiang; Shao-Hu Xiong; Zhi-Ying Zhang; Bao-Hai Liu (Molecular and Cellular Biochemistry, 2012)

Transcriptional regulation of platelet-derived growth factor-B chain by thrombin in endothelial cells: involvement of Egr-1 and CREB-binding protein - Jing Chen; Lin Xu; Sisi Chen; Jian Yang; Hong Jiang (Molecular and Cellular Biochemistry, 2012)

Study on synthesis of thalidomide analogues and their bioactivities; inhibition on iNOS pathway and cytotoxic effects - Chao-Bin Yeh; Pen-Yuan Lin; Jin-Ming Hwang; Chi-Jung Su; Ying-Tung Yeh; Shun-Fa Yang; Ming-Chih Chou (Medicinal Chemistry Research, 2012)

Signal Transducer and Activator of Transcription 2 (STAT2) Metabolism Coupling Postmitotic Outgrowth to Visual and Sound Perception Network in Human Left Cerebrum by Biocomputation - Lin Wang; Juxiang Huang; Minghu Jiang; Hong Lin (Journal of Molecular Neuroscience, 2012)

Calreticulin Mediates Nerve Growth Factor-Induced Neuronal Differentiation - Yu-Yin Shih; Akira Nakagawara; Hsinyu Lee; Hsueh-Fen Juan; Yung-Ming Jeng; Dong-Tsamn Lin; Yung-Li Yang; Yeou-Guang Tsay; Min-Chuan Huang; Chien-Yuan Pan; Wen-Ming Hsu; Yung-Feng Liao (Journal of Molecular Neuroscience, 2012)

Analysis of Isocitrate Dehydrogenase 1 Mutation in 97 Patients with Glioma - You-Xin Zhou; Jun-Xiang Wang; Ming Feng; Chun-Ming Sun; Ting Sun; Gui-Lin Chen; Zi-Wei Du (Journal of Molecular Neuroscience, 2012)

Highly Sensitive Detection of Residual Chlorpromazine Hydrochloride with Solid Substrate Room Temperature Phosphorimetry - Jia-Ming Liu; Li-ping Lin; Xin-Xing Wang; Xuan Lin; Ping Zhou; Shao-Qin Lin; Zhi-Yong Zheng (Journal of Fluorescence, 2012)

Simultaneous Quantitative Analysis of Three Compounds Using Three-Dimensional Fluorescence Spectra Based on Digital Image Techniques - Hong Lin Zhai; Zhi Jie Shan; Rui Na Li; E Yu (Journal of Fluorescence, 2012)

Phenological responses of Ulmus pumila (Siberian Elm) to climate change in the temperate zone of China - Xiaoqiu Chen; Lin Xu (International Journal of Biometeorology, 2012)

Influence of weather conditions on hiking behavior - Ching Li; Shu-Hua Lin (International Journal of Biometeorology, 2012)

Erratum to: Association between gout and polymorphisms in GCKR in male Han Chinese - Jing Wang; Shiguo Liu; Binbin Wang; Zhimin Miao; Lin Han; Nan Chu; Kun Zhang; Dongmei Meng; Changgui Li; Xu Ma (Human Genetics, 2012)

Association between gout and polymorphisms in GCKR in male Han Chinese - Jing Wang; Shiguo Liu; Binbin Wang; Zhimin Miao; Lin Han; Nan Chu; Kun Zhang; Dongmei Meng; Changgui Li; Xu Ma (Human Genetics, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

The human lactase persistence-associated SNP −13910*T enables in vivo functional persistence of lactase promoter–reporter transgene expression - Lin Fang; Jong Kun Ahn; Dariusz Wodziak; Eric Sibley (Human Genetics, 2012)

Validation of prostate cancer risk-related loci identified from genome-wide association studies using family-based association analysis: evidence from the International Consortium for Prostate Cancer Genetics (ICPCG) - Guangfu Jin; Lingyi Lu; Kathleen A. Cooney; Anna M. Ray; Kimberly A. Zuhlke; Ethan M. Lange; Lisa A. Cannon-Albright; Nicola J. Camp; Craig C. Teerlink; Liesel M. FitzGerald; Janet L. Stanford; Kathleen E. Wiley; et al. (Human Genetics, 2012)

CCDC134 interacts with hADA2a and functions as a regulator of hADA2a in acetyltransferase activity, DNA damage-induced apoptosis and cell cycle arrest - Jing Huang; Li Zhang; Wei Liu; Qinyuan Liao; Taiping Shi; Lin Xiao; Fanlei Hu; Xiaoyan Qiu (Histochemistry and Cell Biology, 2012)

Ralstonia solanacearum nlpD (RSc1206) contributes to host adaptation - Chi-Yin Hsieh; Jaw-Fen Wang; Pei-Cheng Huang; Der-Kang Lu; Yu-Mei Lin; Wen-Chieh Yang; Chiu-Ping Cheng (European Journal of Plant Pathology, 2012)

One-step multiplex RT-PCR for simultaneous detection of four pome tree viroids - Liming Lin; Ruhui Li; Ray Mock; Gary Kinard (European Journal of Plant Pathology, 2012)

QTL detection of seven spike-related traits and their genetic correlations in wheat using two related RIL populations - Fa Cui; Anming Ding; Jun Li; Chunhua Zhao; Lin Wang; Xiuqin Wang; Xiaolei Qi; Xingfeng Li; Guoyu Li; Jurong Gao; Honggang Wang (Euphytica, 2012)

Molecular detection and comparison of Acanthamoeba genotypes in different functions of watersheds in Taiwan - Po-Min Kao; Bing-Mu Hsu; Nai-Hsiung Chen; Kuan-Hao Huang; Chin-Chun Huang; Dar-Der Ji; Jung-Sheng Chen; Wei-Chen Lin; Shih-Wei Huang; Yi-Chou Chiu (Environmental Monitoring and Assessment, 2012)

Effects of the fungicide metiram in outdoor freshwater microcosms: responses of invertebrates, primary producers and microbes - Ronghua Lin; Laura Buijse; Mauricio R. Dimitrov; Peter Dohmen; Sujitra Kosol; Lorraine Maltby; Ivo Roessink; Jos A. Sinkeldam; Hauke Smidt; René P. A. Van Wijngaarden; Theo C. M. Brock (Ecotoxicology, 2012)

Effects of 1,1,1-trichloroethane on enzymatic activity and bacterial community in anaerobic microcosm form sequencing batch reactors - Hui Li; Wei Zhang; Lu Li; Yong-Di Liu; Kuang-Fei Lin; Shu-Guang Lu; Bo-Zhong Mu; Xiao-Ming Du; Qiang Lu; Qian Zhang; Ting-Ting Shen; Bing-Zhi Li; et al. (Ecotoxicology, 2012)

Biodegradation of bensulfuron-methyl and its effect on bacterial community in paddy soils - Xiao-Yan Lin; Yu-Yi Yang; Yu-Hua Zhao; Qing-Lin Fu (Ecotoxicology, 2012)

Effects of climate change and elevated atmospheric CO2 on soil organic carbon: a response equation - Zhongbing Lin; Renduo Zhang (Climatic Change, 2012)

Indian summer monsoon influence on the climate in the North Atlantic–European region - Hai Lin; Zhiwei Wu (Climate Dynamics, 2012)

Resistance training and the risk of colon and rectal cancers - Terry Boyle; Fiona Bull; Lin Fritschi; Jane Heyworth (Cancer Causes & Control, 2012)

An alternative method for cDNA cloning from surrogate eukaryotic cells transfected with the corresponding genomic DNA - Lin-yong Hu; Chen-chen Cui; Yu-jie Song; Xiang-guo Wang; Ya-ping Jin; Ai-hua Wang; Yong Zhang (Biotechnology Letters, 2012)

Isolation of high quality and yield of RNA from Agaricus bisporus with a simple, inexpensive and reliable method - De-mei Meng; Lin Shen; Xin-hua Zhang; Ji-ping Sheng (Biotechnology Letters, 2012)

Development of a Procedure to Determine Standardized Mineral Availabilities in Soybean Meal for Broiler Chicks - Songbai Liu; Sufen Li; Lin Lu; Jingjing Xie; Liyang Zhang; Yong Jiang; Xugang Luo (Biological Trace Element Research, 2012)

Effect of elevated carbon dioxide on growth and nitrogen fixation of two soybean cultivars in northern China - Shu Kee Lam; Xingyu Hao; Erda Lin; Xue Han; Rob Norton; Arvin R. Mosier; Saman Seneweera; Deli Chen (Biology and Fertility of Soils, 2012)

Phosphorus availability and rice grain yield in a paddy soil in response to long-term fertilization - Z. M. Lan; X. J. Lin; F. Wang; H. Zhang; C. R. Chen (Biology and Fertility of Soils, 2012)

Brassica green manure rotation crops reduce potato stem rot caused by Sclerotinia sclerotium - Mohammad Reza Ojaghian; Zhou-qi Cui; Guan-Lin Xie; Bin Li; Jingze Zhang (Australasian Plant Pathology, 2012)

Phylogeny and evolution of porcine teschovirus 8 isolated from pigs in China with reproductive failure - Wencheng Lin; Shangjin Cui; Roland Zell (Archives of Virology, 2012)

Nucleotide sequence of a chickpea chlorotic stunt virus relative that infects pea and faba bean in China - Cui-Ji Zhou; Hai-Ying Xiang; Tao Zhuo; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Bombyx mori nucleopolyhedrovirus ORF54, a viral desmoplakin gene, is associated with the infectivity of budded virions - Min-Juan Zhang; Cai-Hong Tian; Xiao-Ying Fan; Yi-Han Lou; Ruo-Lin Cheng; Chuan-Xi Zhang (Archives of Virology, 2012)

miR-15b and miR-16 regulate TNF mediated hepatocyte apoptosis via BCL2 in acute liver failure - Fangmei An; Bangdong Gong; Hui Wang; Dongshan Yu; Gangde Zhao; Lanyi Lin; Weiliang Tang; Hong Yu; Shisan Bao; Qing Xie (Apoptosis, 2012)

Effect of Carrier Gas Properties on Aerosol Distribution in a CT-based Human Airway Numerical Model - Shinjiro Miyawaki; Merryn H. Tawhai; Eric A. Hoffman; Ching-Long Lin (Annals of Biomedical Engineering, 2012)

Impacts of global emissions of CO, NO x , and CH4 on China tropospheric hydroxyl free radicals - Mingfeng Su; Yunping Lin; Xinqiang Fan; Li Peng; Chunsheng Zhao (Advances in Atmospheric Sciences, 2012)

Molecular mechanism of elicitor-induced tanshinone accumulation in Salvia miltiorrhiza hairy root cultures - Guoyin Kai; Pan Liao; Hui Xu; Jing Wang; Congcong Zhou; Wei Zhou; Yaping Qi; Jianbo Xiao; Yuliang Wang; Lin Zhang (Acta Physiologiae Plantarum, 2012)

Effects of sucrose concentration and exogenous hormones on growth and periplocin accumulation in adventitious roots of Periploca sepium Bunge - Jian Zhang; Wen-Yuan Gao; Juan Wang; Xing-lin Li (Acta Physiologiae Plantarum, 2012)

Phylogeny of three choreotrich genera (Protozoa, Ciliophora, Spirotrichea), with morphological, morphogenetic and molecular investigations on three strobilidiid species - Weiwei Liu; Zhenzhen Yi; Xiaofeng Lin; Alan Warren; Weibo Song (Zoologica Scripta, 2012)
Liu, W., Yi, Z., Lin, X., Warren, A. & Song, W. (2012). Phylogeny of three choreotrich genera (Protozoa, Ciliophora, Spirotrichea), with morphological, morphogenetic and molecular investigations on three strobilidiid species. — Zoologica Scripta , 41 , 417–434. The phylogenetic relationships among three strobilidiid genera, namely Strobilidium , Rimostrombidium and Pelagostrobilidium , are investigated using a combination of morphological, morphogenetic and molecular data. The results indicate that all three genera belong to the same lineage, in which Rimostrombidium evolved first and Strobilidium and Pelagostrobilidium derived later. Improved genus diagnoses for Rimostrombidium and Pelagostrobilidium are supplied. The curved kinety 2 and the caudal spiralling of some somatic kineties are confirmed as generic characters for Pelagostrobilidium and Strobilidium , respectively. In addition, the morphology and morphogenesis of three species, namely R. veniliae ( Montagnes & Taylor, 1994 ) Petz et al., 1995 , P. paraepacrum sp. n. and P. minutum sp. n., isolated from the South China Sea are described. Pelagostrobilidium paraepacrum sp. n. is characterized by the presence of six somatic kineties, 30–32 external and two internal membranelles. Pelagostrobilidium minutum sp. n. is characterized by its extremely small body size, four somatic kineties, and in having one internal and 19–21 external membranelles. Rimostrombidium conicum Kahl, 1932 is transferred to the genus Pelagostrobilidium as P. conicum (Kahl, 1932) comb. nov.

Regional variation in otolith Sr:Ca ratios of African longfinned eel Anguilla mossambica and mottled eel Anguilla marmorata : a challenge to the classic tool for reconstructing migratory histories of fishes - Y.‐J. Lin; B. M. Jessop; O. L. F. Weyl; Y. Iizuka; S.‐H. Lin; W.‐N. Tzeng; C.‐L. Sun (Journal of Fish Biology, 2012)
Otolith Sr:Ca ratios of the African longfinned eel Anguilla mossambica and giant mottled eel Anguilla marmorata from nine freshwater sites in four rivers of South Africa were analysed to reconstruct their migratory life histories between freshwater and saltwater habitats. For A. mossambica , the Sr:Ca ratios in the otolith edge differed significantly among rivers and had large effect sizes, but did not differ among sites within a river. Otolith Sr:Ca ratios did not differ among rivers for A. marmorata . When rivers were pooled, the edge Sr:Ca ratios of A. mossambica were not significantly different from those of A. marmorata . According to the river‐specific critical Sr:Ca ratio distinguishing freshwater from saltwater residence, most A. mossambica and A. marmorata had saltwater habitat experience after settlement in fresh water. This was primarily during their elver stage or early in the yellow eel stage. During the middle and late yellow eel stage, freshwater residency was preferred and only sporadic visits were made to saltwater habitats. The data also suggest that regional variations in otolith Sr:Ca ratios affect the critical Sr:Ca value and are a challenge for the reconstruction of migratory life histories that should be explicitly considered to avoid bias and uncertainty.

Identification and expression analysis of major histocompatibility complex IIB gene in orange‐spotted grouper Epinephelus coioides - D. Q. Lu; S. B. Yi; M. Yao; Y. W. Li; X. C. Liu; Y. Zhang; H. R. Lin (Journal of Fish Biology, 2012)
In this study, complementary DNA (cDNA) and DNA sequences of major histocompatibility complex (MHC) class IIB genes ( mhcIIB ) were cloned from orange‐spotted grouper Epinephelus coioides . The gene structure of E. coioides mhcIIB consists of five exons and four introns, and its deduced amino acid sequence length is 249 amino acids, including a signal peptide, a peptide‐binding region, an IGC1 domain, a transmembrane region and a cytoplasmic tail. A phylogenetic study showed that E. coioides mhcIIB shared 32·0–79·1% identity with those of other teleosts and mammals. Real‐time reverse transcriptase (RT)‐PCR was performed to detect the class IIB gene expression in eight different tissues. To characterize the relationship between E. coioides mhcIIB gene and pathogens, in vivo and in vitro studies were performed. Challenge of Cryptocaryon irritans revealed that class IIB genes were down‐regulated after 24 and 48 h of challenge, and their expression was later restored at 72 h. Stimulation of isolated E. coioides leukocytes with lipopolysaccharide (LPS) and polyinosinic:polycytidylic acid (PolyI:C) significantly increased peripheral blood and spleen mhcIIB expression, while head kidney mhcIIB expression remained constant.

Larval Japanese eel ( Anguilla japonica ) as sub‐surface current bio‐tracers on the East Asia continental shelf - YU‐SAN HAN; HENG ZHANG; YU‐HENG TSENG; MAO‐LIN SHEN (Fisheries Oceanography, 2012)
Larval Japanese eel (leptocephali) are passively transported from their spawning sites of the North Equatorial Current to the Kuroshio and its branch waters for 4–6 months before reaching the East Asian coasts. The larvae mainly stay within water depths between 50–150 m. The dispersal dynamics of larvae thus should reflect the sub‐surface oceanic currents on the East Asia continental shelf. An analysis of Japanese glass eel catch data in East Asian countries during 1985 to 2009, and for Taiwan from 1968 to 2008, indicates that the overall annual catch is generally correlated across countries of East Asia, and between north and west areas of Taiwan. The Kuroshio and its branch waters disperse glass eels throughout East Asian habitats, and the glass eel distribution matches the flow directionality of oceanic currents. Recruitment in western Taiwan occurs with a sequential southwestern to northwestern direction, suggesting that the Taiwan Strait Current penetrates the western coast of Taiwan in the sub‐surface layer in winter. The monthly averaged sub‐surface 50 m circulation pattern in the vicinity of Taiwan and modeled tracer experiments also support the northward winter sub‐surface current in Taiwan Strait. These results suggest that the larval Japanese eel could serve as a valuable bio‐tracer of sub‐surface currents, and the earlier recruitment dynamics of Japanese glass eels in Taiwan could be a good predictor for the subsequent catch in other East Asia areas.

Using coupled fish behavior–hydrodynamic model to investigate spawning migration of Japanese anchovy, Engraulis japonicus , from the East China Sea to Taiwan - CHEN‐YI TU; YU‐HENG TSENG; TAI‐SHENG CHIU; MAO‐LIN SHEN; CHIH‐HAO HSIEH (Fisheries Oceanography, 2012)
Adult Japanese anchovies ( Engraulis japonicus ) migrate from the East China Sea to the coastal region of Taiwan to spawn around late winter and early spring and, later, their larvae constitute important fisheries in Taiwan. However, their migration route and its mechanism remain unclear. To investigate their spawning migration, we used a coupled fish behavior–hydrodynamic modeling approach. The physical field is simulated by the Pacific Ocean adaptation of the TaIwan Multi‐scale Community Ocean Model (TIMCOM) and the fish migration by Lagrangian tracer tracking with the aid of approximation of fish swimming behavior. We investigated three fish behavioral scenarios: (i) passive tracking of the current, (ii) swimming along with the current, and (iii) swimming along with the current and then changing to swimming toward the optimal spawning temperature. The comparison with and without Changjiang discharge is used to investigate the impacts of discharge reduction due to the Three Gorges Dam. Our results suggest that spawning migration of Japanese anchovy from the East China Sea to Taiwan may be aided by the China Coastal Current and that adult anchovies cannot reach the spawning site by passive advection alone. Thus, the swimming behavior of anchovies is crucial during the spawning migration, as it provides extra velocity and the orientation to the favorable spawning grounds. In addition, the adult anchovy is unlikely to reach the coastal area of Taiwan without Changjiang discharge. Our findings indicate that a coupled fish behavior–hydrodynamic model can help understand the influences of physical environment on the migration of Japanese anchovies.

Immunoaffinity chromatography purification and ultra-high-performance liquid chromatography-tandem mass spectrometry determination of four β-agonists in beef - Q.-B. Lin; X.-T. Zhao; H. Song; Y.-L. Pan (Food Additives & Contaminants: Part A, 2012)

A System Dynamic Model and Sensitivity Analysis for Simulating Domestic Pollution Removal in a Free-Water Surface Constructed Wetland - Yung-Chieh Wang; Yu-Pin Lin; Chun-Wei Huang; Li-Chi Chiang; Hone-Jay Chu; Wen-Sheng Ou (Water, Air, & Soil Pollution, 2012)

Defining the Ischemic Penumbra Using Hyperacute Neuroimaging: Deriving Quantitative Ischemic Thresholds - Andria L. Ford; Hongyu An; Katie D. Vo; Weili Lin; Jin-Moo Lee (Translational Stroke Research, 2012)

Editorial - Weili Lin; William J. Powers (Translational Stroke Research, 2012)

Noninvasive Measurements of Cerebral Blood Flow, Oxygen Extraction Fraction, and Oxygen Metabolic Index in Human with Inhalation of Air and Carbogen using Magnetic Resonance Imaging - Hongyu An; Souvik Sen; Yasheng Chen; William J. Powers; Weili Lin (Translational Stroke Research, 2012)

Hyperglycemia as a Predictor of Poor Outcome at Discharge in Patients with Acute Spontaneous Cerebellar Hemorrhage - Yung-Tsan Wu; Tsung-Ying Li; Shao-Chi Lu; Liang-Cheng Chen; Heng-Yi Chu; Shang-Lin Chiang; Shin-Tsu Chang (The Cerebellum, 2012)

Inhibitory effect of Salicornia europaea on the marine alga Skeletonema costatum - Dan Jiang; LingFeng Huang; YongQing Lin; LingLing Nie; SuLian Lv; TingYun Kuang; YinXin Li (Science China Life Sciences, 2012)

Drug-related cues exacerbate decision making and increase craving in heroin addicts at different abstinence times - Gui-Bin Wang; Xiao-Li Zhang; Li-Yan Zhao; Li-Li Sun; Ping Wu; Lin Lu; Jie Shi (Psychopharmacology, 2012)

Probing and tracking organelles in living plant cells - Tong Chen; Xiaohua Wang; Daniel von Wangenheim; Maozhong Zheng; Jozef Šamaj; Wanquan Ji; Jinxing Lin (Protoplasma, 2012)

A dynamic evolution of chromosome in subgenus Potamogeton revealed by physical mapping of rDNA loci detection - Tao Wan; Xiao-lin Zhang; Juraj Gregan; Ying Zhang; Pin Guo; You-hao Guo (Plant Systematics and Evolution, 2012)

Development and Evaluation of Intron and Insertion–Deletion Markers for Gossypium barbadense - Xiaqing Wang; Gaofeng Ren; Ximei Li; Jianli Tu; Zhongxu Lin; Xianlong Zhang (Plant Molecular Biology Reporter, 2012)

BcJMJ30, the Gene Encoding jmjC Domain-Containing Histone Demethylase Is Associated with Pollen Development and Fertilization in Brassica campestris ssp. chinensis - Yifei Li; Lin Qiu; Li Huang; Jiashu Cao (Plant Molecular Biology Reporter, 2012)

Agrobacterium-mediated transformation of centipedegrass (Eremochloa ophiuroides [Munro] Hack.) - Mingxi Liu; Shaoyun Lu; Lin Liu; Jiali Tan; Zhenfei Guo (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Protoplast isolation and culture for somatic hybridisation of rapid cycling Brassica rapa with ‘Anand’ CMS and Brassica juncea - Yu-Ji Lian; Xiao-Mei Zhao; Guang-Zhe Lin; Hak-tae Lim (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

FVCOM model estimate of the location of Air France 447 - Changsheng Chen; Richard Limeburner; Guoping Gao; Qichun Xu; Jianhua Qi; Pengfei Xue; Zhigang Lai; Huichan Lin; Robert Beardsley; Breck Owens; Barry Carlson (Ocean Dynamics, 2012)

Identification and expression of C2H2 transcription factor genes in Carica papaya under abiotic and biotic stresses - Ling Jiang; Lin-jie Pan (Molecular Biology Reports, 2012)

A Common variant near the melanocortin 4 receptor is associated with low-density lipoprotein cholesterol and total cholesterol in the Chinese Han population - Liming Tao; Zhou Zhang; Zhuo Chen; Daizhan Zhou; Weidong Li; Mengyuan Kan; Di Zhang; Lin He; Guoying Huang; Yun Liu (Molecular Biology Reports, 2012)

XPA A23G polymorphism and susceptibility to cancer: a meta-analysis - Jun Liu; Zhen Zhang; Xiao-Lin Cao; Da-Peng Lei; Zhong-Qiu Wang; Tong Jin; Xin-Liang Pan (Molecular Biology Reports, 2012)

Common variant (rs9939609) in the FTO gene is associated with metabolic syndrome - Donghao Zhou; Hongjun Liu; Ming’ai Zhou; Shengxiang Wang; Jingling Zhang; Lin Liao; Fang He (Molecular Biology Reports, 2012)

Loss of E-cadherin promotes the growth, invasion and drug resistance of colorectal cancer cells and is associated with liver metastasis - Xiaobing Chen; Yongsheng Wang; Hongping Xia; Qiwu Wang; Xiaochun Jiang; Zihong Lin; Yuedong Ma; Yang Yang; Minghua Hu (Molecular Biology Reports, 2012)

Effect of active immunization against a recombinant mouse granulocyte-macrophage colony-stimulating factor/somatostatin fusion protein on the growth of mice - Bingbing Wu; Ruili Qi; Bin Li; Taoyan Yuan; Heshan Liu; Jun He; Zhiwei Lin; Weifen Li; Yan Fu; Dong Niu (Molecular Biology Reports, 2012)

Isolation, molecular characterization, and functional analysis of the vacuolar Na+/H+ antiporter genes from the halophyte Karelinia caspica - Lin Liu; Youling Zeng; Xinyan Pan; Fuchun Zhang (Molecular Biology Reports, 2012)

Expression characteristics of two ubiquitin/ribosomal fusion protein genes in the developing testis, accessory gonad and ovary of Chinese mitten crab, Eriocheir sinensis - Qun Wang; Lili Chen; Ying Wang; Weiwei Li; Lin He; Hui Jiang (Molecular Biology Reports, 2012)

Morphology and mechanics of chondroid cells from human adipose-derived Stem cells detected by atomic force microscopy - Simin Luo; Qiping Shi; Zhengang Zha; Ping Yao; Hongsheng Lin; Ning Liu; Hao Wu; Hua Jin; Jiye Cai (Molecular and Cellular Biochemistry, 2012)

Fhl1 as a downstream target of Wnt signaling to promote myogenesis of C2C12 cells - Jing-Yu Lee; I-Chun Chien; Win-Yu Lin; Shao-min Wu; Bo-Huei Wei; Yu-En Lee; Hu-Hui Lee (Molecular and Cellular Biochemistry, 2012)

Ginsenoside Rg1 inhibits autophagy in H9c2 cardiomyocytes exposed to hypoxia/reoxygenation - Zi-Long Zhang; Yan Fan; Mei-Lin Liu (Molecular and Cellular Biochemistry, 2012)

Cloning and expression of the two new variants of Nav1.5/SCN5A in rat brain - Cheng-Tao Ren; Dong-Mei Li; Shao-Wu Ou; Yun-Jie Wang; Yi Lin; Zhi-Hong Zong; Masaki Kameyama; Asako Kameyama (Molecular and Cellular Biochemistry, 2012)

Human anti-EGFL7 recombinant full-length antibodies selected from a mammalian cell-based antibody display library - Feng Li; Yan-Hong Liu; Yan-Wen Li; Qian Ju; Lin Chen; Ping-Li Xie; Yue-Hui Li; Guan-Cheng Li (Molecular and Cellular Biochemistry, 2012)

Chronic cigarette smoke exposure enhances brain-derived neurotrophic factor expression in rats with traumatic brain injury - I-Neng Lee; Martin Hsiu-Chu Lin; Chiu-Yen Chung; Ming-Hsueh Lee; Hsu-Huei Weng; Jen-Tsung Yang (Metabolic Brain Disease, 2012)

Identification of a heat shock cognate protein 70 gene in Chinese soft-shell turtle (Pelodiscus sinensis) and its expression profiles under thermal stress - Xiao-liang Li; Yue Kang; Xiao-yan Zhang; Bing-lin Zhu; Wei-huan Fang (Journal of Zhejiang University-SCIENCE B, 2012)

The Hungtsaiping landslides: from ancient to recent - Kuang-Tsung Chang; Ming-Lang Lin; Jia-Jyun Dong; Chang-Hai Chien (Landslides, 2012)

Arbuscular mycorrhizal fungal community structure and diversity in response to 3-year conservation tillage management in a sandy loam soil in North China - Anna Yang; Junli Hu; Xiangui Lin; Anning Zhu; Junhua Wang; Jue Dai; Ming Hung Wong (Journal of Soils and Sediments, 2012)

Gastrin inhibits a novel, pathological colon cancer signaling pathway involving EGR1, AE2, and P-ERK - Ling-Jun Song; Rui-Jun Liu; Zhi Zeng; Seth L. Alper; Heng-Jing Cui; Yang Lu; Lin Zheng; Zhao-Wen Yan; Guo-Hui Fu (Journal of Molecular Medicine, 2012)

Novel phosphatidylinositol 3-kinase inhibitor NVP-BKM120 induces apoptosis in myeloma cells and shows synergistic anti-myeloma activity with dexamethasone - Yuhuan Zheng; Jing Yang; Jianfei Qian; Liang Zhang; Yong Lu; Haiyan Li; Heather Lin; Yongsheng Lan; Zhiqiang Liu; Jin He; Sungyoul Hong; Sheeba Thomas; et al. (Journal of Molecular Medicine, 2012)

Involvement of CtBP2 in LPS-induced microglial activation - Guowei Zhang; Yaohua Yan; Lihua Kang; Qi Cao; Kaifu Ke; Xinmin Wu; Yilu Gao; Qinglei Hang; Chunmiao Li; Lin Zhu; Qin Yuan; Qiyun Wu; et al. (Journal of Molecular Histology, 2012)

Quercetin modulates activities of Taiwan cobra phospholipase A2 via its effects on membrane structure and membrane-bound mode of phospholipase A2 - Yi-Ling Chiou; Shinne-Ren Lin; Wan-Ping Hu; Long-Sen Chang (Journal of Biosciences, 2012)

Beta-amyloid induced changes in A-type K+ current can alter hippocampo-septal network dynamics - Xin Zou; Damien Coyle; KongFatt Wong-Lin; Liam Maguire (Journal of Computational Neuroscience, 2012)

Enhancing a Cancer Prevention and Control Curriculum Through Interactive Group Discussions - L. P. Forsythe; S. M. Gadalla; J. G. Hamilton; B. M. Heckman-Stoddard; E. E. Kent; G. Y. Lai; S. W. Lin; P. Luhn; J. M. Faupel-Badger (Journal of Cancer Education, 2012)

Impacts of glyphosate on photosynthetic behaviors in Kappaphycus alvarezii and Neosiphonia savatieri detected by JIP-test - Tong Pang; Jianguo Liu; Qian Liu; Litao Zhang; Wei Lin (Journal of Applied Phycology, 2012)

Prevention and treatment of allergic inflammation by an Fcγ-Der f2 fusion protein in a murine model of dust mite-induced asthma - Li-hui Lin; Ping Zheng; John W. M. Yuen; Juan Wang; Juan Zhou; Cun-quan Kong; Xia Peng; Jia Li; Li Li (Immunologic Research, 2012)

Tissue-specific transplantation antigen P35B (TSTA3) immune response–mediated metabolism coupling cell cycle to postreplication repair network in no-tumor hepatitis/cirrhotic tissues (HBV or HCV infection) by biocomputation - Lin Wang; Juxiang Huang; Minghu Jiang; Hong Lin (Immunologic Research, 2012)

Computational prediction and experimental assessment of an HLA-A*0201-restricted cytotoxic T lymphocyte epitope from neutral endopeptidase - Jingbo Zhang; Zhengcai Jia; Zhihua Lin; Jingyi Li; Xiaolan Fu; Yunjian Huang; Jinghong Zhao; Ling Nie; Weiping Hou; Fahuan Yuan; Yuzhang Wu (Immunologic Research, 2012)

Cell cycle-dependent subcellular distribution of ClC-3 in HeLa cells - Jianwen Mao; Xiaobo Li; Weiqiang Chen; Bin Xu; Haifeng Zhang; Hongzhi Li; Liwei Wang; Xiaobao Jin; Jiayong Zhu; Guixian lin; Weizhang Wang; Lixin Chen (Histochemistry and Cell Biology, 2012)

Caffeine’s effect on intermittent sprint cycling performance with different rest intervals - Chia-Lun Lee; Ching-Feng Cheng; Jung-Charng Lin; Hsin-Wei Huang (European Journal of Applied Physiology, 2012)

Reemerging of enterovirus 71 in Taiwan: the age impact on disease severity - S.-M. Wang; T.-S. Ho; H.-C. Lin; H.-Y. Lei; J.-R. Wang; C.-C. Liu (European Journal of Clinical Microbiology & Infectious Diseases, 2012)

QTL underlying field grain drying rate after physiological maturity in maize (Zea Mays L.) - Zhenhua Wang; Xia Wang; Lin Zhang; Xianjun Liu; Hong Di; Tingfeng Li; Xiaochun Jin (Euphytica, 2012)

Comparing removal of trace organic compounds and assimilable organic carbon (AOC) at advanced and traditional water treatment plants - Jie-Chung Lou; Chung-Yi Lin; Jia-Yun Han; Wei-Biu Tseng; Kai-Lin Hsu; Ting-Wei Chang (Environmental Monitoring and Assessment, 2012)

Concentrations of polycyclic aromatic hydrocarbon in the surface sediments from inter-tidal areas of Kenting coast, Taiwan - Jing-O Cheng; Fung-Chi Ko; Jan-Jung Li; Te-Hao Chen; Ying-Ming Cheng; Chon-Lin Lee (Environmental Monitoring and Assessment, 2012)

Response to “Letter to editor re: Ling et al. 2011 (Environ Sci Pollut Res Int 18(6): 877–889)” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Effect of particle size of titanium dioxide nanoparticle aggregates on the degradation of one azo dye - Yang-hsin Shih; Cheng-han Lin (Environmental Science and Pollution Research, 2012)

Detection Methanogens in Newly Settled Sediments from Xuanwu Lake in Nanjing, China - Dong-Lin Zhu; Cheng Sun; Huan He (Current Microbiology, 2012)

Cryotherapy is Associated with Improved Clinical Outcomes of Sorafenib Therapy for Advanced Hepatocellular Carcinoma - Yongping Yang; Yinying Lu; Chunping Wang; Wenlin Bai; Jianhui Qu; Yan Chen; Xiujuan Chang; Linjing An; Lin Zhou; Zhen Zeng; Min Lou; Jiyun Lv (Cell Biochemistry and Biophysics, 2012)

Dietary intake of lignans and risk of adenocarcinoma of the esophagus and gastroesophageal junction - Yulan Lin; Agneta Yngve; Jesper Lagergren; Yunxia Lu (Cancer Causes & Control, 2012)

Understanding the trends in torsional effects in asymmetric-plan buildings - Jui-Liang Lin; Keh-Chyuan Tsai; Ming-Chieh Chuang (Bulletin of Earthquake Engineering, 2012)

Enhancement of biodesulfurization by Pseudomonas delafieldii in a ceramic microsparging aeration system - Xing Lin; Huizhou Liu; Feiyan Zhu; Xuetuan Wei; Qiang Li; Mingfang Luo (Biotechnology Letters, 2012)

Metabolic imaging of mild traumatic brain injury - A. P. Lin; H. J. Liao; S. K. Merugumala; S. P. Prabhu; W. P. Meehan; B. D. Ross (Brain Imaging and Behavior, 2012)

Chronic traumatic encephalopathy: neurodegeneration following repetitive concussive and subconcussive brain trauma - Christine M. Baugh; Julie M. Stamm; David O. Riley; Brandon E. Gavett; Martha E. Shenton; Alexander Lin; Christopher J. Nowinski; Robert C. Cantu; Ann C. McKee; Robert A. Stern (Brain Imaging and Behavior, 2012)

A review of magnetic resonance imaging and diffusion tensor imaging findings in mild traumatic brain injury - M. E. Shenton; H. M. Hamoda; J. S. Schneiderman; S. Bouix; O. Pasternak; Y. Rathi; M.-A. Vu; M. P. Purohit; K. Helmer; I. Koerte; A. P. Lin; C.-F. Westin; et al. (Brain Imaging and Behavior, 2012)

Effects of Taurine–Magnesium Coordination Compound on Ionic Channels in Rat Ventricular Myocytes of Arrhythmia Induced by Ouabain - Lin Zhao; Jianshi Lou; Hong Wu; Yongqiang Yin; Yi Kang (Biological Trace Element Research, 2012)

Copper in Organic Proteinate or Inorganic Sulfate Form is Equally Bioavailable for Broiler Chicks Fed a Conventional Corn–Soybean Meal Diet - Songbai Liu; Lin Lu; Sufen Li; Jingjing Xie; Liyang Zhang; Runlian Wang; Xugang Luo (Biological Trace Element Research, 2012)

Effect of Selenium on the Interaction Between Daunorubicin and Cardiac Myosin - Yang Liu; Bu-hai Li; Xiao-mei Sun; Ai-hua Lin; De-bin Wang (Biological Trace Element Research, 2012)

Synthesis and Bioactive Studies of Complex 8-Hydroxyquinolinato-Bis-(Salicylato) Yttrium (III) - Xu Li; Qiang-Guo Li; Hui Zhang; Ji-Lin Hu; Fei-Hong Yao; De-Jun Yang; Sheng-Xiong Xiao; Li-Juan Ye; Yi Huang; Dong-Cai Guo (Biological Trace Element Research, 2012)

Protective Effect of Naringenin Against Lead-Induced Oxidative Stress in Rats - Jicang Wang; Zijun Yang; Lin Lin; Zhanqin Zhao; Zongping Liu; Xuezhong Liu (Biological Trace Element Research, 2012)

Evaluating the prevalence and molecular epidemiology of echovirus 11 isolated from sewage in Shandong Province, China in 2010 - Jing Yang; Ning Cui; Haiyan Wang; Zexin Tao; Yao Liu; Heng Zhang; Hiromu Yoshida; Yanyan Song; Yong Zhang; Lizhi Song; Yan Li; Xiaojuan Lin; et al. (Virus Genes, 2012)

Cloning and sequence analysis of two banana bunchy top virus genomes in Hainan - Nai-Tong Yu; Yu-Liang Zhang; Tuan-Cheng Feng; Jian-Hua Wang; Mahesh Kulye; Wen-Jun Yang; Zhan-Song Lin; Zhongguo Xiong; Zhi-Xin Liu (Virus Genes, 2012)

Production of cloned transgenic cow expressing omega-3 fatty acids - Xia Wu; Hongsheng Ouyang; Biao Duan; Daxin Pang; Li Zhang; Ting Yuan; Lian Xue; Daibang Ni; Lei Cheng; Shuhua Dong; Zhuying Wei; Lin Li; et al. (Transgenic Research, 2012)

Application of biopharmaceutics classification system (BCS) in drug transport studies across human respiratory epithelial cell monolayers - Hyun-Jong Cho; Prabagar Balakrishnan; Hongxia Lin; Min-Koo Choi; Dae-Duk Kim (Journal of Pharmaceutical Investigation, 2012)

Screening and characterization of the alkaline protease isolated from PLI-1, a strain of Brevibacillus sp. collected from Indonesia’s hot springs - Shuai Wang; Xuezheng Lin; Xiaohang Huang; Li Zheng; Dewi Seswita Zilda (Journal of Ocean University of China, 2012)

Response of runoff to climate change and its future tendency in the source region of Yellow River - Lin Li; Hongyan Shen; Sheng Dai; Jianshe Xiao; Xinghe Shi (Journal of Geographical Sciences, 2012)

An efficient molecular sexing of the vulnerable Chinese egret (Egretta eulophotes) from faeces samples - Xunhe Huang; Xiaoping Zhou; Qingxian Lin; Wenzhen Fang; Xiaolin Chen (Conservation Genetics Resources, 2012)

Elevated risk of hypertension induced by arsenic exposure in Taiwanese rural residents: possible effects of manganese superoxide dismutase (MnSOD) and 8-oxoguanine DNA glycosylase (OGG1) genes - Shiuan-Chih Chen; Chun-Chieh Chen; Chung-Yih Kuo; Chun-Huang Huang; Chin-Hsiu Lin; Zi-Yun Lu; Yi-Yu Chen; Hong-Shen Lee; Ruey-Hong Wong (Archives of Toxicology, 2012)

Co-occurrence of arseniasis and fluorosis due to indoor combustion of high fluorine and arsenic content coal in a rural township in northwest China: epidemiological and toxicological aspects - Guo-fang Lin; Shi-you Gong; Cheng Wei; Ji-gang Chen; Klaus Golka; Jian-hua Shen (Archives of Toxicology, 2012)

Verrucosispora wenchangensis sp. nov., isolated from mangrove soil - Qing-yi Xie; Hai-peng Lin; Lei Li; Roselyn Brown; Michael Goodfellow; Zixin Deng; Kui Hong (Antonie van Leeuwenhoek, 2012)

Diversity‐dependent stability under mowing and nutrient addition: evidence from a 7‐year grassland experiment - Haijun Yang; Lin Jiang; Linghao Li; Ang Li; Mingyu Wu; Shiqiang Wan (Ecology Letters, 2012)
Ecology Letters (2012) Abstract Anthropogenic perturbations may affect biodiversity and ecological stability as well as their relationships. However, diversity–stability patterns and associated mechanisms under human disturbances have rarely been explored. We conducted a 7‐year field experiment examining the effects of mowing and nutrient addition on the diversity and temporal stability of herbaceous plant communities in a temperate steppe in northern China. Mowing increased population and community stability, whereas nutrient addition had the opposite effects. Stability exhibited positive relationships with species richness at population, functional group and community levels. Treatments did not alter these positive diversity–stability relationships, which were associated with the stabilising effect of species richness on component populations, species asynchrony and portfolio effects. Despite the difficulty of pinpointing causal mechanisms of diversity–stability patterns observed in nature, our results suggest that diversity may still be a useful predictor of the stability of ecosystems confronted with anthropogenic disturbances.

A unified three-component scattering model for polarimetric coherent target decomposition - Hong-Zhong Li; Chao Wang; Hong Zhang; Lin Liu (International Journal of Remote Sensing, 2012)

Analysis of genetic diversity among Chinese Pleurotus citrinopileatus Singer cultivars using two molecular marker systems (ISSRs and SRAPs) and morphological traits - Qiu-sheng Zhang; Bing-lian Xu; Lin-de Liu; Qin-qin Yuan; Hong-xin Dong; Xian-hao Cheng; De-ling Lin (World Journal of Microbiology and Biotechnology, 2012)

Molecular characterization of Antarctic actinobacteria and screening for antimicrobial metabolite production - Learn-Han Lee; Yoke-Kqueen Cheah; Shiran Mohd Sidik; Nurul-Syakima Ab Mutalib; Yi-Li Tang; Hai-Peng Lin; Kui Hong (World Journal of Microbiology and Biotechnology, 2012)

Diversity of potential pathogenicity and biofilm formation among Burkholderia cepacia complex water, clinical, and agricultural isolates in China - Muhammad Ibrahim; Qiaomei Tang; Yu Shi; Abdulwareth Almoneafy; Yuan Fang; Liuhu Xu; Wen Li; Bin Li; Guan-Lin Xie (World Journal of Microbiology and Biotechnology, 2012)

Molecular characterization of β-lactam-resistant Escherichia coli isolated from Fu River, China - Li-Kou Zou; Li-Wen Li; Xin Pan; Guo-Bao Tian; Yan Luo; Qi Wu; Bei Li; Lin Cheng; Jiu-Jing Xiao; Su Hu; Yang Zhou; Yu-Juan Pang (World Journal of Microbiology and Biotechnology, 2012)

Hyperspectral Remote Sensing of Total Phosphorus (TP) in Three Central Indiana Water Supply Reservoirs - Kaishan Song; Lin Li; Shuai Li; Lenore Tedesco; Bob Hall; Linhai Li (Water, Air, & Soil Pollution, 2012)

Bayesian mapping of genome-wide epistatic imprinted loci for quantitative traits - Shize Li; Xin Wang; Jiahan Li; Tianfu Yang; Lingjiang Min; Yang Liu; Min Lin; Runqing Yang (Theoretical and Applied Genetics, 2012)

NMDA receptor glycine modulatory site in the ventral tegmental area regulates the acquisition, retrieval, and reconsolidation of cocaine reward memory - Shuang-jiang Zhou; Li-fen Xue; Xue-yi Wang; Wen-gao Jiang; Yan-xue Xue; Jian-feng Liu; Yin-yin He; Yi-xiao Luo; Lin Lu (Psychopharmacology, 2012)

Morphological and photosynthetic variations in the process of spermatia formation from vegetative cells in Porphyra yezoensis Ueda (Bangiales, Rhodophyta) and their responses to desiccation - Rui-Ling Yang; Wei Zhou; Song-Dong Shen; Guang-Ce Wang; Lin-Wen He; Guang-Hua Pan (Planta, 2012)

Salicylic acid-altering Arabidopsis mutants response to salt stress - Lin Hao; Yan Zhao; Dandan Jin; Ling Zhang; Xiaohua Bi; Hongxing Chen; Qiang Xu; Chunyan Ma; Guangzhe Li (Plant and Soil, 2012)

Gene silencing using the recessive rice bacterial blight resistance gene xa13 as a new paradigm in plant breeding - Changyan Li; Jing Wei; Yongjun Lin; Hao Chen (Plant Cell Reports, 2012)

Effects of exogenous nitric oxide on antioxidation and DNA methylation of Dendrobium huoshanense grown under drought stress - Honghong Fan; Tingchun Li; Lei Guan; Zhengpeng Li; Ning Guo; Yongping Cai; Yi Lin (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Regional differences in the relationship between climatic factors, vegetation, land surface conditions, and dust weather in China’s Beijing-Tianjin Sand Source Region - Jianjun Wu; Lin Zhao; Yanting Zheng; Aifeng Lü (Natural Hazards, 2012)

Assessing Taiwan’s energy security under climate change - Shih-Mo Lin; Jun-Chiang Feng; Fu-Kuang Ko (Natural Hazards, 2012)

Differential expression of genes involved in alternative glycolytic pathways, phosphorus scavenging and recycling in response to aluminum and phosphorus interactions in Citrus roots - Lin-Tong Yang; Huan-Xin Jiang; Yi-Ping Qi; Li-Song Chen (Molecular Biology Reports, 2012)

PDGF-induced airway smooth muscle proliferation is associated with Human antigen R activation and could be weakened by AMPK activation - Pengju Zhang; Mingfeng Cao; Yi Liu; Zhimei Lv; Qingrui Yang; Xiaoyan Lin; Huaichen Li; Qiang Wan (Molecular Biology Reports, 2012)

Risk stratification of spontaneous bacterial peritonitis in cirrhosis with ascites based on classification and regression tree analysis - Ke-Qing Shi; Yu-Chen Fan; Li Ying; Xian-Feng Lin; Mei Song; Ling-Fei Li; Xie-Yan Yu; Yong-Ping Chen; Ming-Hua Zheng (Molecular Biology Reports, 2012)

Expression of connective tissue growth factor and interleukin-11 in intratumoral tissue is associated with poor survival after curative resection of hepatocellular carcinoma - Zuo-Lin Xiang; Zhao-Chong Zeng; Jia Fan; Zhao-You Tang; Hai-Ying Zeng (Molecular Biology Reports, 2012)

Cloning and the expression pattern of Spätzle gene during embryonic development and bacterial challenge in Artemia sinica - Lu-ping Zheng; Lin Hou; Miao Yu; Xiang Li; Xiang-yang Zou (Molecular Biology Reports, 2012)

The polymorphisms of IL-4, IL-4R and IL-13 genes and bladder cancer risk in a Chinese population: a case–control study - Haiyan Chu; Lan Ma; Meilin Wang; Danni Shi; Chao Qin; Lin Yuan; Changjun Yin; Zhengdong Zhang (Molecular Biology Reports, 2012)

Identification of an intronic cis-acting element in the human dopamine transporter gene - Ying Zhao; Yanhong Zhou; Nian Xiong; Zhicheng Lin (Molecular Biology Reports, 2012)

VEGF is essential for the growth and migration of human hepatocellular carcinoma cells - Lei Zhang; Jia-Ning Wang; Jun-Ming Tang; Xia Kong; Jian-Ye Yang; Fei Zheng; Ling-Yun Guo; Yong-Zhang Huang; Li Zhang; Lin Tian; Shu-Fen Cao; Chang-Hai Tuo; et al. (Molecular Biology Reports, 2012)

Expression analysis and functional characterization of a novel cold-responsive gene CbCOR15a from Capsella bursa-pastoris - Mingqi Zhou; Lihua Wu; Jing Liang; Chen Shen; Juan Lin (Molecular Biology Reports, 2012)

Modulation of gene expression in cold-induced sweetening resistant potato species Solanum berthaultii exposed to low temperature - Xia Chen; Botao Song; Jun Liu; Jianwen Yang; Tianjiu He; Yuan Lin; Huiling Zhang; Conghua Xie (Molecular Genetics and Genomics, 2012)

Identification of furo[3′, 2′:3,4]naphtho[1,2-d]imidazole derivatives as orally active and selective inhibitors of microsomal prostaglandin E2 synthase-1 (mPGES-1) - Chih-Hua Tseng; Cherng-Chyi Tzeng; Pin-Keng Shih; Chia-Ning Yang; You-Chung Chuang; Shin-I Peng; Chang-Sheng Lin; Jih-Pyang Wang; Chih-Mei Cheng; Yeh-Long Chen (Molecular Diversity, 2012)

A new species of Perenniporia (Polyporales, Basidiomycota) described from southern China based on morphological and molecular characters - Chang-Lin Zhao; Bao-Kai Cui (Mycological Progress, 2012)

Cytology and ultrastructure of interactions between Ustilago esculenta and Zizania latifolia - Jing-Ze Zhang; Fu-Qiang Chu; De-Ping Guo; Kevin D. Hyde; Guang-Lin Xie (Mycological Progress, 2012)

Astragaloside IV prevents MPP+-induced SH-SY5Y cell death via the inhibition of Bax-mediated pathways and ROS production - Zhi-guo Zhang; Lin Wu; Ju-lei Wang; Jian-dong Yang; Jing Zhang; Jian Zhang; Li-hong Li; Yi Xia; Li-bo Yao; Huai-zhou Qin; Guo-dong Gao (Molecular and Cellular Biochemistry, 2012)

Urotensin upregulates transforming growth factor-β1 expression of asthma airway through ERK-dependent pathway - Wei-xi Zhang; Ya-feng Liang; Xiao-ming Wang; Ying Nie; Lei Chong; Li Lin; Chun Chen; Chang-chong Li (Molecular and Cellular Biochemistry, 2012)

Association between TaqIB polymorphism of cholesteryl ester transfer protein and coronary artery disease in the Chinese population - Qi Yu; En-qi Liu; Si-hai Zhao; Ya-feng Li; Yan-li Wang; Yu-long Chen; Ke-na Wei; Bing-qiao Huang; Jian-lin Fan; Peng-hui Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Erbin inhibits TGF-β1-induced EMT in renal tubular epithelial cells through an ERK-dependent pathway - Qiaodan Zhou; Rui Zeng; Chuou Xu; Lili Liu; Lin Chen; Pei Kou; Guangchang Pei; Shoujun Bai; Yamin Zhang; Caixia Li; Song Rong; Min Han; et al. (Journal of Molecular Medicine, 2012)

Mortality in a Chinese chrysotile miner cohort - Xiaorong Wang; Sihao Lin; Eiji Yano; Hong Qiu; Igtanius T. S. Yu; Lapah Tse; Yajia Lan; Mianzhen Wang (International Archives of Occupational and Environmental Health, 2012)

A new insect cell line from pupal ovary of Spodoptera exigua established by stimulation with N-methyl-N′-nitro-N-nitrosoguanidine (MNNG) - Xuan Li; Qilian Qin; Ning Zhang; Wei Zhu; Jihong Zhang; Hongtuo Wang; Lin Miao; Huan Zhang (In Vitro Cellular & Developmental Biology - Animal, 2012)

Experimental study on the effect of waves on netting panels at a range of angles to the wave direction - Wei-hua Song; Zhen-lin Liang; Rong Wan; Fen-Fang Zhao; Kinoshita Takeshi; Liu-yi Huang; Jia-zhi Ma; Bo-hai Chen (Fisheries Science, 2012)

Comparison of artificial neural network (ANN) and partial least squares (PLS) regression models for predicting respiratory ventilation: an exploratory study - Ming-I Brandon Lin; William A. Groves; Andris Freivalds; Eun Gyung Lee; Martin Harper (European Journal of Applied Physiology, 2012)

Norway spruce (Picea abies L.) regeneration and growth of understory trees under single-tree selection silviculture in Finland - C. Julian Lin; Olavi Laiho; Erkki Lähde (European Journal of Forest Research, 2012)

Spatial distribution and multiple sources of heavy metals in the water of Chaohu Lake, Anhui, China - Guolian Li; Guijian Liu; Chuncai Zhou; Chen-Lin Chou; Liugen Zheng; Jizhong Wang (Environmental Monitoring and Assessment, 2012)

Response to “Dr. Luca Giannini’s Letter to the Editor” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Response to “Letter to Editor: Inappropriate exposure data and misleading calculations invalidate the estimates of health risk for airborne titanium dioxide and carbon black nanoparticle exposures in the workplace” - Min-Pei Ling; Chia-Pin Chio; Wei-Chun Chou; Wei-Yu Chen; Nan-Hung Hsieh; Yi-Jun Lin; Chung-Min Liao (Environmental Science and Pollution Research, 2012)

Pt and Pd in sediments from the Pearl River Estuary, South China: background levels, distribution, and source - Li-feng Zhong; Wen Yan; Jie Li; Xiang-lin Tu; Bao-ming Liu; Zhen Xia (Environmental Science and Pollution Research, 2012)

High Growth Rate Downregulates fumA mRNA Transcription but Is Dramatically Compensated by Its mRNA Stability in Escherichia coli - Hsiao-Hsien Lin; Ching-Hsueh Lin; Shiaw-Min Hwang; Ching-Ping Tseng (Current Microbiology, 2012)

Deuterium excess record in a southern Tibetan ice core and its potential climatic implications - Huabiao Zhao; Baiqing Xu; Tandong Yao; Guangjian Wu; Shubiao Lin; Jing Gao; Mo Wang (Climate Dynamics, 2012)

Differential DNA Methylation Status Between Human Preadipocytes and Mature Adipocytes - Jin-gai Zhu; Li Xia; Chen-bo Ji; Chun-mei Zhang; Guan-zhong Zhu; Chun-mei Shi; Lin Chen; Da-ni Qin; Xi-rong Guo (Cell Biochemistry and Biophysics, 2012)

Liquefaction potential and post-liquefaction settlement evaluations of the Chuoshui River Alluvial Fan in Taiwan - Muhsiung Chang; Chih-ping Kuo; Ron-eeh Hsu; Shih-hui Shau; Tin-mei Lin (Bulletin of Engineering Geology and the Environment, 2012)

Internal ribosome entry site mediates protein synthesis in yeast Pichia pastoris - Shuli Liang; Ying Lin; Cheng Li; Yanrui Ye (Biotechnology Letters, 2012)

Biotransformation of ginsenosides Re and Rg1 into ginsenosides Rg2 and Rh1 by recombinant β-glucosidase - Lin-Hu Quan; Jin-Woo Min; Subramaniyam Sathiyamoorthy; Dong-Uk Yang; Yeon-Ju Kim; Deok-Chun Yang (Biotechnology Letters, 2012)

Prokaryotic expression of pathogenesis related protein 1 gene from Nicotiana benthamiana: antifungal activity and preparation of its polyclonal antibody - Feng Zhu; Moyun Xu; Shaodong Wang; Shudan Jia; Ping Zhang; Honghui Lin; Dehui Xi (Biotechnology Letters, 2012)

Relative Bioavailability of Manganese Proteinate for Broilers Fed a Conventional Corn–Soybean Meal Diet - Funing Wang; Lin Lu; Sufen Li; Songbai Liu; Liyang Zhang; Junhu Yao; Xugang Luo (Biological Trace Element Research, 2012)

Influence of Selenium on Body Weights and Immune Organ Indexes in Ducklings Intoxicated with Aflatoxin B1 - Shining Guo; Dayou Shi; Shenquan Liao; Rongsheng Su; Yuanchao Lin; Jiaqiang Pan; Zhaoxin Tang (Biological Trace Element Research, 2012)

Effect of C-terminal truncation on enzyme properties of recombinant amylopullulanase from Thermoanaerobacter pseudoethanolicus - Fu-Pang Lin; Yi-Hsuan Ho; Hsu-Yang Lin; Hui-Ju Lin (Extremophiles, 2012)

Characterization of a new phage, termed ϕA318, which is specific for Vibrio alginolyticus - Ying-Rong Lin; Chi-Wen Chiu; Feng-Yi Chang; Chan-Shing Lin (Archives of Virology, 2012)

Etiology and epidemiology of viral diarrhea in children under the age of five hospitalized in Tianjin, China - Yabo Ouyang; Hui Ma; Min Jin; Xinwei Wang; Jingfeng Wang; Lu Xu; Shuxiang Lin; Zhiqiang Shen; Zhaoli Chen; Zhigang Qiu; Zhixian Gao; Lin Peng; et al. (Archives of Virology, 2012)

Rhizobium helanshanense sp. nov., a bacterium that nodulates Sphaerophysa salsula (Pall.) DC. in China - Wei Qin; Zhen Shan Deng; Lin Xu; Na Na Wang; Ge Hong Wei (Archives of Microbiology, 2012)

Identification and characterization of an indigo-producing oxygenase involved in indole 3-acetic acid utilization by Acinetobacter baumannii - Guang-Huey Lin; Hao-Ping Chen; Jui-Hsin Huang; Tze-Tze Liu; Tze-Kang Lin; Shih-Jon Wang; Cheng-Hsing Tseng; Hung-Yu Shu (Antonie van Leeuwenhoek, 2012)

Interdecadal change in the Antarctic Circumpolar Wave during 1951–2010 - Lingen Bian; Xiang Lin (Advances in Atmospheric Sciences, 2012)

Oxidative stress in greater duckweed (Spirodela polyrhiza) caused by long-term NaCl exposure - In-Hwa Chang; Kai-Teng Cheng; Po-Chuan Huang; Yen-Yu Lin; Lee-Ju Cheng; Tai-Sheng Cheng (Acta Physiologiae Plantarum, 2012)

The expression of a new HD-Zip II gene, MSHB1, involving the inhibitory effect of thidiazuron on somatic embryogenic competence in alfalfa (Medicago sativa L. cv. Jinnan) callus - Xin Hu; Chun-Rong Zhang; Hui Xie; Xia Huang; Yun-Feng Chen; Xue-Lin Huang (Acta Physiologiae Plantarum, 2012)

Investigation of saltwater intrusion and salinity stratification in winter of 2007/2008 in the Zhujiang River Estuary in China - Wei Zhou; Dongxiao Wang; Lin Luo (Acta Oceanologica Sinica, 2012)

Species phylogenetic relatedness, priority effects, and ecosystem functioning - Jiaqi Tan; Zhichao Pu; Wade A. Ryberg; Lin Jiang (Ecology, 2012)
Species immigration history can structure ecological communities through priority effects, which are often mediated by competition. As competition tends to be stronger between species with more similar niches, we hypothesize that species phylogenetic relatedness, under niche conservatism, may be a reasonable surrogate of niche similarity between species, and thus influence the strength of priority effects. We tested this hypothesis using a laboratory microcosm experiment in which we established bacterial species pools with different levels of phylogenetic relatedness and manipulated the immigration history of species from each pool into microcosms. Our results showed that strong priority effects, and hence multiple community states, only emerged for the species pool with the greatest phylogenetic relatedness. Community assembly also resulted in a significant positive relationship between bacterial phylogenetic diversity and ecosystem functions. Interestingly, these results emerged despite a lack of phylogenetic conservatism for most of the bacterial functional traits considered. Our results highlight the utility of phylogenetic information for understanding the structure and functioning of ecological communities, even when phylogenetically conserved functional traits are not identified or measured.

Chemical composition and antioxidant activities of extracts from Apocyni Veneti Folium - Sui-Hong Yan; Ying-Yong Zhao; Hai-Song Zeng; Yongmin Zhang; Rui-Chao Lin; Wen-Ji Sun (Natural Product Research, 2012)

Antioxidant Properties of Seven Cultivated and Natural Edible Seaweed Extracts from Taiwan - Hui-Chiu Lin; Wann-Sheng Tsai; Tsai-Hsin Chiu (Journal of Aquatic Food Product Technology, 2012)

Membrane Bioreactors for Industrial Wastewater Treatment: A Critical Review - Hongjun Lin; Weijue Gao; Fangang Meng; Bao-Qiang Liao; Kam-Tin Leung; Leihong Zhao; Jianrong Chen; Huachang Hong (Critical Reviews in Environmental Science and Technology, 2012)

Assessment of Radar Waveform Retracked Jason-2 Altimetry Sea Surface Heights Near Taiwan Coastal Ocean - Chung-Yen Kuo; Huan-Chin Kao; Hyongki Lee; Kai-Chien Cheng; Li-Ching Lin (Marine Geodesy, 2012)

Gene cloning, expression and characterization of a neoagarotetraose-producing β-agarase from the marine bacterium Agarivorans sp. HZ105 - Bokun Lin; Guoyong Lu; Yandan Zheng; Wei Xie; Shengkang Li; Zhong Hu (World Journal of Microbiology and Biotechnology, 2012)

Identification and analysis of the metabolic functions of a high-salt-tolerant halophilic aromatic yeast Candida etchellsii for soy sauce production - Jie Feng; Xiao-Bei Zhan; Dong Wang; Li-Min Zhang; Chi-Chung Lin (World Journal of Microbiology and Biotechnology, 2012)

Relationships between photosystem II efficiency and photochemical reflectance index under different levels of illumination: comparison among species grown at high- and low elevations through different seasons - Jen-Hsien Weng; Shau-Lian Wong; Kuan-Ming Lai; Rong-Jhih Lin (Trees, 2012)

Salusins protect myocardium against ischemic injury by alleviating endoplasmic reticulum stress - JianFei Wang; Yin Wang; ShiFu Shan; TianTian Hu; HuYan Chen; Jing Tian; AnJing Ren; Xu Zhou; WenJun Yuan; Li Lin (Science China Life Sciences, 2012)

Arctic Oscillation anomaly in winter 2009/2010 and its impacts on weather and climate - Lin Li; ChongYin Li; Jie Song (Science China Earth Sciences, 2012)

Spatial modeling of the Ulmus pumila growing season in China’s temperate zone - Lin Xu; XiaoQiu Chen (Science China Earth Sciences, 2012)

Cyclic electron flow plays an important role in photoprotection for the resurrection plant Paraboea rufescens under drought stress - Wei Huang; Shi-Jian Yang; Shi-Bao Zhang; Jiao-Lin Zhang; Kun-Fang Cao (Planta, 2012)

Proteomic analysis of embryo development in rice (Oryza sativa) - Hong Xu; Weiping Zhang; Yi Gao; Yong Zhao; Lin Guo; Jianbo Wang (Planta, 2012)

Proteomic Analysis of Osmotic Stress-Responsive Proteins in Sugarcane Leaves - Gui Zhou; Li-Tao Yang; Yang-Rui Li; Cheng-Lin Zou; Li-Ping Huang; Li-Hang Qiu; Xing Huang; Manoj Kumar Srivastava (Plant Molecular Biology Reporter, 2012)

Isolation and Characterization of an Anther-Specific Polygalacturonase Gene, BcMF16, in Brassica campestris ssp. chinensis - Aihong Zhang; Lin Qiu; Li Huang; Xiaolin Yu; Gang Lu; Jiashu Cao (Plant Molecular Biology Reporter, 2012)

Interaction between iron plaque and root border cells ameliorates aluminum toxicity of Oryza sativa differing in aluminum tolerance - Miao-Zhen Cai; Shu-Na Zhang; Cheng-Hua Xing; Fang-Mei Wang; Lei Zhu; Ning Wang; Li-Yu Lin (Plant and Soil, 2012)

Random BAC FISH of monocot plants reveals differential distribution of repetitive DNA elements in small and large chromosome species - Go Suzuki; Yuka Ogaki; Nozomi Hokimoto; Lin Xiao; Akie Kikuchi-Taura; Chiaki Harada; Ryozo Okayama; Asami Tsuru; Misa Onishi; Naoko Saito; Geum Sook Do; Sun Hee Lee; et al. (Plant Cell Reports, 2012)

Regulation of voltage-gated sodium current by endogenous Src family kinases in cochlear spiral ganglion neurons in culture - Shuang Feng; Melissa Pflueger; Shuang-Xiu Lin; Bradley R. Groveman; Jiping Su; Xian-Min Yu (Pflügers Archiv - European Journal of Physiology, 2012)

Persistent sodium current and Na+/H+ exchange contributes to the augmentation of the reverse Na+/Ca2+ exchange during hypoxia or acute ischemia in ventricular myocytes - Qiong Tang; Jihua Ma; Peihua Zhang; Wei Wan; Linghao Kong; Lin Wu (Pflügers Archiv - European Journal of Physiology, 2012)

Modeling and assessment of bridge structure for seismic hazard prevention - Jeng-Wen Lin; Cheng-Wu Chen; Shang-Heng Chung (Natural Hazards, 2012)

Mutation of the Nrf2 gene in non-small cell lung cancer - Yi Hu; Yanfang Ju; Dongmei Lin; Zhikuan Wang; Yurong Huang; Sujie Zhang; Chao Wu; Shunchang Jiao (Molecular Biology Reports, 2012)

Effects of isoflurane exposure during pregnancy on postnatal memory and learning in offspring rats - Fei-juan Kong; Yu-wen Tang; Ai-fei Lou; Hong Chen; Lin-hao Xu; Xiao-ming Zhang; Hui-shun Lu (Molecular Biology Reports, 2012)

Apolipoprotein A-I mimetic peptide D-4F promotes human endothelial progenitor cell proliferation, migration, adhesion though eNOS/NO pathway - Zhengang Zhang; Jianhua Qun; Chunmei Cao; Jun Wang; Wei Li; Yong Wu; Lin Du; Pei Zhao; Kaizheng Gong (Molecular Biology Reports, 2012)

TFF3 mediated induction of VEGF via hypoxia in human gastric cancer SGC-7901 cells - Bayasi Guleng; Jia Han; Jin-Qiu Yang; Qing-Wen Huang; Jian-Kun Huang; Xiao-Ning Yang; Jing-Jing Liu; Jian-Lin Ren (Molecular Biology Reports, 2012)

Analysis of Na+/Ca2+ exchanger (NCX) function and current in murine cardiac myocytes during heart failure - Lin Xu; Jing Chen; Xu-Yong Li; Shan Ren; Cong-Xin Huang; Gang Wu; Xiao-Yan Li; Xue-Jun Jiang (Molecular Biology Reports, 2012)

The expression level of Rosa Terminal Flower 1 (RTFL1) is related with recurrent flowering in roses - Li-Na Wang; Yun-Feng Liu; Yu-Man Zhang; Rong-Xiang Fang; Qing-Lin Liu (Molecular Biology Reports, 2012)

Proteomic analysis of peritrophic membrane (PM) from the midgut of fifth-instar larvae, Bombyx mori - Xiaolong Hu; Lin Chen; Xingwei Xiang; Rui Yang; Shaofang Yu; Xiaofeng Wu (Molecular Biology Reports, 2012)

Identification and characterization of a LEA family gene CarLEA4 from chickpea (Cicer arietinum L.) - Hanyan Gu; Yuying Jia; Xiansheng Wang; Quanjia Chen; Shubing Shi; Lin Ma; Jusong Zhang; Hua Zhang; Hao Ma (Molecular Biology Reports, 2012)

Determination of the complete mitochondrial DNA sequence of Octopus minor - Rubin Cheng; Xiaodong Zheng; Xiangzhi Lin; Jianmin Yang; Qi Li (Molecular Biology Reports, 2012)

Characterization, and expression profile of a phenylalanine ammonia lyase gene from Jatropha curcas L. - Jihai Gao; Shuwen Zhang; Feng Cai; Xiaojiang Zheng; Na Lin; Xiaobo Qin; Yangchao Ou; Xiaoping Gu; Xihong Zhu; Ying Xu; Fang Chen (Molecular Biology Reports, 2012)

Deletion of Siah-interacting protein gene in Drosophila causes cardiomyopathy - Michelle E. Casad; Lin Yu; Joseph P. Daniels; Matthew J. Wolf; Howard A. Rockman (Molecular Genetics and Genomics, 2012)

Genome-wide analysis of Aux/IAA gene family in Solanaceae species using tomato as a model - Jian Wu; Zhen Peng; Songyu Liu; Yanjun He; Lin Cheng; Fuling Kong; Jie Wang; Gang Lu (Molecular Genetics and Genomics, 2012)

Determination of organophosphorus pesticide residues in vegetables by an enzyme inhibition method using α-naphthyl acetate esterase extracted from wheat flour - Jun-liang Wang; Qing Xia; An-ping Zhang; Xiao-yan Hu; Chun-mian Lin (Journal of Zhejiang University-SCIENCE B, 2012)

Alleviative effect of quercetin on germ cells intoxicated by 3-methyl-4-nitrophenol from diesel exhaust particles - Tong-liang Bu; Yu-dong Jia; Jin-xing Lin; Yu-ling Mi; Cai-qiao Zhang (Journal of Zhejiang University-SCIENCE B, 2012)

Spermidine affects the transcriptome responses to high temperature stress in ripening tomato fruit - Lin Cheng; Rong-rong Sun; Fei-yan Wang; Zhen Peng; Fu-ling Kong; Jian Wu; Jia-shu Cao; Gang Lu (Journal of Zhejiang University-SCIENCE B, 2012)

SIRT1 is required for long-term growth of human mesenchymal stem cells - Hong-Feng Yuan; Chao Zhai; Xin-Long Yan; Dan-Dan Zhao; Jing-Xue Wang; Quan Zeng; Lin Chen; Xue Nan; Li-Juan He; Si-Ting Li; Wen Yue; Xue-Tao Pei (Journal of Molecular Medicine, 2012)

Expression patterns of ADAMs in the developing chicken lens - Xin Yan; Juntang Lin; Arndt Rolfs; Jiankai Luo (Journal of Molecular Histology, 2012)

Blockade of acid-sensing ion channels protects articular chondrocytes from acid-induced apoptotic injury - Wei Hu; Fei-Hu Chen; Feng-Lai Yuan; Teng-Yue Zhang; Fan-Rong Wu; Chao Rong; Sheng Jiang; Jie Tang; Cheng-Cheng Zhang; Mei-Ying Lin (Inflammation Research, 2012)

Growth and union acclimation process of sweet pepper grafted by a tubing-grafting robotic system - Yung-Chiung Chang; Suming Chen; Yi-Chich Chiu; Lian-Hsiung Lin; Yu-Sen Chang (Horticulture, Environment, and Biotechnology, 2012)

Construction and characterization of a full-length cDNA library and identification of genes involved in salinity stress in wild eggplant (Solanum torvum Swartz) - Gang Chen; Hua Wang; Jun-Yi Gai; Yue-Lin Zhu; Li-Fei Yang; Qian-Qian Liu; Gong-Chen Zhang; Guo-Hu Chen (Horticulture, Environment, and Biotechnology, 2012)

Acute effects of plyometric jumping and intermittent running on serum bone markers in young males - Che-Fu Lin; Tsang-hai Huang; Kuo-Cheng Tu; Linda L. Lin; Yi-Hsuan Tu; Rong-Sen Yang (European Journal of Applied Physiology, 2012)

Determination of critical power in trained rowers using a three-minute all-out rowing test - Ching-Feng Cheng; Yi-Shan Yang; Hui-Mei Lin; Chia-Lun Lee; Chun-Yi Wang (European Journal of Applied Physiology, 2012)

Chemical forms and ecological risk of arsenic in the sediment of the Daliao River System in China - Shiliang Wang; Ping Wang; Bin Men; Chunye Lin; Mengchang He (Environmental Monitoring and Assessment, 2012)

Characterizations of volatile organic compounds during high ozone episodes in Beijing, China - An Jun-lin; Wang Yue-si; Wu Fang-kun; Zhu Bin (Environmental Monitoring and Assessment, 2012)

Analyses of gene expression and physiological changes in Microcystis aeruginosa reveal the phytotoxicities of three environmental pollutants - Haifeng Qian; Xiangjie Pan; Jun Chen; Dongming Zhou; Zuoguo Chen; Lin Zhang; Zhengwei Fu (Ecotoxicology, 2012)

Physiological response of Cu and Cu mine tailing remediation of Paulownia fortunei (Seem) Hemsl - Zao-Fa Jiang; Su-Zhen Huang; Yu-Lin Han; Jiu-Zhou Zhao; Jia-Jia Fu (Ecotoxicology, 2012)

Changes of Sodium Iodide Symporter Regulated by IGF-I and TGF-β1 in Mammary Gland Cells from Lactating Mice at Different Iodine Levels - Xue Yu; Hongmei Shen; Lixiang Liu; Lin Lin; Meili Gao; Shinan Wang (Biological Trace Element Research, 2012)

Characteristics and Kinetics of Iron Releasefrom the Ferritin under the EGCG reduction - Xuetao Ji; Lin Huang; Qing Lin; Heqing Huang (Biological Trace Element Research, 2012)

Evaluation of DNA fragments covering the entire genome of a monopartite begomovirus for induction of viral resistance in transgenic plants via gene silencing - Ching-Yi Lin; Wen-Shi Tsai; Hsin-Mei Ku; Fuh-Jyh Jan (Transgenic Research, 2012)

Experiments on channel evolution caused by check-dam failure - Wen-Hsiao Tseng; Hsiao-Wen Wang; Shih-Chieh Chou; Yu-Lin Kao; Chjeng-Lun Shieh (Journal of Mountain Science, 2012)

The combined influence of background climate and urbanization on the regional warming in Southeast China - Peng Si; Yu Ren; Dongpo Liang; Bingwen Lin (Journal of Geographical Sciences, 2012)

Research on the distribution of major metal elements in the typical landslide soil of the Three Gorges Reservoir area - Luwen Liu; Wei Xiang; Zhaoxiang Lin; Linmei Liu; Jinquan Wu (Journal of Earth Science, 2012)

Sucrose treatment alters floral induction and development in vitro in gloxinia - Ming-Zhe Zhang; Li-Ling Wang; Dan Ye; Xi Chen; Zhi-Yi Wu; Xiao-Jia Lin; Wu-Jian Chen; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (In Vitro Cellular & Developmental Biology - Plant, 2012)

Multiple reference consistency check for LAAS: a novel position domain approach - Liang Li; Mohammed Quddus; Stephen Ison; Lin Zhao (GPS Solutions, 2012)

Study of phenol biodegradation using Bacillus amyloliquefaciens strain WJDB-1 immobilized in alginate–chitosan–alginate (ACA) microcapsules by electrochemical method - Daban Lu; Yan Zhang; Shiquan Niu; Letao Wang; Shaoxiong Lin; Chunming Wang; Weichun Ye; Chunlei Yan (Biodegradation, 2012)

Autographa californica multiple nucleopolyhedrovirus odv-e25 (Ac94) is required for budded virus infectivity and occlusion-derived virus formation - Lin Chen; Xiaolong Hu; Xingwei Xiang; Shaofang Yu; Rui Yang; Xiaofeng Wu (Archives of Virology, 2012)

Transcriptional analysis and functional characterization of XCC1294 gene encoding a GGDEF domain protein in Xanthomonas campestris pv. campestris - Yi-Min Hsiao; Wan-Ling Song; Chao-Tsai Liao; I-Hsuan Lin; Mei-Ying Pan; Ching-Fen Lin (Archives of Microbiology, 2012)

Preferential involvement of mitochondria in Toll-like receptor 3 agonist-induced neuroblastoma cell apoptosis, but not in inhibition of cell growth - Jiin-Haur Chuang; Tsu-Kung Lin; Ming-Hong Tai; Chia-Wei Liou; Sheng-Teng Huang; Chia-Ling Wu; Hung-Yi Lin; Pei-Wen Wang (Apoptosis, 2012)

Overexpression of microRNA-378 attenuates ischemia-induced apoptosis by inhibiting caspase-3 expression in cardiac myocytes - Ji Fang; Xiao-Wei Song; Jing Tian; Hu-Yan Chen; Dong-Feng Li; Jian-Fei Wang; An-Jing Ren; Wen-Jun Yuan; Li Lin (Apoptosis, 2012)

Food partitioning among three sympatric odontocetes ( Grampus griseus , Lagenodelphis hosei , and Stenella attenuata ) - Ming‐Chih Wang; Kwang‐Tsao Shao; Shiang‐Lin Huang; Lien‐Siang Chou (Marine Mammal Science, 2012)
Food is one of the most important dimensions of resource partitioning for species coexistence. In this study, we investigated the dietary composition and foraging habits of three sympatric odontocetes in order to identify their levels of food niche overlap and ecological separation. Stomach content analysis was performed on samples collected from carcasses confiscated by police or entangled in gill nets from 1994 to 2001, including 27 Risso's dolphins (GG) ( Grampus griseus ), 27 Fraser's dolphins (LH) ( Lagenodelphis hosei ), and 45 pantropical spotted dolphins (SA) ( Stenella attenuata ). GG consumed only cephalopods, with Enoploteuthis chunii accounting for 90.5% of total prey consumed, LH fed on mesopelagic fishes and cephalopods, dominated by hatchetfish, Polyipnus stereope (50.2%), and SA ate both mesopelagic and epipelagic preys, primarily fishes of Myctophum asperum (20.3%) and squids of E. chunii (25.8%). Among the three odontocetes, GG had the narrowest dietary niche width, while SA had the widest width. Both the niche overlap index and the analysis of similarities (ANOSIM) showed significant diet differentiation among these three dolphin species. The depth distribution of their principal prey items further suggests that LH feeds in the deepest waters while SA utilizes prey resources near surface.

Microbial methane cycling in a terrestrial mud volcano in eastern Taiwan - Yung‐Hsin Chang; Ting‐Wen Cheng; Wen‐Jing Lai; Wen‐Yu Tsai; Chih‐Hsien Sun; Li‐Hung Lin; Pei‐Ling Wang (Environmental Microbiology, 2012)
Summary Microbial communities responsible for methane cycling in mud volcanoes onshore are poorly characterized. This study analysed bubbling fluids and cored sediments retrieved from a mud volcano in eastern Taiwan. The pore water profiles revealed that methane concentrations generally increased with depth and changed dramatically at different depth intervals at different sites. The methane concentrations were inversely correlated with Fe 2+ /Mn 2+ concentrations and δ 13 C values of methane, marking iron/manganese‐methane transition zones in the sediment cores. Archaeal communities were dominated by ANME‐2a members and methylotrophic methanogens, whereas bacterial communities consisted primarily of Proteobacteria, Firmicutes and Bacteroidetes . The 16S rRNA gene copy numbers of ANME‐2a and Desulfuromonas / Pelobacter populations varied by two to three orders of magnitude along the profile and exhibited a pattern comparable with those of Fe 2+ and δ 13 C values of methane. These lines of evidence suggest a coupling between anaerobic methanotrophy and metal reduction in the metal‐methane transition zones under sulfate‐deficient conditions, a metabolic scheme contrasting with that observed in marine cold seeps. Anaerobic methanotrophs proliferate by removing methane produced from in situ methanogenesis and originating from the deep source. Methane finally emitted into the atmosphere is quantitatively and isotopically altered by various microbial processes compartmentalized at different depth intervals.

Comparison of remotely sensed and meteorological data-derived drought indices in mid-eastern China - Lei Zhou; Jie Zhang; Jianjun Wu; Lin Zhao; Ming Liu; Aifeng Lü; Zhitao Wu (International Journal of Remote Sensing, 2012)

Rice heading date retrieval based on multi-temporal MODIS data and polynomial fitting - Hongshuo Wang; Jinsong Chen; Zhifeng Wu; Hui Lin (International Journal of Remote Sensing, 2012)

Three-level frame and RD-schematic algorithm for automatic detection of individual trees from MLS point clouds - Yi Lin; Juha Hyyppä; Anttoni Jaakkola; Xiaowei Yu (International Journal of Remote Sensing, 2012)

LC determination of luteolin-7- O -β- D -glucoside and apigenin-7- O -β- D -glucoside in rat plasma after administration of Humulus scandens extract and its application to pharmacokinetic studies - Zaixing Chen; Xixiang Ying; Shu Meng; Xu Zhu; Hong Jiang; Qishen Cao; Lin Wang; Fanhao Meng (Natural Product Research, 2012)

Isolation, characterization and colonization of 1-aminocyclopropane-1-carboxylate deaminase-producing bacteria XG32 and DP24 - Mei-Xia Wang; Jia Liu; Shuang-lin Chen; Shu-Zhen Yan (World Journal of Microbiology and Biotechnology, 2012)

Oxygen Metabolism in Ischemic Stroke Using Magnetic Resonance Imaging - Hongyu An; Qingwei Liu; Yasheng Chen; Katie D. Vo; Andria L. Ford; Jin-Moo Lee; Weili Lin (Translational Stroke Research, 2012)

Iron Enhances the Neurotoxicity of Amyloid β - Lin Wang; Guohua Xi; Richard F. Keep; Ya Hua (Translational Stroke Research, 2012)

Different mechanisms of extinction of conditioned taste aversion are dependent on time intervals of extinction following conditioning - Pei-Yi Lin; Yi-Ya Fang; Su-Ping Wang; Mei-Yun Tai; Yuan-Feen Tsai (The Science of Nature, 2012)

Comparison of Intestinal Absorption and Disposition of Structurally Similar Bioactive Flavones in Radix Scutellariae - Chenrui Li; Li Zhang; Limin Zhou; Siu Kwan Wo; Ge Lin; Zhong Zuo (The AAPS Journal, 2012)

Quasi-stationary planetary wave-mean flow interactions in the Northern Hemisphere stratosphere and their responses to ENSO events - XiaoQing Lan; Wen Chen; Lin Wang (Science China Earth Sciences, 2012)

Role of calcineurin in the VTA in rats behaviorally sensitized to methamphetamine - Jun Wang; Li-Li Sun; Wei-Li Zhu; Yan Sun; Jian-Feng Liu; Lin Lu; Jie Shi (Psychopharmacology, 2012)

Availability of dopamine and serotonin transporters in opioid-dependent users—a two-isotope SPECT study - Tzung Lieh Yeh; Kao Chin Chen; Shih-Hsien Lin; I. Hui Lee; Po See Chen; Wei Jen Yao; Sheng-Yu Lee; Yen Kuang Yang; Ru-Band Lu; Mei-Hsiu Liao; Nan-Tsing Chiu (Psychopharmacology, 2012)

Unbiased genomic distribution of genes related to cell morphogenesis in cotton by chromosome mapping - Chuanxiang Liu; Zhongxu Lin; Xianlong Zhang (Plant Cell, Tissue and Organ Culture (PCTOC), 2012)

Purification of the photosynthetic reaction center from Heliobacterium modesticaldum - Iosifina Sarrou; Zahid Khan; John Cowgill; Su Lin; Daniel Brune; Steven Romberger; John H. Golbeck; Kevin E. Redding (Photosynthesis Research, 2012)

Excitation energy transfer and trapping dynamics in the core complex of the filamentous photosynthetic bacterium Roseiflexus castenholzii - Yueyong Xin; Jie Pan; Aaron M. Collins; Su Lin; Robert E. Blankenship (Photosynthesis Research, 2012)

Improving the Chemical Stability of Amorphous Solid Dispersion with Cocrystal Technique by Hot Melt Extrusion - Xu Liu; Ming Lu; Zhefei Guo; Lin Huang; Xin Feng; Chuanbin Wu (Pharmaceutical Research, 2012)

The Use of Nano Polymeric Self-Assemblies Based on Novel Amphiphilic Polymers for Oral Hydrophobic Drug Delivery - Hoskins Clare; Paul Kong Thoo Lin; Laurence Tetley; Woei Ping Cheng (Pharmaceutical Research, 2012)

Neuroprotection by marine-derived compound, 11-dehydrosinulariolide, in an in vitro Parkinson’s model: a promising candidate for the treatment of Parkinson’s disease - Wu-Fu Chen; Chiranjib Chakraborty; Chun-Sung Sung; Chien-Wei Feng; Yen-Hsuan Jean; Yen-You Lin; Han-Chun Hung; Tzu-Yi Huang; Shi-Ying Huang; Thung-Ming Su; Ping-Jyun Sung; Jyh-Horng Sheu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Regional economic impact analysis of earthquakes in northern Taiwan and its implications for disaster reduction policies - H. C. Lin; Y. L. Kuo; D. Shaw; M. C. Chang; T. M. Kao (Natural Hazards, 2012)

Genotyping and Antifungal Drug Susceptibility of Trichosporon asahii Isolated from Chinese Patients - Zhikuan Xia; Rongya Yang; Wenling Wang; Lin Cong (Mycopathologia, 2012)

Association between HFE polymorphisms and susceptibility to Alzheimer’s disease: a meta-analysis of 22 studies including 4,365 cases and 8,652 controls - Min Lin; Lin Zhao; Jin Fan; Xue-Gan Lian; Jian-xin Ye; Lei Wu; Hang Lin (Molecular Biology Reports, 2012)

Intron retention and 3′-UTR analysis of Arabidopsis Dicer-like 2 transcripts - Qiongji He; Jiejun Peng; Fei Yan; Lin Lin; Yuwen Lu; Hongying Zheng; Hairu Chen; Jianping Chen (Molecular Biology Reports, 2012)

Inhibitor of DNA-binding-1/inhibitor of differentiation-1 (ID-1) is implicated in various aspects of gastric cancer cell biology - Wei Li; Chun-Hua Zhang; Yi-Lin Hong; Jun Li; Yong-Mei Hu; Cui-Fen Zhao (Molecular Biology Reports, 2012)

Chemicobiological effects of herbicide MCPA-Na on plasma proteins - Hua-xin Zhang; Lin Liu (Molecular Biology Reports, 2012)

Molecular cloning and characterization of an F-box family gene CarF-box1 from chickpea (Cicer arietinum L.) - Yuying Jia; Hanyan Gu; Xiansheng Wang; Quanjia Chen; Shubing Shi; Jusong Zhang; Lin Ma; Hua Zhang; Hao Ma (Molecular Biology Reports, 2012)

Distribution and expression characteristics of triterpenoids and OSC genes in white birch (Betula platyphylla suk.) - Jing Yin; Chun-Lin Ren; Ya-Guang Zhan; Chun-Xiao Li; Jia-Lei Xiao; Wei Qiu; Xin-Yu Li; Hong-Mei Peng (Molecular Biology Reports, 2012)

Characterization of the first specific jasmonate biosynthetic pathway gene allene oxide synthase from Artemisia annua - Xu Lu; Fangyuan Zhang; Weimin Jiang; Xiuyan Lin; Yunfei Chen; Qian Shen; Tao Wang; Shaoyan Wu; Xiaofen Sun; Kexuan Tang (Molecular Biology Reports, 2012)

MicroRNA- 1 represses Cx43 expression in viral myocarditis - Hong-Fei Xu; Yu-Jie Ding; Yi-Wen Shen; Ai-Min Xue; Hong-Mei Xu; Cheng-Liang Luo; Bei-Xu Li; Yue-Lin Liu; Zi-Qin Zhao (Molecular and Cellular Biochemistry, 2012)

Arginine decreases peroxisome proliferator-activated receptor-γ activity via c-Jun - Kechen Ban; Zhanglong Peng; Wei Lin; Rosemary A. Kozar (Molecular and Cellular Biochemistry, 2012)

Wear analysis of chamfered elongated acetabular cup liners - Hsiao-Che Lin; Tzuo-Liang Luo; Jian-Horng Chen (Medical & Biological Engineering & Computing, 2012)

Aesthetascs in Lysmata spp. shrimp: sexual dimorphism and relationship with social environments - Jing Zhu; Dong Zhang; Junda Lin; Michael S. Grace (Marine Biology, 2012)

NAD(P)H oxidase inhibiting with apocynin improved vascular reactivity in tail-suspended hindlimb unweighting rat - Ran Zhang; Hai-hong Ran; Jin Ma; Yun-gang Bai; Le-jian Lin (Journal of Physiology and Biochemistry, 2012)

[11C]DAC-PET for Noninvasively Monitoring Neuroinflammation and Immunosuppressive Therapy Efficacy in Rat Experimental Autoimmune Encephalomyelitis Model - Lin Xie; Tomoteru Yamasaki; Naotsugu Ichimaru; Joji Yui; Kazunori Kawamura; Katsushi Kumata; Akiko Hatori; Norio Nonomura; Ming-Rong Zhang; Xiao-Kang Li; Shiro Takahara (Journal of Neuroimmune Pharmacology, 2012)

Relationships between common irrigation application uniformity indicators - Lin Zhang; Gary P. Merkley (Irrigation Science, 2012)

Vancomycin-loaded nano-hydroxyapatite pellets to treat MRSA-induced chronic osteomyelitis with bone defect in rabbits - Ji-Le Jiang; Yun-Fei Li; Tao-Lin Fang; Jian Zhou; Xi-Lei Li; Yi-Chao Wang; Jian Dong (Inflammation Research, 2012)

Developmental incompatibility of human parthenogenetic embryonic stem cells in mouse blastocysts - Lili Du; Xiaoming Xu; Xin Duan; Guangxiu Lu; Ge Lin (In Vitro Cellular & Developmental Biology - Animal, 2012)

A study of genetic variations, population size, and population dynamics of the catadromous Japanese eel Anguilla japonica (Pisces) in northern Taiwan - Mei-Chen Tseng; Hsiao-Wei Kao; Yin-Huei Hung; Tung-Lin Lee (Hydrobiologia, 2012)

Associations between common variants in GC and DHCR7/NADSYN1 and vitamin D concentration in Chinese Hans - Ling Lu; Hongguang Sheng; Huaixing Li; Wei Gan; Chen Liu; Jingwen Zhu; Ruth J. F. Loos; Xu Lin (Human Genetics, 2012)

Functional analysis of Waardenburg syndrome-associated PAX3 and SOX10 mutations: report of a dominant-negative SOX10 mutation in Waardenburg syndrome type II - Hua Zhang; Hongsheng Chen; Hunjin Luo; Jing An; Lin Sun; Lingyun Mei; Chufeng He; Lu Jiang; Wen Jiang; Kun Xia; Jia-Da Li; Yong Feng (Human Genetics, 2012)

Genome-wide association study identifies HMGN3 locus for spine bone size variation in Chinese - Shu-Feng Lei; Hui Shen; Tie-Lin Yang; Yan Guo; Shan-Shan Dong; Xiang-Hong Xu; Fei-Yan Deng; Qing Tian; Yong-Jun Liu; Yao-Zhong Liu; Jian Li; Hong-Wen Deng (Human Genetics, 2012)

Differential gene expression in incompatible interaction between turnip mosaic virus and non-heading Chinese cabbage - Hai-Tao Peng; Li Wang; Ying Li; Yan-Xiao Li; Wei Guan; Yang Yang; Xiao-Hai Xu; Xi-Lin Hou (European Journal of Plant Pathology, 2012)

Seedling recruitment patterns in a 20 ha subtropical forest plot: hints for niche-based processes and negative density dependence - Yue Bin; Guojun Lin; Buhang Li; Linfang Wu; Yong Shen; Wanhui Ye (European Journal of Forest Research, 2012)

Mapping of QTLs associated with important agronomic traits using three populations derived from a super hybrid rice Xieyou9308 - Yongshu Liang; Xiaodeng Zhan; Zhiqiang Gao; Zechuan Lin; Zhanlie Yang; Yinxin Zhang; Xihong Shen; Liyong Cao; Shihua Cheng (Euphytica, 2012)

Retrieval of total suspended matter (TSM) and chlorophyll-a (Chl-a) concentration from remote-sensing data for drinking water resources - Kaishan Song; Lin Li; Zongming Wang; Dianwei Liu; Bai Zhang; Jingping Xu; Jia Du; Linhai Li; Shuai Li; Yuandong Wang (Environmental Monitoring and Assessment, 2012)

Linking Carbon Saturation Concepts to Nitrogen Saturation and Retention - Michael J. Castellano; Jason P. Kaye; Henry Lin; John P. Schmidt (Ecosystems, 2012)

Erratum to: Hyperhomocysteinemia and Related Genetic Polymorphisms Correlate with Ulcerative Colitis in Chinese Han population in Central China - Yi Jiang; Xuanping Xia; Wenxing Wang; Limiao Lin; Changlong Xu; Zhenzai Cai; Bo Zheng; Jihua Pei; Sujian Shen; Bing Xia (Cell Biochemistry and Biophysics, 2012)

Anti-tumor Function of Double-promoter Regulated Adenovirus Carrying SEA Gene, in the Treatment of Bladder Cancer - Jianpeng Hu; Xujun Xuan; Conghui Han; Lin Hao; Peiying Zhang; Meng Chen; Houguang He; Tao Fan; Binzheng Dong (Cell Biochemistry and Biophysics, 2012)

Seasonal Variation and Health Risk Assessment of Polycyclic Aromatic Hydrocarbons in Miaoli City, Taiwan - C. C. Wu; T. S. Lin; T. T. Yang; H. W. Hsu; C. L. Chang; C. H. Huang; W. Y. Lin (Bulletin of Environmental Contamination and Toxicology, 2012)

Influence of Selenium on Hepatic Mitochondrial Antioxidant Capacity in Ducklings Intoxicated with Aflatoxin B1 - Dayou Shi; Shining Guo; Shenquan Liao; Rongsheng Su; Jiaqiang Pan; Yuanchao Lin; Zhaoxin Tang (Biological Trace Element Research, 2012)

A spatial aggregation index for effective fallow decision in paddy irrigation demand planning - Ming-Daw Su; Mei-Chun Lin; Chun-Hung Lin; Shih-Fu Wang; Tzai-Hung Wen; Hsin-I Hsieh (Paddy and Water Environment, 2012)

Non-classical MHC-Ι genes in chronic hepatitis B and hepatocellular carcinoma - Jian Zhang; Lelin Pan; Luyan Chen; Xiaowen Feng; Lin Zhou; Shusen Zheng (Immunogenetics, 2012)

Multiple cycles of glacier advance and retreat during the Nantuo (Marinoan) glacial termination in the Three Gorges area - Jun Hu; Jiasheng Wang; Hongren Chen; Zhou Wang; Lei Xie; Qi Lin (Frontiers of Earth Science, 2012)

A novel multiplex PCR assay for species identification in the Chinese Egret (Egretta eulophotes) and Little Egret (E. garzetta) - Xunhe Huang; Xiaoping Zhou; Qingxian Lin; Zhenni Peng; Wenzhen Fang; Xiaolin Chen (Conservation Genetics Resources, 2012)

Peptidergic Regulation of Expression of Genes Encoding Antioxidant and Anti-Inflammatory Proteins - V. Kh. Khavinson; N. S. Lin’kova; A. V. Dudkov; V. O. Polyakova; I. M. Kvetnoi (Bulletin of Experimental Biology and Medicine, 2012)

Neurogenesis of bone marrow-derived mesenchymal stem cells onto β-mercaptoethanol-loaded PLGA film - Gilson Khang; Hye Lin Kim; Minsung Hong; Dongwon Lee (Cell and Tissue Research, 2012)

In vitro selection of resistant mutant garlic lines by using crude pathogen culture filtrate of Sclerotium cepivorum - Lin-qing Zhang; Zhi-hui Cheng; Muhammad Azam Khan; Yan-li Zhou (Australasian Plant Pathology, 2012)

Complete genomic sequence analysis reveals a novel fabavirus infecting cucurbits in China - Shu-Wei Dong; Hai-Ying Xiang; Qiao-Xia Shang; Da-Wei Li; Jia-Lin Yu; Cheng-Gui Han (Archives of Virology, 2012)

Three-dimensional interpretation of sparse survey line MT data: Synthetic examples - Chang-Hong Lin; Han-Dong Tan; Qing Shu; Tuo Tong; Yu-Mei Zhang (Applied Geophysics, 2012)

PC-based artificial neural network inversion for airborne time-domain electromagnetic data - Kai-Guang Zhu; Ming-Yao Ma; Hong-Wei Che; Er-Wei Yang; Yan-Ju Ji; Sheng-Bao Yu; Jun Lin (Applied Geophysics, 2012)

Micromonospora haikouensis sp. nov., isolated from mangrove soil - Qing-yi Xie; Zhi Qu; Hai-peng Lin; Lei Li; Kui Hong (Antonie van Leeuwenhoek, 2012)

Strontium Ranelate Prevents Bone Loss in a Rat Model of Localized Muscle Paralysis - Zhi-Feng Sheng; Yu-Lin Ma; Dejun Tong; De-Yu Fang; Qing-Chun Liang; Li-Hong Liu; Jian Zhang; Er-Yuan Liao (Annals of Biomedical Engineering, 2012)

The Use of SU-8 Topographically Guided Microelectrode Array in Measuring Extracellular Field Potential Propagation - Jessica Ka-Yan Law; Chi-Kong Yeung; Lin Li; John Anthony Rudd; Sven Ingebrandt; Mansun Chan (Annals of Biomedical Engineering, 2012)

Spatial dependence of alveolar angiogenesis in post-pneumonectomy lung growth - Moritz A. Konerding; Barry C. Gibney; Jan P. Houdek; Kenji Chamoto; Maximilian Ackermann; Grace S. Lee; Miao Lin; Akira Tsuda; Steven J. Mentzer (Angiogenesis, 2012)

Global response to tropical diabatic heating variability in boreal winter - Xu Zhang; Hai Lin; Jing Jiang (Advances in Atmospheric Sciences, 2012)

The accumulation of pigment in fiber related to proanthocyanidins synthesis for brown cotton - Tingchun Li; Honghong Fan; Zhengpeng Li; Jun Wei; Yi Lin; Yongping Cai (Acta Physiologiae Plantarum, 2012)

Longitudinal patterns of spring-intermonsoon phytoplankton biomass, species compositions and size structure in the Bay of Bengal - Gang Li; Zhixin Ke; Qiang Lin; Guangyan Ni; Pingping Shen; Huaxue Liu; Jianqiang Yin; Kaizhi Li; Liangmin Huang; Yehui Tan (Acta Oceanologica Sinica, 2012)

Reconstructing the upper ocean thermal profiles using one-dimensional numerical model - Zhenhua Lin; Dongliang Zhao; Jinbao Song (Acta Oceanologica Sinica, 2012)

The proportions and variations of the light absorption coefficients of major ocean color components in the East China Sea - Hui Lei; Delu Pan; Yan Bai; Bangyi Tao; Jun Sun; Lin Zhang; Xuan Zhang (Acta Oceanologica Sinica, 2012)

Differential expression profiling of orange‐spotted grouper larvae, Epinephelus coioides (Hamilton), that survived a betanodavirus outbreak - M‐S Wu; C‐W Chen; C‐H Lin; C‐S Tzeng; C‐Y Chang (Journal of Fish Diseases, 2012)
Nervous necrosis virus (NNV), a piscine nodavirus, has caused serious viral nervous necrosis and viral encephalopathy and retinopathy in hatchery‐reared larvae and juveniles of a wide range of marine teleost species worldwide in the last two decades. Although the mortality of NNV‐infected larvae is nearly 100%, there are still some larvae that survive this catastrophe. To comprehensively understand the variations of these survivors at the molecular level, we collected orange‐spotted grouper larvae that survived an NNV outbreak in an indoor hatchery in southern Taiwan to study differential gene expression. Healthy larvae with high, medium and low levels of detected NNV were compared with morbid larvae using a 9600‐clone‐containing grouper larva cDNA microarray, and differential gene expression was further confirmed by a quantitative real‐time polymerase chain reaction. Significant variation exists in healthy larvae. The following genes were upregulated: adenylate kinase 1‐2, myosin binding protein H‐like, myosin light chain 2, myosin light chain 3, tropomyosin, fast/white muscle troponin T embryonic isoform, and parvalbumin 1 and 2 genes. The following genes were downregulated: apolipoprotein A‐I, trypsinogen, pyruvate kinase and astacin‐like metalloprotease. Moreover, immunoglobulin M heavy chain gene transcription was significantly higher in healthy larvae that had high virus levels, indicating that humoral immunity might protect organisms from viral infection. These results suggest that some non‐immune‐related genes may have played important roles in survival during the larval metamorphosis stage, after betanodavirus infection.

Germ cells and fertilization differences among Japanese flounder Paralichthys olivaceus , summer flounder Paralichthys dentatus and their first and second generations - J. Sui; D. Y. Ma; Q. H. Liu; S. H. Xu; Z. Z. Xiao; F. Lin; Y. S. Xiao; J. Li (Journal of Fish Biology, 2012)
The morphology of gametes and the fertilization biology of Japanese flounder Paralichthys olivaceus (Po), summer flounder Paralichthys dentatus (Pd) and their hybrids were examined. Multiple generations (two hybrids: Po♀× Pd♂ (F1) and Pd♀× Po♂; two backcrosses: F1♀× Po♂ and F1♀× Pd♂) were obtained by artificial insemination. Comparison of egg ultrastructure among Po, Pd and F1 showed the morphology of micropyle region and the distribution density of pores were species specific. There were c . 100–200 accessory openings around the micropyle in Po, but not in Pd and F1. The zona radiata thickness and number of parallel bands were similar between F1 and Po, which were different from Pd. Comparison of spermatozoa ultrastructure revealed a close relationship between Po and Pd. Cytologically, the six crosses obeyed normal fertilization and cleavage processes, and only one male pronucleus was observed in a fertilized egg, indicating a monospermic fertilization pattern. Analysis of the time distribution from fertilization to first cleavage revealed an obvious delay at pronucleus fusion in the Pd × Po cross. The delay might indicate some cytoplasmic‐nuclear incompatibility during the process of fertilization.

The role of microcystins in maintaining colonies of bloom‐forming Microcystis spp. - Nanqin Gan; Yan Xiao; Lin Zhu; Zhongxing Wu; Jin Liu; Chenlin Hu; Lirong Song (Environmental Microbiology, 2012)
Summary Microcystis is a cosmopolitan genus of cyanobacteria and occurs in many different forms. Large surface blooms of the cyanobacterium are well known in eutrophic lakes throughout the globe. We evaluated the role of microcystins (MCs) in promoting and maintaining bloom‐forming cell aggregates at environmentally relevant MC concentrations (0.25–10 µg l −1 ). MCs significantly enhanced Microcystis colony sizes. Colonial diameters in microcystin‐RR (MC‐RR)‐treated cultures (at 1 µg l −1 ) were significantly larger than control colonies, by factors of 1.5, 2.6 and 2.7 in Microcystis wesenbergii DC‐M1, M. ichthyoblabe TH‐M1 and Microcystis sp. FACHB1027 respectively. Depletion of extracellular MC concentrations caused Microcystis colony size to decrease, suggesting that released MCs are intimately involved in the maintenance of Microcystis colonial size. MC‐RR exposure did not influence Microcystis growth rate, but did significantly increase the production of extracellular polysaccharides (EPS). In addition, MC‐RR exposure appeared to trigger upregulation of certain parts of four polysaccharide biosynthesis‐related genes: capD , csaB , tagH and epsL . These results strongly indicate that induction of polysaccharides by MC‐RR was the major mechanism through which MCs enhanced colony formation in Microcystis spp. Cellular release of MCs, therefore, may play a key role in the persistence of algal colonies and the dominance of Microcystis.

Interactions between mangroves and exotic Spartina in an anthropogenically disturbed estuary in southern China - Yihui Zhang; Guanmin Huang; Wenqing Wang; Luzhen Chen; Guanghui Lin (Ecology, 2012)
Cordgrass ( Spartina alterniflora ) was introduced to China in 1979 from the United States for reducing coastal erosion. It grows vigorously in China and has spread over much of the Chinese coast, from Leizhou Peninsula to Liaoning, a range of more than 19 degrees of latitude. On the southern coast of China, S. alterniflora has invaded mangrove‐dominated habitats during the last two decades, but little is known about interactions between native mangroves and invasive S. alterniflora . We studied the distribution and competitive interactions between native mangroves and S. alterniflora in the Zhangjiang Estuary at four tidal sites along a salinity gradient: oligohaline upstream, mesohaline, polyhaline, and euhaline downstream. S. alterniflora occurred at all four sites, and several mangrove species occurred at all but the downstream euhaline site. S. alterniflora has invaded the estuary widely and has spread to the lower tidal margins of mangroves. It has not invaded mangrove areas with a closed canopy but has established in the mangrove zone where the canopy was opened by human disturbance. Ramets of S. alterniflora transplanted into the understory of mangrove stands with closed canopies died within 10 weeks, but 37.5% survived and grew well on open mud flats. S. alterniflora had virtually no competitive effect on mangrove seedlings planted at the upstream oligohaline site. However, S. alterniflora competitively reduced biomass of mangrove seedlings to 33% over a period of 14 weeks at the mesohaline and polyhaline sites where human disturbance has opened the mangrove canopy. In contrast, S. alterniflora marginally facilitated growth and survival of experimental seedlings at the downstream euhaline site. In China, mangroves occur along the coastline south of Whenzhou, but they have been severely disturbed and removed widely, mainly by mariculture activities. Natural vegetation patterns and our experimental results suggest that, without intervention, S. alterniflora could gradually replace these mangroves in mid‐salinity regions of Chinese estuaries.

The genetic association of adakites and Cu–Au ore deposits': a reply - Weidong Sun; Mingxing Ling; Xing Ding; Sun-Lin Chung; Xiao-Yong Yang; Weiming Fan (International Geology Review, 2012)

Latitudinal variability (6°S–20°N) of early summer phytoplankton species compositions and size-fractioned productivity from Java Sea to South China Sea - Gang Li; Liangmin Huang; Huaxue Liu; Zhixin Ke; Qiang Lin; Guangyan Ni; Jianqiang Yin; Kaizhi Li; Xingyu Song; Pingping Shen; Yehui Tan (Marine Biology Research, 2012)

Improved synthesis of 2′-deoxyadenosine and 5-methyluridine by Escherichia coli using an auto-induction system - Juan Xiong; Wenquan Zhang; Jingtan Su; Junlong Shangguan; Yin Lin; Yang Yang; Rongqing Zhang; Liping Xie; Hongzhong Wang (World Journal of Microbiology and Biotechnology, 2012)

An effective and simplified scale-up strategy for acarbose fermentation based on the carbon source control - Kun-tai Li; Sai-jin Wie; Lin Huang; Xin Cheng (World Journal of Microbiology and Biotechnology, 2012)

Effect of pH on the Analysis of 2-MIB and Geosmin in Water - Wen-Hsing Hsieh; Wei-Nung Hung; Gen-Shuh Wang; Shu-Ting Hsieh; Tsair-Fuh Lin (Water, Air, & Soil Pollution, 2012)

Climate Change Effects on Hydrology and Ecology of Wetlands in the Mid-Atlantic Highlands - Jonathan L. Pitchford; Chenjie Wu; LianShin Lin; J. Todd Petty; Richard Thomas; Walter E. Veselka; Danny Welsch; Nicolas Zegre; James T. Anderson (Wetlands, 2012)

Analysis of quantitative disease resistance to southern leaf blight and of multiple disease resistance in maize, using near-isogenic lines - Araby R. Belcher; John C. Zwonitzer; Jose Santa Cruz; Mathew D. Krakowsky; Chia-Lin Chung; Rebecca Nelson; Consuelo Arellano; Peter J. Balint-Kurti (Theoretical and Applied Genetics, 2012)

Identification of the novel recessive gene pi55(t) conferring resistance to Magnaporthe oryzae - XiuYing He; XinQiong Liu; Li Wang; Ling Wang; Fei Lin; YongSheng Cheng; ZhaoMing Chen; YaoPing Liao; QingHua Pan (Science China Life Sciences, 2012)

Viral suppression of RNA silencing - Lin Jiang; ChunHong Wei; Yi Li (Science China Life Sciences, 2012)

The vertical structure and seasonal changes of atmosphere ozone and temperature at Zhongshan Station over East Antarctica - LinGen Bian; Zhong Lin; DongQi Zhang; XiangDong Zheng; LongHua Lu (Science China Earth Sciences, 2012)

Molecular Cloning, Sequence Analysis, and Expression of the Polygalacturonase-inhibiting Protein (PGIP) Gene in Mulberry - Dongqing Hu; Ruiqiang Dai; Yuhua Wang; Yinghua Zhang; Zhaoyue Liu; Rongjun Fang; Weiguo Zhao; Long Li; Qiang Lin; Liu Li (Plant Molecular Biology Reporter, 2012)

Dew water isotopic ratios and their relationships to ecosystem water pools and fluxes in a cropland and a grassland in China - Xue-Fa Wen; Xuhui Lee; Xiao-Min Sun; Jian-Lin Wang; Zhong-Min Hu; Sheng-Gong Li; Gui-Rui Yu (Oecologia, 2012)

A numerical study of the circulation and monthly-to-seasonal variability in the Caribbean Sea: the role of Caribbean eddies - Yuehua Lin; Jinyu Sheng; Richard J. Greatbatch (Ocean Dynamics, 2012)

Kalman filter decision systems for debris flow hazard assessment - Jeng-Wen Lin; Cheng-Wu Chen; Cheng-Yi Peng (Natural Hazards, 2012)

Induced bone marrow mesenchymal stem cells improve cardiac performance of infarcted rat hearts - Xiao-Hong Li; Yong-Heng Fu; Qiu-Xiong Lin; Zai-Yi Liu; Zhi-Xin Shan; Chun-Yu Deng; Jie-Ning Zhu; Min Yang; Shu-Guang Lin; Yangxin Li; Xi-Yong Yu (Molecular Biology Reports, 2012)

The expression of HIF-1α in primary hepatocellular carcinoma and its correlation with radiotherapy response and clinical outcome - Zuo-Lin Xiang; Zhao-Chong Zeng; Jia Fan; Zhao-You Tang; Jian He; Hai-Ying Zeng; Joe Y. Chang (Molecular Biology Reports, 2012)

Quantitative assessment of the effect of ABCA1 R219K polymorphism on the risk of coronary heart disease - Yang Li; Kefu Tang; Kejun Zhou; Zhiyun Wei; Zhen Zeng; Lin He; Chunling Wan (Molecular Biology Reports, 2012)

Plk1-mediated phosphorylation of UAP56 regulates the stability of UAP56 - Fuyin Xiong; Yanli Lin; Zhengbin Han; Gengshou Shi; Liyuan Tian; Xiaojie Wu; Qiangcheng Zeng; Yanrong Zhou; Jixian Deng; Hongxing Chen (Molecular Biology Reports, 2012)

Molecular cloning and its expression of trachealess gene (As-trh) during development in brine shrimp, Artemia sinica - Jia-Qing Wang; Lin Hou; Nan Yi; Riu-Feng Zhang; Xiang-Yang Zou; Qin Xiao; Ran Guo (Molecular Biology Reports, 2012)

Association of SERPINE2 gene with the risk of chronic obstructive pulmonary disease and spirometric phenotypes in northern Han Chinese population - Li An; Ting Yang; Yongbiao Zhang; Yingxiang Lin; Hong Zhang; Xia Jiao; Lin Hua; Huaping Dai; Chen Wang (Molecular Biology Reports, 2012)

Penehyclidine hydrochloride attenuates LPS-induced iNOS production by inhibiting p38 MAPK activation in endothelial cells - Jia Zhan; Zong-ze Zhang; Chang Chen; Kai Chen; Yan-lin Wang (Molecular Biology Reports, 2012)

FTH1 binds to Daxx and inhibits Daxx-mediated cell apoptosis - Fang Liu; Zhi-Yin Du; Jun-Lin He; Xue-Qing Liu; Qiu-Bo Yu; Ying-Xiong Wang (Molecular Biology Reports, 2012)

Two species of Lirula on Abies from Yunnan, Southwest China - Li Fan; Ying-Ren Lin; Shuang Wang; Cheng-Lin Hou (Mycological Progress, 2012)

VPA inhibits breast cancer cell migration by specifically targeting HDAC2 and down-regulating Survivin - Lei Zhang; Guiying Wang; Lin Wang; Chenlin Song; Ye Leng; Xinhua Wang; Jiuhong Kang (Molecular and Cellular Biochemistry, 2012)

Norcantharidin, a protective therapeutic agent in renal tubulointerstitial fibrosis - Ying Li; Yan Ge; Fu You Liu; You Ming Peng; Lin Sun; Jun Li; Qiong Chen; Yan Sun; Kun Ye (Molecular and Cellular Biochemistry, 2012)

Induction of Mitogynogenetic Diploids and Identification of WW Super-female Using Sex-Specific SSR Markers in Half-Smooth Tongue Sole (Cynoglossus semilaevis) - Song-Lin Chen; Xiang-Shan Ji; Chang-Wei Shao; Wen-Long Li; Jing-Feng Yang; Zuo Liang; Xiao-Lin Liao; Gen-Bo Xu; Ying Xu; Wen-Tao Song (Marine Biotechnology, 2012)

Immobilization of foreign protein into polyhedra of Bombyx mori nucleopolyhedrovirus (BmNPV) - Xing-wei Xiang; Rui Yang; Lin Chen; Xiao-long Hu; Shao-fang Yu; Cui-ping Cao; Xiao-feng Wu (Journal of Zhejiang University-SCIENCE B, 2012)

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

A Novel Mutation in CACNA1S Gene Associated with Hypokalemic Periodic Paralysis Which has a Gender Difference in the Penetrance - Fei-Feng Li; Qian-Qian Li; Zhen-Xuan Tan; Si-Yao Zhang; Ji Liu; Er-ying Zhao; Gui-Chun Yu; Jin Zhou; Li-Ming Zhang; Shu-Lin Liu (Journal of Molecular Neuroscience, 2012)

The expression of PCNA, c-erbB-2, p53, ER and PR as well as atypical hyperplasia in tissues nearby the breast cancer - Zongliang Jia; Wei Zhao; Lin Fan; Wei Sheng (Journal of Molecular Histology, 2012)

Meta-analysis of new genome-wide association studies of colorectal cancer risk - Ulrike Peters; Carolyn M. Hutter; Li Hsu; Fredrick R. Schumacher; David V. Conti; Christopher S. Carlson; Christopher K. Edlund; Robert W. Haile; Steven Gallinger; Brent W. Zanke; Mathieu Lemire; Jagadish Rangrej; et al. (Human Genetics, 2012)

Genetic diversity of ‘Cadidatus Liberibacter solanacearum’ strains in the United States and Mexico revealed by simple sequence repeat markers - Hong Lin; Md Sajedul Islam; Yang Bai; Amin Wen; Suque Lan; Neil C. Gudmestad; Edwin L. Civerolo (European Journal of Plant Pathology, 2012)

Vegetative Ecological Characteristics of Restored Reed (Phragmites australis) Wetlands in the Yellow River Delta, China - Xuehong Wang; Junbao Yu; Di Zhou; Hongfang Dong; Yunzhao Li; Qianxin Lin; Bo Guan; Yongli Wang (Environmental Management, 2012)

Otolith Sr:Ca and Ba:Ca may give inconsistent indications of estuarine habitat use for American eels (Anguilla rostrata) - Brian M. Jessop; Chia-Hui Wang; Wann-Nian Tzeng; Chen-Feng You; Jen-Chieh Shiao; Shih-Huan Lin (Environmental Biology of Fishes, 2012)

Characteristics of Polycyclic Aromatic Hydrocarbon Emissions of Particles of Various Sizes from Smoldering Incense - T. T. Yang; T. S. Lin; J. J. Wu; F. J. Jhuang (Bulletin of Environmental Contamination and Toxicology, 2012)

Glycated hemoglobin A1c is superior to fasting plasma glucose as an independent risk factor for colorectal neoplasia - Yao-Chun Hsu; Han-Mo Chiu; Jyh-Ming Liou; Chun-Chao Chang; Jaw-Town Lin; Hui-Hsiung Liu; Ming-Shiang Wu (Cancer Causes & Control, 2012)

Prediction of expansive soil swelling based on four micro-scale properties - Botao Lin; Amy B. Cerato (Bulletin of Engineering Geology and the Environment, 2012)

Heavy Metal Contamination in the Water-Level Fluctuating Zone of the Yangtze River within Wanzhou Section, China - Junjie Lin; Chuan Fu; Xudong Zhang; Kun Xie; Zhiguo Yu (Biological Trace Element Research, 2012)

Subsurface flow processes in sloping cropland of purple soil - Jialilang Tang; Bo Zhu; Tao Wang; Xunqiang Cheng; Meirong Gao; Henry Lin (Journal of Mountain Science, 2012)

Tail position affects the body temperature of rats during cold exposure in a low-energy state - Yuki Uchida; Ken Tokizawa; Mayumi Nakamura; Cheng-Hsien Lin; Kei Nagashima (Journal of Comparative Physiology A, 2012)

Cervid satellite DNA and karyotypic evolution of Indian muntjac - Yueh-Chun Li; Chyi-Chyang Lin (Genes & Genomics, 2012)

Perturbed solving method for interdecadal sea-air oscillator model - Jiaqi Mo; Yihua Lin; Wantao Lin; Lihua Chen (Chinese Geographical Science, 2012)

Bait worm packaging as a potential vector of invasive species - Christina L. Haska; Charles Yarish; George Kraemer; Noreen Blaschik; Robert Whitlatch; Huan Zhang; Senjie Lin (Biological Invasions, 2012)

G6PD Genotype and Its Associated Enzymatic Activity in a Chinese Population - Wei Ying Jiang; Bing Yi Zhou; Guo Long Yu; Han Liu; Jing Bo Zeng; Qun Di Lin; Hong Li Xi; Hua Liang (Biochemical Genetics, 2012)

Quantification of ecosystem carbon exchange characteristics in a dominant subtropical evergreen forest ecosystem - Yue-Lin Li; Guo-Yi Zhou; De-Qiang Zhang; Katherine Owen Wenigmann; Dennis Otieno; John Tenhunen; Qian-Mei Zhang; Jun-Hua Yan (Asia-Pacific Journal of Atmospheric Sciences, 2012)

A prospective clinical study in hepatitis B e antigen-negative chronic hepatitis B patients with stringent cessation criteria for adefovir - Minghao Ha; Guotong Zhang; Shu Diao; Mingfang Lin; Liping Sun; Huiyuan She; Chenbao Kuan; Lihui Shen; Chunhong Huang; Wenjuan Shen; Zhongming Huang (Archives of Virology, 2012)

High incidence of acute promyelocytic leukemia specifically induced by N-nitroso-N-methylurea (NMU) in Sprague–Dawley rats - Yun-Ching Chang; Jeng-Dong Hsu; Wea-Lung Lin; Yi-Ju Lee; Chau-Jong Wang (Archives of Toxicology, 2012)

2,5-Hexanedione induces human ovarian granulosa cell apoptosis through BCL-2, BAX, and CASPASE-3 signaling pathways - Yan Sun; Yuan Lin; Hong Li; Jin Liu; Xiaohua Sheng; Wenchang Zhang (Archives of Toxicology, 2012)

Application of the Similarity Parameter (λ) to Prediction of the Joint Effects of Nonequitoxic Mixtures - Dayong Tian; Zhifen Lin; JianQing Ding; Daqiang Yin; Yalei Zhang (Archives of Environmental Contamination and Toxicology, 2012)

HepG2 cells infected with Klebsiella pneumoniae show DNA laddering at apoptotic and necrotic stages - Pei-Yin Yang; Wen-Xin Chen; Fong-Yin Chang; Hui-Wen Chen; Chun-Hung Lin; Yu-Chun Hsu; June Hsieh Wu (Apoptosis, 2012)

Unsteady inter-porosity flow modeling for a multiple media reservoir - Ren-Shi Nie; Ying-Feng Meng; Yong-Lu Jia; Jian-Lin Shang; Yong Wang; Jian-Guo Li (Acta Geophysica, 2012)

Extension of the growing season due to delayed autumn over mid and high latitudes in North America during 1982–2006 - Wenquan Zhu; Hanqin Tian; Xiaofeng Xu; Yaozhong Pan; Guangsheng Chen; Wenpeng Lin (Global Ecology and Biogeography, 2012)
Aim We intend to characterize and understand the spatial and temporal patterns of vegetation phenology shifts in North America during the period 1982–2006. Location North America. Methods A piecewise logistic model is used to extract phenological metrics from a time‐series data set of the normalized difference vegetation index (NDVI). An extensive comparison between satellite‐derived phenological metrics and ground‐based phenology observations for 14,179 records of 73 plant species at 802 sites across North America is made to evaluate the information about phenology shifts obtained in this study. Results The spatial pattern of vegetation phenology shows a strong dependence on latitude but a substantial variation along the longitudinal gradient. A delayed dormancy onset date (0.551 days year −1 , P = 0.013) and an extended growing season length (0.683 days year −1 , P = 0.011) are found over the mid and high latitudes in North America during 1982–2006, while no significant trends in greenup onset are observed. The delayed dormancy onset date and extended growing season length are mainly found in the shrubland biome. An extensive validation indicates a strong robustness of the satellite‐derived phenology information. Main conclusions It is the delayed dormancy onset date, rather than an advanced greenup onset date, that has contributed to the prolonged length of the growing season over the mid and high latitudes in North America during recent decades. Shrublands contribute the most to the delayed dormancy onset date and the extended growing season length. This shift of vegetation phenology implies that vegetation activity in North America has been altered by climatic change, which may further affect ecosystem structure and function in the continent.

Vertical stratification of subsurface microbial community composition across geological formations at the Hanford Site - Xueju Lin; David Kennedy; Jim Fredrickson; Bruce Bjornstad; Allan Konopka (Environmental Microbiology, 2012)
Summary Microbial diversity in subsurface sediments at the Hanford Site 300 Area near Richland, Washington state (USA) was investigated by analysing 21 samples recovered from depths of 9–52 m. Approximately 8000 near full‐length 16S rRNA gene sequences were analysed across geological strata that include a natural redox transition zone. These strata included the oxic coarse‐grained Hanford formation, fine‐grained oxic and anoxic Ringold Formation sediments, and the weathered basalt group. We detected 1233 and 120 unique bacterial and archaeal OTUs (operational taxonomic units at the 97% identity level) respectively. Microbial community structure and richness varied substantially across the different geological strata. Bacterial OTU richness (Chao1 estimator) was highest (> 700) in the upper Hanford formation, and declined to about 120 at the bottom of the Hanford formation. Just above the Ringold oxic–anoxic interface, richness was about 325 and declined to less than 50 in the deeper reduced zones. The deeper Ringold strata were characterized by a preponderance ( c . 90%) of Proteobacteria . The bacterial community in the oxic sediments contained not only members of nine well‐recognized phyla but also an unusually high proportion of three candidate divisions (GAL15, NC10 and SPAM). Additionally, 13 novel phylogenetic orders were identified within the Deltaproteobacteria , a clade rich in microbes that carry out redox transformations of metals that are important contaminants on the Hanford Site.

Automatic extraction of parallel edges based on eigenvalue analysis and collateral expansion - Yi Lin; Juha Hyyppä (International Journal of Remote Sensing, 2012)

A new isoflavone from the mangrove endophytic fungus Fusarium sp. (ZZF60) - Zhongjing Huang; Jianxiang Yang; Zhigang She; Yongcheng Lin (Natural Product Research, 2012)

A comparative policy analysis of the Clean Development Mechanism in South Africa and China - John Fay; Farai Kapfudzaruwa; Lin Na; Shirley Matheson (Climate and Development, 2012)

Oil-Spill Monitoring in the Coastal Waters of Hong Kong and Vicinity - Yuanzhi Zhang; Hui Lin; Qiang Liu; Jinrong Hu; Xiaofeng Li; Kin Yeung (Marine Geodesy, 2012)

Expression, purification, and characterization of alanine racemase from Pseudomonas putida YZ-26 - Jun-Lin Liu; Xiao-Qin Liu; Ya-Wei Shi (World Journal of Microbiology and Biotechnology, 2012)

Water Resources Flows Related to Urbanization in China: Challenges and Perspectives for Water Management and Urban Development - Chao Bao; Chuang-lin Fang (Water Resources Management, 2012)

An Experimental Study of CO2 Exsolution and Relative Permeability Measurements During CO2 Saturated Water Depressurization - Lin Zuo; Samuel Krevor; Ronald W. Falta; Sally M. Benson (Transport in Porous Media, 2012)

Detection of trends in precipitation extremes in Zhejiang, east China - Ye Tian; Yue-Ping Xu; M. J. Booij; Shengji Lin; Qingqing Zhang; Zhanghua Lou (Theoretical and Applied Climatology, 2012)

AURKB and MAPK involvement in the regulation of the early stages of mouse zygote development - Lin Xu; Tong Liu; Feng Han; ZhiHong Zong; GuoLi Wang; BingZhi Yu; Jie Zhang (Science China Life Sciences, 2012)

L-type calcium current in right ventricular outflow tract myocytes of rabbit heart - ShengHui Liang; ChenHui Lin; Yuan Li; TaiFeng Liu; Yan Wang (Science China Life Sciences, 2012)

Reasons for lower transformation efficiency in indica rice using Agrobacterium tumefaciens-mediated transformation: lessons from transformation assays and genome-wide expression profiling - Weiwei Tie; Fei Zhou; Lei Wang; Weibo Xie; Hao Chen; Xianghua Li; Yongjun Lin (Plant Molecular Biology, 2012)

Waking with the hypothalamus - Helmut L. Haas; Jian-Sheng Lin (Pflügers Archiv - European Journal of Physiology, 2012)

Bp5250 inhibits vascular endothelial growth factor-induced angiogenesis and HIF-1α expression on endothelial cells - Kuan-Ting Lin; Jin-Cherng Lien; Ching-Hu Chung; Sheng-Chu Kuo; Tur-Fu Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2012)

Soluble expression and purification of Brucella cell surface protein (BCSP31) of Brucella melitensis and preparation of anti-BCSP31 monoclonal antibodies - Lei Zhang; Xing An Wu; Fang Lin Zhang; Cui Hong An; Yang Xin Sun; Wen Tao Bai; Zhi Kai Xu (Molecular Biology Reports, 2012)

Differential effects of Cucumber mosaic virus satellite RNAs in the perturbation of microRNA-regulated gene expression in tomato - Junli Feng; Leiyu Lai; Ruohong Lin; Chunzhi Jin; Jishuang Chen (Molecular Biology Reports, 2012)

Cloning and characterization of β-catenin gene in early embryonic developmental stage of Artemia sinica - Xiang Li; Lin Hou; Jian Ma; Yudong Liu; Luping Zheng; Xiangyang Zou (Molecular Biology Reports, 2012)

AP-2β enhances p53-mediated transcription of the αB-crystallin gene through stabilizing p53 - Xiang Hu; Lin Wang; Wei Sun; Ling Xiao; Yuan Wu; Yiming Zhuo; Dongsong Nie; Jianlin Zhou; Jian Zhang (Molecular Biology Reports, 2012)

An upstream regulatory element confers orientation-independent enhancement of the TSG101 promoter activity in transformed cells - Shih-Fang Hsu; Yih-Gang Goan; Hsien-Yu Tsai; Yi-Ru Lin; Rue-Tsuan Liu; Jiin-Tsuey Cheng (Molecular Biology Reports, 2012)

The cyclophosphamide metabolite, acrolein, induces cytoskeletal changes and oxidative stress in Sertoli cells - Feng Liu; Xu-Liang Li; Tao Lin; Da-Wei He; Guang-Hui Wei; Jun-Hong Liu; Lu-Sheng Li (Molecular Biology Reports, 2012)

Matrix metalloproteinase-9 as new biomarkers of severity in multiple organ dysfunction syndrome caused by trauma and infection - Lin Teng; Min Yu; Jun-ming Li; Hua Tang; Jing Yu; Li-hua Mo; Jing Jin; Xian-zhe Liu (Molecular and Cellular Biochemistry, 2012)

Association between polymorphisms in the signal transducer and activator of transcription and dilated cardiomyopathy in the Chinese Han population - Ying Peng; Bin Zhou; Yanyun Wang; Yu Chen; Hui Li; Yaping Song; Lin Zhang; Li Rao (Molecular and Cellular Biochemistry, 2012)

Simvastatin protects osteoblast against H2O2-induced oxidative damage via inhibiting the upregulation of Nox4 - Wei Huang; Wei-lin Shang; De-hao Li; Wen-wen Wu; Shu-xun Hou (Molecular and Cellular Biochemistry, 2012)

Nicotine promotes proliferation and collagen synthesis of chondrocytes isolated from normal human and osteoarthritis patients - Xiaozhou Ying; Shaowen Cheng; Yue Shen; Xiaojie Cheng; Ferdinand An Rompis; Wei Wang; Zhongqin Lin; Qingyu Chen; Wei Zhang; Dongquan Kou; Lei Peng; Xin Qiao Tian; et al. (Molecular and Cellular Biochemistry, 2012)

Shotgun proteomics and network analysis of ubiquitin-related proteins from human breast carcinoma epithelial cells - Jian Zhou; Deng Bi; Yong Lin; Ping Chen; Xianchun Wang; Songping Liang (Molecular and Cellular Biochemistry, 2012)

ADAM17 regulates prostate cancer cell proliferation through mediating cell cycle progression by EGFR/PI3K/AKT pathway - Ping Lin; Xicai Sun; Tian Feng; Haifeng Zou; Ying Jiang; Zijun Liu; Dandan Zhao; Xiaoguang Yu (Molecular and Cellular Biochemistry, 2012)

Chronic alcohol intake-induced oxidative stress and apoptosis: role of CYP2E1 and calpain-1 in alcoholic cardiomyopathy - Ling Jing; Cheng-mei Jin; Shan-shan Li; Feng-min Zhang; Lin Yuan; Wei-min Li; Ying Sang; Shuang Li; Li-jun Zhou (Molecular and Cellular Biochemistry, 2012)

Analysis of promoter activity of PtDrl02 gene in white poplars - Huiquan Zheng; Yang Lei; Zhiyi Zhang; Shanzhi Lin; Qian Zhang; Wenfeng Liu; Juan Du; Xinmin An; Xiyang Zhao (Journal of Plant Biochemistry and Biotechnology, 2012)

Application of a simple binary mixing model to the reconstruction of lead pollution sources in two Mississippi River floodplain lakes - Richard B. Brugam; Michael Ketterer; Laylonda Maines; Zhi Qing Lin; William A. Retzlaff (Journal of Paleolimnology, 2012)

Hydrodynamic change recorded by diatoms in sediments of Liuxihe Reservoir, southern China - Jing Liu; Zhangwen Lin; Huajun Zhang; Bo-Ping Han (Journal of Paleolimnology, 2012)

Role of interleukin 1 beta in esophageal squamous cell carcinoma - Miao-Fen Chen; Ming-Shian Lu; Ping-Tsung Chen; Wen-Cheng Chen; Paul-Yang Lin; Kuan-Der Lee (Journal of Molecular Medicine, 2012)

Therapeutic inhibition of fatty acid oxidation in right ventricular hypertrophy: exploiting Randle’s cycle - Yong-Hu Fang; Lin Piao; Zhigang Hong; Peter T. Toth; Glenn Marsboom; Peter Bache-Wiig; Jalees Rehman; Stephen L. Archer (Journal of Molecular Medicine, 2012)

Gambogenic acid-induced time- and dose-dependent growth inhibition and apoptosis involving Akt pathway inactivation in U251 glioblastoma cells - Hong-Bo Chen; Lan-Zhen Zhou; Lin Mei; Xiao-Jun Shi; Xiao-Shan Wang; Qing-Lin Li; Laiqiang Huang (Journal of Natural Medicines, 2012)

Growth inhibition and apoptotic effect of alpha-eleostearic acid on human breast cancer cells - Tingting Zhang; Yanping Gao; Yu Mao; Quanbo Zhang; Caiyu Lin; Ping Lin; Jie Zhang; Xiujie Wang (Journal of Natural Medicines, 2012)

A Promising CdSe@CdS-Quantum Dots-Cysteine for the Determination of Trace IgE by Solid Substrate Room Temperature Phosphorescence Immunoassay - Jia-Ming Liu; Li-ping Lin; Zhen-Bo Liu; Min-Lan Yang; Xin-xing Wang; Li-hong Zhang; Ma-lin Cui; Li Jiao (Journal of Fluorescence, 2012)

Donor-Acceptor Compound Based on Rhodanineacetic Acid-Pyrene Derivative: Red-Light Emitting Fluorescent Organic Nanoparticles - Bo Zhang; Wei Diao; Chun Bi; Jian Sun; Guoxia Han; Yi Shi; Li Sheng; Gui Yin; Lin Pu (Journal of Fluorescence, 2012)

Arsenic content, fractionation, and ecological risk in the surface sediments of lake - S. L. Wang; C. Y. Lin; X. Z. Cao; X. Zhong (International Journal of Environmental Science and Technology, 2012)

Exact timing of granulite metamorphism in the Namche-Barwa, eastern Himalayan syntaxis: new constrains from SIMS U–Pb zircon age - Wen Su; Ming Zhang; Xiaohan Liu; Jinfu Lin; Kai Ye; Xin Liu (International Journal of Earth Sciences, 2012)

Molecular genetic studies of gene identification for sarcopenia - Li-Jun Tan; Shan-Lin Liu; Shu-Feng Lei; Christopher J. Papasian; Hong-Wen Deng (Human Genetics, 2012)

Stable cell-surface expression of Japanese flounder growth hormone in yeast Saccharomyces cerevisiae and growth-promoting effect on juvenile fish by oral administration - Bin Liu; Xiao-Nan Zang; Xin-Fu Liu; Xue-Cheng Zhang; Ji-Lin Lei (Fisheries Science, 2012)

Effect of temperature on development and reproduction of Neoseiulus barkeri (Acari: Phytoseiidae) fed on Aleuroglyphus ovatus - Bin Xia; Zhiwen Zou; Pengxin Li; Peng Lin (Experimental and Applied Acarology, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

The backend design of an environmental monitoring system upon real-time prediction of groundwater level fluctuation under the hillslope - Hsueh-Chun Lin; Yao-Ming Hong; Yao-Chiang Kan (Environmental Monitoring and Assessment, 2012)

Characterizing hydrochemical properties of springs in Taiwan based on their geological origins - Cheng-Shin Jang; Jui-Sheng Chen; Yun-Bin Lin; Chen-Wuing Liu (Environmental Monitoring and Assessment, 2012)

Construction and characterization of a normalized cDNA library from the river snail Bellamya aeruginosa after exposure to copper - Zi-Cheng Li; Li-Hui An; Qing Fu; Ying Liu; Lei Zhang; Hao Chen; Xing-Ru Zhao; Li-Jing Wang; Bing-Hui Zheng; Lin-Bo Zhang (Ecotoxicology, 2012)

Down-regulation of matrix metalloproteinase-7 inhibits metastasis of human anaplastic thyroid cancer cell line - Szu-Tah Chen; Dah-Wel Liu; Jen-Der Lin; Fang-Wu Chen; Yu-Yao Huang; Brend Ray-Sea Hsu (Clinical & Experimental Metastasis, 2012)

Hyperhomocysteinemia and Related Genetic Polymorphisms Correlate with Ulcerative Colitis in Southeast China - Yi Jiang; Xuanping Xia; Wenxing Wang; Limiao Lin; Changlong Xu; Zhenzai Cai; Bo Zheng; Jihua Pei; Sujian Shen; Bing Xia (Cell Biochemistry and Biophysics, 2012)

A Novel Canine Model of Portal Vein Stenosis Plus Thioacetamide Administration-Induced Cirrhotic Portal Hypertension With Hypersplenism - Dexin Lin; Xianbin Wu; Xiaoke Ji; Qiyu Zhang; YuanWei Lin; WeiJian Chen; Wangxun Jin; Liming Deng; Yunzhi Chen; Bicheng Chen; Jianmin Li (Cell Biochemistry and Biophysics, 2012)

Anti-tumor Effects of All-trans Retinoic Acid are Enhanced by Genistein - Ren-Jie Zhou; Xue-Qin Yang; Dong Wang; Qian Zhou; Lei Xia; Meng-Xia Li; Lin-Li Zeng; Ge Wang; Zhen-Zhou Yang (Cell Biochemistry and Biophysics, 2012)

Inhibition of Lymphoma Cell Proliferation by Peroxisomal Proliferator-Activated Receptor-γ Ligands via Wnt Signaling Pathway - Jia-Jun Liu; Xue-Jun Dai; Yan Xu; Pei-Qing Liu; Yong Zhang; Xiao-Dan Liu; Zhi-Gang Fang; Dong-Jun Lin; Ruo-Zhi Xiao; Ren-Wei Huang; He-Qing Huang (Cell Biochemistry and Biophysics, 2012)

Comparing the benefits of screening for breast cancer and lung cancer using a novel natural history model - Ray S. Lin; Sylvia K. Plevritis (Cancer Causes & Control, 2012)

Cholecystectomy and risk of pancreatic cancer: a meta-analysis of observational studies - Genlai Lin; Zhaochong Zeng; Xiaolin Wang; Zheng Wu; Jian Wang; Chenggang Wang; Qiao Sun; Yixing Chen; Hongbo Quan (Cancer Causes & Control, 2012)

Bioaccessibility and Risk Assessment of Cadmium from Uncooked Rice Using an In Vitro Digestion Model - Lin-Sheng Yang; Xiu-Wu Zhang; Yong-Hua Li; Hai-Rong Li; Ying Wang; Wu-Yi Wang (Biological Trace Element Research, 2012)

Rapid change of AM fungal community in a rain-fed wheat field with short-term plastic film mulching practice - Yongjun Liu; Lin Mao; Xinhua He; Gang Cheng; Xiaojun Ma; Lizhe An; Huyuan Feng (Mycorrhiza, 2012)

Bacterial wilt of sweet potato caused by Ralstonia solanacearum in Taiwan - Yi-Jeng Chen; Yi-Sheng Lin; Wen-Hsin Chung (Journal of General Plant Pathology, 2012)

Variations in thermal physiology and energetics of the tree shrew (Tupaia belangeri) in response to cold acclimation - Lin Zhang; Peng-fei Liu; Wan-long Zhu; Jin-hong Cai; Zheng-kun Wang (Journal of Comparative Physiology B, 2012)

Comparative analysis of phase I and II enzyme activities in 5 hepatic cell lines identifies Huh-7 and HCC-T cells with the highest potential to study drug metabolism - Jie Lin; Lilianna Schyschka; Ruben Mühl-Benninghaus; Jan Neumann; Liping Hao; Natascha Nussler; Steven Dooley; Liegang Liu; Ulrich Stöckle; Andreas K. Nussler; Sabrina Ehnert (Archives of Toxicology, 2012)

The 3Cs provide a novel concept of bacterial species: messages from the genome as illustrated by Salmonella - Le Tang; Shu-Lin Liu (Antonie van Leeuwenhoek, 2012)

Is the isentropic surface always impermeable to the potential vorticity substance? - Chanh Q. Kieu; Da-Lin Zhang (Advances in Atmospheric Sciences, 2012)

Flow cytometry investigation of picoplankton across latitudes and along the circum Antarctic Ocean - Ling Lin; Jianfeng He; Yunlong Zhao; Fang Zhang; Minghong Cai (Acta Oceanologica Sinica, 2012)

The preliminary study of the high chlorophyll in the central Bohai Sea in summer - Yue Wang; Dexing Wu; Xiaopei Lin (Acta Oceanologica Sinica, 2012)

Carbon dynamics and community production in the Mississippi River plume - Xianghui Guo; Wei-Jun Cai; Wei-Jen Huang; Yongchen Wang; Feizhou Chen; Michael C. Murrell; Steven E. Lohrenz; Li-Qing Jiang; Minhan Dai; Justin Hartmann; Qi Lin; Randy Culp (Limnology and Oceanography, 2012)
Dissolved inorganic carbon (DIC), total alkalinity (TAlk), pH, and dissolved oxygen (DO) were determined in the Mississippi River plume during five cruises conducted in the spring, summer, and fall. In contrast to many other large rivers, both DIC and TAlk were higher in river water than in seawater. Substantial losses of DIC, relative to TAlk, occurred within the plume, particularly at intermediate salinities. DIC removal was accompanied by high DO, high pH, and nutrient depletion, and was attributed to high phytoplankton production. As a result, the carbonate saturation in the plume became much higher than in ocean and river waters. A mixing model was used to determine DIC removal. We provide evidence that the use of a two—end‐member (river and ocean) mixing model was valid during late summer and fall (low discharge period). However, for other periods we used salinity and TAlk to delineate a mixing model that included two river end members and an ocean end member. Net community production rates in the plume, estimated using a box model, peaked in the summer and were among the highest reported to date for large river plumes. In the summer and fall, biological production in the river plume consumed a majority of the available nutrients, whereas during the spring only a small fraction of the available nutrients were consumed in the plume. Biological production was the dominant process influencing pH and carbonate saturation state along the river—ocean gradient, whereas physicochemical dynamics of mixing played an important role in controlling the TAlk and DIC distributions of this large river plume.